Divergent formation pathways of soil particulate and mineral-associated organic carbon across soil depths under conservation tillage - Hong-Xuan Duan; Yu-Gang Tian; Cheng-Ze Yang; Qing Luo; Yang Liu; Zhi-Yan Hou; Rattan Lal; Yash Pal Dang; Zhi Dong; Xin Zhao; Hai-Lin Zhang (Applied Soil Ecology, 2026)

Phylogenomics and morphological evidence reveal a new genus Callibractia gen. Nov. (Apiaceae, Apioideae), a distinct alpine lineage of Sino-Himalaya shaped by uplift of the Pan-Tibetan Highlands - Zi-Xuan Li; Chang Peng; Xing-Jin He; Yu-Lin Xiao; Wei-Yan Tan; Li-Jia Liu; Song-Dong Zhou (Molecular Phylogenetics and Evolution, 2026)

Characterization of phosphorylated whey protein and its hydrolytic insoluble peptide aggregates - Hui Yang; Ru Lin; Yinuo Xiao; Xuan Shang; Shanshan Bai (International Dairy Journal, 2026)

Association of structural characteristics with immunostimulatory activity of pectic polysaccharides prepared from Tartary buckwheat sprouts by enzymatic degradation and partial acid hydrolysis - Lin Zhang; Bo Li; Xuan Gao; Mao-Qing Wang; Ya-Nan Cao; Mao-Ling Tan; Yi-Chen Hu; Liang Zou; Dan Li; Yong Deng; Jing-Wei Huang; Ding-Tao Wu (Food Research International, 2026)

Photothermal antibacterial bilayer films from konjac glucomannan/shellac: A Prussian blue-engineered strategy for preservation of fresh-cut Benincasa hispida - Xin Lei; Yueguang Wang; Xianrui Chen; Jing Zhang; Xuan Lin; Wenjun Guo; Xiuqing Guan; Chengrong Wen; Di Zhang; Lin Wang; Jie Pang (Food Research International, 2026)

CqSESN2 suppresses WSSV infection via the CqNrf2 antioxidant pathway in Cherax quadricarinatus - Yan Wang; Kai-Ming Cai; Xuan Zeng; Wen-lin Wu; Hai-Peng Liu (Fish & Shellfish Immunology, 2026)

Progressive fluorescence amplification of molecular rotors via G-run-length engineering of G-rich DNA scaffolds - Ruo-Yao Cui; Yu-Chao Cao; Yi-Xuan Gu; Ling-Li Zhao; Xu-Yang Shen; Ying Liu; Ying-Lin Zhou; Xin-Xiang Zhang (Analytica Chimica Acta, 2026)

Microplastic pollution and ecological risks in the wet season: Potential effects on bacterial communities and nitrogen cycling in a coastal watershed of Southeast China - Yaling Huang; Suofang Zhong; Wantao Lin; Shoufeng Zhang; Hua Jiang; Xuan Wang; Jingli Mu (Marine Pollution Bulletin, 2026)

Xanthopterin is likely responsible for the yellow-green flesh coloration in the Kumamoto oyster Crassostrea sikamea - Sheng Liu; Haixin Wang; Yicong Xuan; Youli Liu; Haiyan Zhang; Zhihua Lin; Qinggang Xue (Aquaculture, 2026)

Sediment pore-network architecture may shape spatial patterns of denitrification in freshwater littoral zones - Xuemei Zhao; Yi Zhu; Weijie Lin; Fangyu Liu; Xuan Huang; Huan Fang; Dongli She; Xiaoqin Sun; Yongqiu Xia (Water Research, 2026)

Integrated transcriptomic and metabolomic analyses reveal the involvement of AtGASA1 and AtGASA4 in salicylic acid pathway-associated immune responses in Arabidopsis - Jian-Bo Song; Ya-Ru Li; Zi-Xin Zhao; Xian-Zhi Zuo; Cai-Feng Wang; Min Huang; Shu-Fan Liu; Yu-Fan Chen; Wen-Qian Song; Lin Wang; Ying-Juan Wang; Xuan Huang (Plant Science, 2026)

Structure and bioactivity of protolimonoids from the root bark of Dictamnus dasycarpus Turcz. - Hua Yue; Zi-Xuan Li; Zi-Tong Hao; Dan Zeng; Jie Bao; Ling-Zhi Zhang; Xue-Man Lin; Hua Sun; Shu-Fang Li; Su-Juan Wang (Phytochemistry, 2026)

Hypurpurins A-P, furanolabdane diterpenoids from the aerial parts of Hypoestes purpurea and their bioactivities - Lin-Fen Ding; Bin Cheng; Mei-Yi Zhang; Shi-Huan Yin; Xin-Ying Wang; Lu Sai; Hui-ling Zhou; Xuan Jiang; Jia Su; Xing-De Wu (Phytochemistry, 2026)

Investigation of bacterial co-metabolism and electron transfer process in bioelectrochemical sensors - Lin Wang; Yuge Ma; Ziying Liu; Qiaochu Liang; Yan Wang; Liang Xuan; Chen Li; Yang Zhang (Journal of Water Process Engineering, 2026)

Cu-based MOFs@TiO2/PVDF composite membrane for efficient oil-water separation and bacterial isolation and sterilization - Lin-Lin Liu; Xue-Ling Zeng; Xuan Shi; Yu-Zhuo Fan; Wen-Yan Zeng; Ze-Hui Bai; Rong-Ke You; Xue-Qin Zhan; Fang-Chang Tsai; Ning Ma (Journal of Environmental Chemical Engineering, 2026)

Enhanced organic acid recovery and mechanism analysis using microbial electrosynthesis coupled with electrodialysis - Ziting Liu; Hao Liu; Lin Wang; Qiaochu Liang; Yan Wang; Liang Xuan; Chen Li; Yang Zhang (Journal of Environmental Chemical Engineering, 2026)

A loop-closed process for recovering high purity products from lithium leaching solution - Lin Chen; Wenjie Chen; Peng Chen; Xuan Chen; Duchao Zhang; Weifeng Liu (Journal of Environmental Chemical Engineering, 2026)

Liupao tea alleviates high-fat diet-induced obesity by re-establishing metabolic homeostasis of short-chain fatty acids and chenodeoxycholic acid - Yuru Tan; Xuancheng Wang; Anlong Song; Song Xu; Xueting Lin; Bao Yang; Jichu Luo; Ying Tong; Mingsen Wen; Xuan Guan; Peiting Li; Zhe Luo; et al. (Food Research International, 2026)

A high-throughput strategy for screening umami peptides from Chouguiyu based on peptidomics and machine learning-assisted molecular simulation - Sitong Lyu; Shichao Xuan; Fan Yang; Honglin Yu; Di Meng; Jianqing Zhou; Cristabelle De Souza; Zhe Zhang; Tongjie Liu; Huaxi Yi; Qingjuan Tang; Lanwei Zhang; et al. (Food Research International, 2026)

Preparation of plant-based meat analogues by soft matter method: Effects of NaCl concentrations and addition order - Jing-Wen Zhang; Qin Yang; Hui-Lin Li; Qing-Xuan Liu; Han-Qing Chen (Food Hydrocolloids, 2026)

Ventilation strategies for mold control during egg storage and transportation: A comprehensive evaluation integrating ITS sequencing and antibacterial efficacy - Wenbin Zhou; Yuanhang Shi; Yu Liu; Lin Xuan; Xuefeng Shi; Runzhe Wang; Jiajie Yang; Zhanpeng Wang; Junying Li; Guiyun Xu; Jiangxia Zheng (Food Control, 2026)

Seasonal variability and atmospheric drivers of particle-phase PFAS in PM2.5 near a municipal solid waste incineration facility in Nanchang, China - Xiaolu Liu; Dandan Huang; Zehui Zhang; Li Zhang; Xuan Lin; Chunyu Yan; Meng Chen; Renting Nie; Bai Gao; Wenjie Ma; Yuanyuan Liu; Haiyang Zhang (Environmental Pollution, 2026)

PFAS exposure is associated with retinal neurotoxicity in Chinese adolescents: Mechanistic insights from integrated toxicogenomic and in vitro analyses - Xing-Xuan Dong; Shi-Yi Gong; Yu-Hui Hu; Gang Liang; Hua Xu; Dan-Lin Li; Yun Zhao; Chen-Wei Pan (Environmental Pollution, 2026)

An objective detection method for tinnitus using memristors - Hui Ma; Xiaoyan Ma; Yingying Xuan; Zelin Cao; Lin Li; Kaikai Gao; Mengna Wang; Ruifeng Qiao; Qin Hu; Wentao Yan; Kun Wang; Haoyuan Wang; et al. (Chemical Engineering Journal, 2026)

Oral self-assembled nanomedicine orchestrates hierarchical regulation of the lipid–ROS–inflammation cascade for comprehensive therapy of non-alcoholic fatty liver disease - Jia-Jian Zhang; Yin-Sheng Tan; Chen-Lei Zhang; Yan Gui; Fan-Zhi Yan; Jie Hou; Xiang-Xuan Liu; Hua Kong; Meng-Ru Guo; Yang-Feng Cui; Xian-He Lin; Tao-Tao Fan; et al. (Chemical Engineering Journal, 2026)

Chemical constituents from the leaves of Yulania denudata and their chemotaxonomic significance - Zhen-Quan Li; Qiu-Ye Zhao; Hui-Ling Zhou; Shi-Huan Yin; Xuan Jiang; Xin-Ying Wang; Lu Sai; Lin-Fen Ding; Liu-Dong Song (Biochemical Systematics and Ecology, 2026)

An integrative framework linking substrate composition and physiological trade-offs to black soldier fly larval performance in organic waste valorization - Hongge Wang; Peiqi Yang; Xiaofei Wu; Zhaohai Bai; Lin Ma; Xuan Wang; Marcel Dicke; Feng Zhu (Waste Management, 2026)

Evaluation and forecasting of habitat suitability and thermal growth responses in the mud clam Geloina coaxans under climate change - Bing-Xian Liu; Yu-Yang Zhang; Cheng-Rui Yan; Zhan-Wei Zhao; Ning Zhang; Lin-Xuan Ma; Xian-Bo Qiu; Yun-Wei Dong (Marine Environmental Research, 2026)

Directional disparity between oysters and mud snails in modulating marine carbon sequestration - Zhou Zhang; Xuan Dong; Yu-Jia Lei; Zhi-Yong Guo; Shuang-Jie Tian; Chang-Lin Li; Miao-Jun Pan; Xiang-Li Tian; Yun-Wei Dong; Jing-Yu Li; Shuang-Lin Dong (Journal of Environmental Management, 2026)

PFAS associated with dysglycemia and glucose trajectories: a prospective cohort study from the Isomers of C8 Health Project in China - Wen-Qi Yang; Yun-Ting Zhang; Wen-Yu Wang; Haseeb Tufail Moryani; Muhammad Amjad; Zeeshan Mohammed; Xuan Liu; Yan-Xu Chen; Kun Zhao; Chu Chu; Yang Zhou; Li-Zi Lin; et al. (Environmental Pollution, 2026)

Co-exposure to PFAS, PFAS alternatives, and metals and liver function in Chinese adults - Shui-Yue Lu; Jing-Lin Zhang; Nuo Chen; Muhammad Amjad; Yun-Ting Zhang; Wan-Ting He; Xuan Liu; Yan-Xu Chen; Jia-Xin Zhou; Wen-Wen Bao; Yang Zhou; Li-Zi Lin; et al. (Environmental Pollution, 2026)

A framework for constructing a regional climate-adaptive landscape pattern: A case study in Chengdu-Chongqing urban agglomeration, China - Yunni Zhou; Qihan Xu; Xuan Wang; Qianna Wang; Yanyun Luo; Lin Peng (Environmental Development, 2026)

Pd single atoms anchored on mesoporous C3N5: An exceptional photocatalyst for hydrogen production - Yang Wang; Cun-Feng Fan; Jiao-Yan Li; Xiao-Qin Zheng; Xuan-Yi Liu; Ying Zhou; Jiahui Kou; Hengming Huang; Lin-Bing Sun (Chemical Engineering Journal, 2026)

Ultrahigh-resolution flexible quantum-dot light-emitting diodes via dual assembly and transfer printing - Xin Hu; Yangbin Zhu; Runzhen Sun; Zhen Wang; Jiayu Sun; Qinghong Lin; Yi Jiang; Hongyang Fu; Kejia You; Xuan Guo; Yue Wang; Deli Li; et al. (Chemical Engineering Journal, 2026)

Constructing hydrophobic carbon-encapsulated Fe5C2 catalysts for enhanced Fischer-Tropsch synthesis to olefins with reduced CO2 selectivity - Ranqing Zhang; Xuan Zhou; Derun Li; Kun Gong; Yunlei An; Jing Xin; Peipei Zhang; Yanfang Song; Yuanyuan Dai; Tiejun Lin; Liangshu zhong (Chemical Engineering Journal, 2026)

Multiomics, pharmacogenomic, and structural characterization of NCCRP1 as a candidate therapeutic target in ovarian cancer - Dahlak Daniel Solomon; Yung-Kuo Lee; Sachin Kumar; Kai-Fu Chang; Chung-Hsien Lin; Ching-Chung Ko; Ngoc Uyen Nhi Nguyen; Do Thi Minh Xuan; Neethu Palekkode; Chih-Yang Wang; Hui-Ru Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Maternal PAN2 selectively maintains mRNA Poly(A) tail homeostasis to regulate RNA degradation during oocyte-to-early embryo transition in mice - Xuan Wu; Hua Zhang; Yu-Ke Wu; Zhuo-Yue Niu; Jing-Wen Liu; Lu Chen; Jia-Jia Cao; Yu-Lin Chen; Shu-Yan Ji; Fa-Long Lu; Heng-Yu Fan (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Resource valorization of hazardous lead residue: A comparative evaluation of cleaner recovery for critical metals - Xuan Cui; Xuejin Liu; Xiaolei Li; Lianghong Duan; Jinxi Qiao; Guangmei Li; Xin Zhang; Xin Cai; Lin Tan; Qinghua Tian; Zhipeng Xu (Hydrometallurgy, 2026)

Environmental factors drive rutin accumulation through a synergistic network promoting flavonoid biosynthesis and suppressing hydrolysis in tea plants (Camellia sinensis) - Ping Xiang; Puzhen Xu; Yuanyuan Li; Marat Tukhvatshin; Qiufang Zhu; Huaxiu Gong; Yingying Wei; Jinliang Li; Qiliang Peng; Xuan Zhao; Jianghong Liu; Jinke Lin (Food Chemistry, 2026)

Postharvest properties and metabolomic profiling of cucumbers treated with hydrogen sulfide under low-temperature storage - Wei Han Foo; Mingmin Chen; Xue Zhao; Yu Xuan Lim; Lin Chen (Food Chemistry, 2026)

Functional characterization of STING in large yellow croaker (Larimichthys crocea), a pivotal regulator associated with TRIF, TRAF3, IRF3, and IRF7 in modulating antiviral signaling - Yi Lin Li; Jia Xi Zhang; Jun Chun Tang; Ying Li; Xuan Zhu; Jian Zhong Han; Yong Hua Jiang; Yi Lei Wang; Peng Fei Zou (Fish & Shellfish Immunology, 2026)

Nanoplastics reshape nitrogen cycling in submerged macrophyte systems: A metagenomic perspective - Weiliang Pan; Lin Zhang; Lin Liang; Lianfeng Du; Xuan Guo (Environmental Research, 2026)

Aging-Related Changes in the Injury Response of the Peripheral Nervous System - Yue-Yan Cen; Mu-Yun Wang; Qin-Xuan Song; Xin-Lin Gao; Cheng Zhou; Chun-Jie Li; Fei Liu; Yan-Yan Zhang; Jie-Fei Shen (Neuroscience Bulletin, 2026)
Peripheral nerve injury (PNI) significantly impairs patients’ quality of life, with elderly individuals experiencing particularly severe consequences due to aging-related declines in neuronal injury response and repair capabilities. Processes of the generation and transmission of injury signals, axonal disruption, initiation of regeneration, and the elongation of regenerating axons, as well as the subsequent reinnervation by these axons, are all significantly influenced by aging. These alterations are closely associated with changes in mitochondrial function, neuronal transport systems, a persistent inflammatory milieu, and various microenvironmental non-neuronal cells. Therefore, this review synthesized the pivotal role of aging in the multifaceted regulation of the nervous system following PNI and highlighted promising molecular regulatory mechanisms in the signaling pathways. Furthermore, it identified critical areas for future research, including unresolved questions in age-associated injury responses, potential targets for pharmacological intervention, and emerging therapeutic strategies meriting consideration for research and development.

Unveiling Key Factors in Determining Biodegradable Mulching Film Adoption Through Evolutionary Game Analysis - Wanying Lin; Xi Mo; Luca Nizzetto; Xuan Shi; Yuan Chen; Jinhui Li; Yan Lin (Bulletin of Environmental Contamination and Toxicology, 2026)

Role of NADPH oxidase generated O2− in seed germination and cold stress response of Brassica napus - Wei-liang Qi; Guo-yan Bao; Mei-ying Sun; Wen-juan Ma; Xuan-ting Yang; Xiang-hong Gao; Miao-xin Zhou; Qi-lin Wang (Protoplasma, 2026)

Genotyping-by-sequencing reveals microclimate-selected genotypes drive thermal tolerance variation in the clam Mactra veneriformis - Tian-Zhe Zhang; Liang Zhang; Zhi Hu; Lin-Xuan Ma; Yun-Wei Dong (Regional Studies in Marine Science, 2026)

Transcriptomic changes of starch and sugar conversion during storage of potato tubers treated with citronella essential oil - Xinxin Guan; Lei Zhu; Wenqiang Guan; Qianqian Zhang; Xuan Wang; Xingxing He; Qiong Lin (Postharvest Biology and Technology, 2026)

Tolypaxillines A–J: indole diterpenoids with neuroprotective activities from a soil-derived fungus Tolypocladium album DWS131 - Yu-Fen Tan; Xing-Yi Chen; Chao Wang; Ai-Lin Liang; Wen-Yu Lu; Le-Meng Feng; Qi Huang; Yue-Ping Jiang; Shao Liu; Xiao-Bo Xia; Jing Li; Wen-Xuan Wang (Phytochemistry, 2026)

Knowledge-driven multimodal feature selection fusion and collaborative learning for underwater object tracking - Ning Li; Huimin Deng; Yuanzhi Zhang; Lin Huang; Jiahui Yin; Chunhua Zhu; Xuan Fei; Binglin Wu (Ocean Engineering, 2026)

Westerly reorganization driven by orbital forcing: Late Miocene aridification in the Tarim Basin, Central Asia - Dong Wang; Qingqing Qiao; Chuang Xuan; Zhuangzhuang Lv; Sunyi Dong; Gangqiang Li; Long Ma; Yudong Chen; Zhanwei Lin; Zhongyin Gao (Global and Planetary Change, 2026)

Cretaceous sediment provenance, dispersal systems, and tectono-paleogeography of the western Tarim Basin, Northwest China: Far-field effects of Neo-Tethyan flat subduction - Hong-Xiang Wu; Feng-Qi Zhang; Cai-Yun Wang; Xiao-Gan Cheng; Kai-Xuan An; Yildirim Dilek; Cai Chen; Yu-Qing Zhang; Xiu-Bin Lin; Shuan-Hong Zhang; Han-Lin Chen (Global and Planetary Change, 2026)

TDCIPP induces placental dysfunction and fetal growth restriction via oxidative stress-mediated PINK1/Parkin mitophagy - Ziming Lin; Mingqi Hu; Ruijie Li; Xiaorui Gong; Man Zhao; Haiyan Zhang; Jin Xuan; Wenlan Qiao; Anna Li (Food and Chemical Toxicology, 2026)

Structural degradation of olivine LiMn0.6Fe0.4PO4 under high-voltage charging induced by Mn-ion migration - Xuan Cao; Yingge Zhang; Shu Zhang; Zejing Lin; Chao Li; Jiuhui Han (Chemical Engineering Journal, 2026)

Short-term hot spring balneotherapy ameliorates sleep disorders: wrist-worn wearable-assessed sleep improvement associated with neuroimmune, tryptophan metabolic and gut microbiome alterations - Xiao Zhang; Yue Zou; Xiao-qin He; Yi-hang Xu; Hong-xia Li; Fen Yang; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Si-fan Hao; Meng-meng Wang; et al. (International Journal of Biometeorology, 2026)

Rapid and efficient detection of Mycoplasma pneumoniae via an ERA/Cas12f1_ge4.1-coupled colloidal gold lateral flow assay - Hangxi Liu; Honghua Tang; Jian Liu; Sheping Zhang; Piaoting Wen; Mei Lin; Xuan Zhou; Mingqi Jiao; Zhongliang Deng (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Correction to: Isolation of Proteus sp. Closely Related to P. Vulgaris (Vulgaris/hauseri Complex) from Ornamental Koi (Cyprinus rubrofuscus) and its Pathogenicity - Crystal Jia Jing Lim; Hung Hui Chung; Melinda Mei Lin Lau; Cindy Jia Yung Kho; Leonard Whye Kit Lim; Kristene Ling Yong; Pei Xuan Hew (Current Microbiology, 2026)

Effects of Temperature on Artificial Breeding and Early Development of Osteochilus salsburyi - Yang Yang; Yutian Gong; Guoliang Li; Qi Su; Shifeng Guan; Haitao Zheng; Lin Xu; Feng Chen; Xuan Zhao; Zhiming Zhang (Fishes, 2026)
To determine the optimal water temperature range for artificial breeding and early development of Osteochilus salsburyi, six water temperature gradients (14, 18, 22, 26, 30, and 34 °C) were set to systematically investigate the effects of water temperature on artificial reproduction efficiency, embryonic development, the morphology of newly hatched larvae, larval growth performance, and the timing of organ development in O. salsburyi. The results showed that the spawning induction rate of O. salsburyi reached 100% at 14–30 °C. The fertilization rate and hatching rate peaked at 18–22 °C, and no fertilization was completed at 34 °C. The malformation rates of embryos and larvae showed a U-shaped change, with the lowest malformation rate at 18 °C, and the teratogenic effect of high-temperature stress was more significant. The embryonic development rate was significantly negatively correlated with water temperature, and the development duration was significantly shortened with increasing water temperature. Embryonic development was arrested and all embryos died at 34 °C, while hatching could be completed at 14 °C but with an excessively long cycle. The morphological indicators of newly hatched larvae showed differentiated sensitivity to water temperature; total length, pre-anal length, and body height were highly sensitive indicators, and larvae exhibited balanced and robust morphological development at 18–22 °C. The larval survival rate first increased and then decreased with increasing water temperature, reaching the highest rate at 22–26 °C. The absolute growth increment, relative growth increment, and specific growth rate (SGR) continued to increase with increasing water temperature. The timing of larval organ differentiation and behavioral development was significantly advanced with increasing water temperature. Late organ development of larvae was blocked at 14 °C, only early development was completed at 34°C, and the internal and external organs of larvae developed completely and in an orderly manner at 18–30 °C. In summary, the optimal water temperature for artificial breeding and early development of O. salsburyi is 18–26 °C, among which 18–22 °C is the best for artificial reproduction and 22–26 °C is optimal for larval rearing. The results can provide a scientific basis for the precise regulation of water temperature in large-scale seedling production of O. salsburyi.

Analytical study of Bragg reflection by an array of rectified cosinoidal bars or trenches on a fringing reef flat - Jian-Jian Xie; Ming-Xuan Zhu; Yun-Lin Ni; Jinbao Wang (Ocean Engineering, 2026)

Association between lipid oxidation, water activity and aflatoxin B1 risk reversal in stored sunflower seeds: A storage microenvironment observation study - Sen Zeng; Jiamin Song; Xuan Ou; Tinyan Sang; Siying Lin; Ruixia Zhang; Jie Chen; Yuhua Tang; Songlei Wang; Yanan Sun (Journal of Stored Products Research, 2026)

Effects of inoculum sources from different depths and oxygen concentration on bioleaching and microbial community assembly in mine waste dump - Zi Han Lin; Bing Zhou; Chen Sheng Zhang; Xuan Qi Zhang; Yan Bo Chen; Min Liang Fei; Xiao Fei Wei; Zhang Zheng Cai; Tian Shou Hu; Jie Hu; Han Ke (Journal of Hazardous Materials, 2026)

A bibliometric and visualization analysis of electrochemical phosphorus recovery research from 1994 to 2024 - Xuan Lin; Lin Liu; Renguang Zhang; Yingxin Ding; Xin Liu; Mengni Zhang; Xiong Yang; Chao Huang (Journal of Environmental Chemical Engineering, 2026)

Dual-reductant synergy in vacuum: Sustainable upcycling of tellurium casting slag to 4N-grade purity - Chaosong Meng; Xuan Cui; Jinxi Qiao; Dong Li; Zhipeng Xu; Qinghua Tian; Guangmei Li; Xin Cai; Xin Zhang; Lin Tan (Journal of Environmental Chemical Engineering, 2026)

Copper nanoparticles enhance azo dye decolorization by Shewanella putrefaciens CN32: enhanced effect and underlying mechanisms - Bai-Hang Zhao; Rui-Xuan Liu; Bing-Lin Zhang; Xin-Yu Zhang; Xu-Ming Liu (Journal of Environmental Sciences, 2026)

Machine-learning-guided extraction optimization and physicochemical characteristic of GRAS microalgae proteins for sustainable food applications - Wei Han Foo; Mingmin Chen; Yu Xuan Lim; Lin Chen (Food Hydrocolloids, 2026)

Building performance evaluation of double-skin facade with thermotropic glazing in a reference office room of China - Xiaoqiang Hong; Xia Deng; Yilin You; Weiqiang Liu; Xuan Yang; Ruiyang Yang; Chenyuan Zheng; Yuehua Lin; Feng Shi (Energy and Buildings, 2026)

Synergistic engineering of zincophilic sites and hierarchical porosity in lignin-derived carbon nanofiber networks for ultra-high energy density flexible zinc-ion hybrid capacitors - Lin-Xuan Wu; Bo Wang; Jia-Long Wen; Zhan-hui Yuan; Tong-Qi Yuan (Chemical Engineering Journal, 2026)

Levels and emission factors of polycyclic aromatic hydrocarbons in night market cooking fumes - Thi-Hieu Le; Cindy Soo Yun Tan; Hsin-Chieh Kung; Riza P. Gumaling; Danielle E. Que; How-Ran Chao; Ying I. Tsai; Xuan-Thanh Bui; Guo-Ping Chang-Chien; Lin-Chi Wang (Atmospheric Environment, 2026)

Decoupling Risks in the Fringe: An Integrated SOM-PMF Framework for Spatially-Explicit PFAS Source Apportionment Across Surface–Groundwater Interfaces - Xuan Lin; Shengpin Yu; Dandan Huang; Yiwen Pan; Zehui Zhang; Li Zhang; Chunyu Yan; Xiaolu Liu; Bai Gao; Yuanyuan Liu; Wenjie Ma (Water, Air, & Soil Pollution, 2026)

Efficient DNA Extraction Coupled with Fluorescence Loop-Mediated Isothermal Amplification (LAMP) for On-Site Early Warning Detection of Vibrio parahaemolyticus - Fengyi Liu; Qilin Geng; Xue Sun; Jie Lin; Xuan Zhu; Danyang Wang; Xiao-Hua Zhang; Jingjie Hu; Shi Wang; Lisui Bao; Jia Lv (Marine Biotechnology, 2026)

DynamicDTA: Drug-Target Binding Affinity Prediction Using Dynamic Descriptors and Graph Representation - Dan Luo; Jinyu Zhou; Le Xu; Sisi Yuan; Xuan Lin (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Function and transcription of stoS gene of Xanthomonas campestris pathovar campestris - Kai-Xuan Lin; Hsiao-Ching Chang; Chih-En Li; Chao-Tsai Liao; Yi-Min Hsiao (Antonie van Leeuwenhoek, 2026)

Structurally diverse monoterpenoid indole alkaloids from Damnacanthus hainanensis as well as their potential anti-inflammatory and anti-HIV effects - Gui-Qiong Wu; Long-Cheng Cui; Ye-Ping Liu; Chen-Xu Yue; Lin-Xuan Li; Tian-Yu Wang; Yu-Shan Wang; Shu-Ri Li; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2026)

Subject-specific whole-lung CFPD coupled with PBPK/PD to predict inhaled bronchodilator response in asthmatic and healthy subjects - Prathish K. Rajaraman; Xuan Zhang; Alejandro P. Comellas; Eric A. Hoffman; Ching-Long Lin (Journal of Aerosol Science, 2026)

Nanostructured electrospun nitrocellulose: Stabilization mechanisms and degradation kinetics of organic stabilizers - Wen-Jie Xu; Xue-Ning Cheng; Zhong-Xuan Han; Zhan-Jun Yang; Shu-Na Zhao; Hao Liu; Mi Li; Lin Jiang (Fuel, 2026)

A novel direct solid pyrolysis coupled microplasma optical emission spectrometry for rapid determination of dithiocarbamates in food samples - Bing Qian; Xuan Zhu; Changhuang Lin; Qiong Wu; Meng Zhang; Bei Li; Bingjun Han (Food Chemistry, 2026)

Single-cell transcriptomics reveal PRRC1 as a malignant cell enriched driver of DNA repair and therapy resistance in glioblastoma - Sachin Kumar; Ming-Cheng Tsai; Dahlak Daniel Solomon; Juan Lorell Ngadio; Do Thi Minh Xuan; Ching-Chung Ko; Hung-Yun Lin; Meng-Chi Yen; I-Jeng Yeh; Yung-Kuo Lee; Hui-Ru Lin; Jian-Ying Chuang; et al. (DNA Repair, 2026)

Data-driven discovery of high-performance surface passivators for efficient and stable perovskite solar cells - Feiyi Zhou; Zeyu Wang; Shangshang Zhao; Xu Zhang; Qingyue Guo; Runze Dai; Fanxiang Meng; Huajie Lyu; Jun Wan; Yi Dong; Zhe Jin; Shanqing Yu; et al. (Chemical Engineering Journal, 2026)

Corrigendum to “Dissection of denitrification pathways and synergistic degradation mechanisms of functional microbial communities under per- and polyfluoroalkyl substances (PFAS) exposure”. [Biores. Technol. 444 (2026) 133926] - Li Zhang; Dandan Huang; Zehui Zhang; Xiaolu Liu; Xuan Lin; Bai Gao; Yuanyuan Liu; Wenjie Ma; Haiyang Zhang (Bioresource Technology, 2026)

Gene-Environment Interaction of Rims1 and Adolescent Social Isolation on Schizophrenia-Like Behaviors in Mice - Lian-Hong Lin; Wei-Min Li; Qian-Yun Wu; Shuang-Yan Li; Xu-Xuan Ma; Yuan Xu; Si-Fu Deng; Bin Zhang; Ji-Hong Liu (Neuroscience Bulletin, 2026)

Satellite-derived light exposure and ocular health: Bibliometric mapping of research trends and knowledge structure - Xuan Zhang; Yahan Yang; Danqi Zeng; Yang Liu; Haotian Lin; Qingling Zhang (Remote Sensing Applications: Society and Environment, 2026)

Improved method for adjusting natural frequency of structures via stacked piezoelectric ceramic actuators - Wei Lin; Chaodong Xue; Yingjie Ren; Xuan Yao; Yu Zhang; Xiongliang Yao (Ocean Engineering, 2026)

Microalgal–bacterial granule-based wastewater treatment: Effects of COD/N ratio on particle characteristics and nutrient removal - Mai-Duy-Thong Pham; Phuong-Thao Nguyen; Chitsan Lin; Chettiyappan Visvanathan; Xuan-Thanh Bui (Journal of Environmental Chemical Engineering, 2026)

Environmental risks and upcycling potential in ternary geopolymer development for oily sludge pyrolysis byproducts - Chenxu Zhong; Chujun Luan; Xuan Guo; Fawei Lin; Jingwei Li; Beibei Yan; Zhanjun Cheng; Eminov Ashraf Mamurovich; Bigaliev Aitkhazha Bigalievich; Guanyi Chen (Journal of Environmental Chemical Engineering, 2026)

CO2 hydrogenation to methanol achieves nearly 100% selectivity on ZnZrOx/MoS2 heterojunction by reducibility modulation - Xuan Zhang; Xin Tian; Keying Lin; Dong Feng; Baojun Ma (Fuel, 2026)

Intelligent recognition of the fermentation stage of baijiu based on multi-dimensional data fusion and interpretable machine learning - Lin Du; Junchao Zhou; Yongqing Tang; Xuan Liu; Jing Zhong; Bo Yang; Yuancheng He; Xianguo Tuo; Haiping Du (Food Research International, 2026)

Integrated multi-omics and machine learning reveal aroma profiles and brand fingerprints in various fermented mandarin fish - Jian Shi; Shichao Xuan; Sitong Lyu; Fengzhi Qiao; Qingjuan Tang; Naiyong Xiao; Mingyu Yin; Wenzheng Shi; Lanwei Zhang; Jianan Sun; Yongxiang Wu; Kai Lin (Food Bioscience, 2026)

Regulation of metal-support interaction for enhanced Fischer-Tropsch synthesis over Co/TiO2 catalysts - Xuan Zhou; Ding Du; Shan Qiao; Xiao Yang; Ranqing Zhang; Yuanyuan Dai; Tiejun Lin; Yunlei An; Liangshu Zhong (Chemical Engineering Journal, 2026)

Targeting PTGS2/NF-κB Pathway: MG-132’s Role in Reducing Ischemic Stroke Injury - Yong-Sheng Wang; Yuan-Cheng Huang; Yong-Qi Wang; Yi-Xuan Zheng; Ying-Ren Gao; Min-Xia Wu; Fang-Hong Gao; Hong-Zhang Wang; Kun Liu; Lin Yan (Biochemical Genetics, 2026)

Magnetoelastomer-based grain flow sensor for combine harvesters - Xin-Dong Ni; Mao-Lin Li; Fang-Lei Li; Zi-Xuan Dai; Chun-Xiao Xing; Feng Wang; Yan-Xin Yin; Du Chen; Zhi-Zhu He (Computers and Electronics in Agriculture, 2026)

Deformation response and damage evolution of subway station under earthquake and post-earthquake fire - Jun-Xing Rao; Zhen-Dong Cui; Zhang-Lin Zhu; Ke-Xuan Li (Tunnelling and Underground Space Technology, 2026)

Quercus variabilis Blume. Source-sink dynamics: Mechanistic responses to photosynthate feedback inhibition - Shan You; Xuan Wang; Dayong Fan; Lin Yi; Qihua Yuan; Qingxin Wu; Xinna Zhang (Plant Science, 2026)

Dynamics of the Arabian Sea thermocline and monsoon-climate coupling mechanisms over the past 55,000 years: Multi-proxy paleoenvironmental reconstruction - Feng Wang; Yunhai Li; Min Chen; Xuan Ding; Yunpeng Lin (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Low doses of chlorothalonil cause testicular impairment in mammals through the antimicrobial-like mechanism - Han-Zhang Wang; Yi-Ming Xiong; Shi-Lin Song; Qian-Cheng Zhao; Xuan-Yue Chen; Jing-Ran Gao; Yuan-Yuan Li; Zhan-Fen Qin (Journal of Hazardous Materials, 2026)

Multi-omics reveals efficient thiamethoxam biodegradation but altered flavor profile by native microbiota during Pixian broad bean paste fermentation - Xuan Yu; Siqi Huang; Jie Tang; Chuanning Peng; Qi Wen; Siqi Chen; Lanqi lei; Chenxi Yang; Yuanxi Liu; Wenliang Xiang; Qing Zhang; Hongbin Lin; et al. (International Journal of Food Microbiology, 2026)

Multi-stage study of pyrolysis kinetics, combustion characteristics, and fire modeling for selected nature wood species - Yi-Xuan Lin; Qiang Wang; Qi-Xian Li; Qing-Wen Lin; Peng-Rui Man; Shu-Nan Zhou; Yang Li; Jun Deng (Fuel, 2026)

Recombinant bovine lactoferrin ameliorates cold stress-induced immunosuppression by modulating the gut microbiota in mice - Lin-Lin Ding; Haiyan Sun; Xuan-Yi Xu; Yu Zhang; Ai-Mei Liao; Yin-Chen Hou; Ji-Hong Huang; Long Pan (Food Bioscience, 2026)

Redox imbalance and NF-κB activation drives 1,3-diphenylguanidine (DPG)-induced hepatotoxicity in grass carp (Ctenopharyngodon idella): HSP70 as a protective therapeutic target - Siwen Li; Ruijing She; Bixiao Lin; Keman Li; Yiang Bai; Xuan Xiong; Xingchao Liu (Environmental Research, 2026)

Periosteum-inspired lightweight aerogel composite for ultrahigh energy dissipation and dynamic impact perception - Qiankun Chen; Jianpeng Wu; Shuai Liu; Xinyi Wang; Shiyu Lin; Purun Wang; Xinglong Gong; Shaolin Ge; Ken Cham-Fai Leung; Shouhu Xuan (Chemical Engineering Journal, 2026)

Dissection of denitrification pathways and synergistic degradation mechanisms of functional microbial communities under per- and polyfluoroalkyl substances (PFAS) exposure - Li Zhang; Dandan Huang; Zehui Zhang; Xiaolu Liu; Xuan Lin; Bai Gao; Yuanyuan Liu; Wenjie Ma; Haiyang Zhang (Bioresource Technology, 2026)

Soybean Hyperspectral Leaf Area Index (LAI) Estimation Based On Soil-vegetation Separation Algorithm and Derivative Spectroscopy - Nai-ning Zhong; Yu-lin Liu; Yi-zheng Zhao; Yi-xuan Mei; Hao-lin Shen; Xin-Zhou Lei; Yu-ning Wu; Juan-li Ju; Youzhen Xiang (Journal of Soil Science and Plant Nutrition, 2026)

Isolation and characterization of the novel lytic Bacillus subtilis phage vB_Bsu_W1188 revealing a wall teichoic acid glycosylation-dependent resistance mechanism - Miao Wang; Guanhua Xuan; Hong Lin; Jingxue Wang (Archives of Virology, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Histone H3.3 phosphorylation facilitates H3K9me3-heterochromatin formation during retrotransposon silencing and X-chromosome inactivation via H3.3K27me3–CBX7–KAP1 axis - Jun Chen; Jiyu Chen; Zhouliang Yu; Liwei Zhang; Yanchao Liu; Xuan Ouyang; Juan Yu; Menghan Wang; Shangqiang Xie; Ming Wang; Tiantian Zhang; Zhaohui Jin; et al. (Science Bulletin, 2026)

Adjuvant-metal-ion-chelating PTEN mRNA with cell-membrane-coating augments the immune sensitivity for precise cancer immunotherapy - Mengyu Guo; Jin-Cheng Guo; Haodong Yao; Fene Gao; Lina Zhao; Lu Cai; Xuan Fan; Lin Bao; Xin Li; Xiaoyu Zhang; Mingdi Hu; Jie Mei; et al. (Science Bulletin, 2026)

Concurrent removal of cetirizine hydrochloride and biodiesel accumulation in Chlorella vulgaris - Wen-Bo Yan; Zhong-Hong Zhang; Guo-Hui He; Jia-Xuan Tang; Hui-Lin Guo; Yi-Fan Zhan; Wei-Dong Yang; Hong-Ye Li; Xiang Wang (Journal of Hazardous Materials, 2026)

Enhanced fluoxetine removal from water via Fe/Cu-doped biochar-activated percarbonate under sunlight and aeration - Yang Wu; Zhi-hao Li; Xi-xi Lu; Zi-xuan Lin; Chang-ping Yu (Journal of Environmental Chemical Engineering, 2026)

Corrigendum to “Influence of catechin–PAYCS interactions on gastrointestinal structural and bioactivity stability: Key mechanisms in digestive enzymes inhibition” [Food Chem. 490 (2025) 145132] - Jieqiong Chen; Chunyan Lin; Lijia Yang; Yang Liu; Guowan Su; Yehui Zhang; Weifeng Liu; Mouming Zhao; Xuan Zhao; Lihua Huang; Tiantian Zhao (Food Chemistry, 2026)

Flexible and compressible thermoelectric foam for temperature–pressure dual sensor - Po-Shen Lin; Meng Li; Yong-Qi Chen; Bo-Xuan Hu; Cheng-Liang Liu; Zhi-Gang Chen (Chemical Engineering Journal, 2026)

A multi-stimuli-responsive supramolecular polymer from γ-Cyclodextrin and Viologen for dual-mode display and ammonia/amines sensing - Dong-Xue Xia; Chen-Yan Xu; Dan-Xuan Pan; Ming-Fu Ye; Rui-Lian Lin; Jing-Xin Liu (Chemical Engineering Journal, 2026)

Injectable anti-inflammatory nanofiber hydrogel reprograms immunosuppressive tumor microenvironment via cascade-amplified immunogenic cell death - Ruo-Yun Zhang; Wei Yue; Yang Xuan; Long Qi; Lin-Lin Guo; Zhen-Zhen Zhu; Ming Yang; Zhang-Jie Pu; Guo-Qiang Li; Xin-Yi Mao; Ding Zhou; Zhao-Wei Zhang (Chemical Engineering Journal, 2026)

Isolation of Proteus sp. Closely Related to P. Vulgaris (Vulgaris/hauseri Complex) from Ornamental Koi (Cyprinus rubrofuscus) and its Pathogenicity - Crystal Jia Jing Lim; Hung Hui Chung; Melinda Mei Lin Lau; Cindy Jia Yung Kho; Leonard Whye Kit Lim; Kristene Ling Yong; Pei Xuan Hew (Current Microbiology, 2026)

Descent-rate-adaptive salinity correction for underway conductivity-temperature-depth profiler data - Xuan Wang; Zhigang Chen; Lin Cao; Shousheng Liu; Yang Zhou; Xu Chai; Jiliang Ding; Fei Wu; Fengxiang Guo; Xinyu Li; Zhigang Gai (Acta Oceanologica Sinica, 2026)

A bezafibrate bearing Pt(IV) prodrug triggers ferroptosis via modulating lipid metabolism in lung cancer cells - Neng Wan; Xuan-Lin Ren; Xiang-Yu Ma; Tao Zhu; Cheng-Zhi Xie; Jing-Yuan Xu; Xin Qiao (JBIC Journal of Biological Inorganic Chemistry, 2026)

Organochlorine pesticides (OCPs) in the sediment of the Bohai Sea in China: Slow phasing out but risk remaining - Xuan Shi; Jing Wang; Ming Xin; Chunye Lin; Baodong Wang; Hongguang Cheng; Mengchang He; Xitao Liu; Wei Ouyang (Marine Pollution Bulletin, 2026)

Molecular identification and population genetic analysis of a three-way cross hybrid abalone - Haichen Zhang; Qizhen Xiao; Weihong Lin; Zekun Huang; Benben Miao; Yang Gan; Chengyun Li; Caihuan Ke; Xuan Luo; Weiwei You (Aquaculture, 2026)

Sustainable production of high-purity crystalline FePO4 from sludge for battery electrodes - Xuan Wang; Yijiao Chang; Zhu Liang; Anjie Li; Yiru Wu; Bohua Wen; Bing Li; Feiyun Sun; Xiao-yan Li; Bruce E. Logan; Lin Lin (Water Research, 2026)

Clostridium perfringens can promote the formation of fatty liver in cows - Haolong Wang; Congzhu; Junhui Wang; Xuan Lin; YuYang Guo; Faisal Ayub Kiani; Xiaoshu Zhou; Yi Ding (Veterinary Microbiology, 2026)

Improving soil organic carbon sequestration through conservation tillage incorporating legume-based crop rotations - Wen-Xuan Liu; Zhuo Shi; Hai-Yan He; Bai-Jian Lin; Cong He; Yash Pal Dang; Xin Zhao; Hai-Lin Zhang (Soil and Tillage Research, 2026)

Spin valve effect in hybrid spin filters with Cr2Ge2Te6 - Xiaoyu Wang; Shuxi Wang; Ying Zhang; Yi Ding; Xueyan Dong; Lin Zou; Shaojie Liu; Miao He; Takashi Taniguchi; Kenji Watanabe; Xuan Pan; Lei Zhang; et al. (Science Bulletin, 2026)

Insecticide resistance monitoring and identification of ryanodine receptor mutations driving diamide resistance in Cnaphalocrocis medinalis - Hong-Shuang Li; Pin-Xuan Lin; Meng-Zhen Wang; Bei-Bei Dong; Cong-Fen Gao; Shun-Fan Wu (Pesticide Biochemistry and Physiology, 2026)

Rice SINA E3 ligases dichotomously control ERECTA1 ubiquitination and stability to regulate panicle morphogenesis and grain yield - Zi-Qi Lu; Tao Guo; Ying-Jie Cao; Jun-Xiang Shan; Wang-Wei Ye; Nai-Qian Dong; Yi Kan; Yi-Bing Yang; Shuang-Qin Guo; Jie-Jie Lei; Xiao-Rui Mu; Ji-Fu Zhou; et al. (Molecular Plant, 2026)

Photo-responsive imprinted cellulose nanocrystalline aerogels for selective terbium recovery and controlled desorption - Youming Zhu; Xudong Zheng; Jingbo Sun; Lin Guo; Xinmiao Pan; Xiang Gu; Xuan Ma; Jinfeng Mei; Zhongyu Li (Journal of Cleaner Production, 2026)

Greenhouse gas emissions and control measures for constructed wetland: A systematic review - Lin Zhang; Weiliang Pan; Chang Xu; Lianfeng Du; Xuan Guo (Journal of Environmental Management, 2026)

Unveiling the metabolic mechanism of pesticide in food fermentation through metagenomics and metabolomics: A case study of β-cypermethrin in Pixian broad-bean paste - Siqi Huang; Xuan Yu; Jie Tang; Chuanning Peng; Qi Wen; Siqi Chen; Lanqi lei; Chenxi Yang; Yuanxi Liu; Wenliang Xiang; Qing Zhang; Hongbin Lin; et al. (Food Chemistry, 2026)

Isomeric halide engineering of self-assembled hole-selective layers for efficient indoor perovskite photovoltaics - Zhong-En Shi; Yi-Ting Hong; Cheng-Chieh Lu; Po-Cheng Shih; Shih-I Lu; Hsiao-Chi Hsieh; Sie-Rong Li; Yu-Che Lin; Zheng-Xuan Cai; Yan-Duo Lin; Chih-Ping Chen (Chemical Engineering Journal, 2026)

Soil nutrient heterogeneity induces foraging behavior but does not improve overall growth performance in six bamboo species - Lin-Xuan He; Li-Li Zheng; Jia-Yu Zhang; Xiao-Mei Zhang; Jing-Pin Lei; Mai-He Li; Fei-Hai Yu (Plant and Soil, 2026)

Magnetic functionalized triazine based microporous organic network for efficient extraction of quinolone antibiotics in water and food samples: Adsorption mechanisms and analytical application - Zhe Zhao; Bolong Liang; Ming Su; Shumin Lin; Shu-Xuan Liang; Zhaohan Liu; Jianwei Zhao; Mao Peng (Analytica Chimica Acta, 2026)

Large-scale analysis of SARS-CoV-2 genomic data from sewage using eVarEPS reveals that amino acid mutations detected in sewage provide an early warning on population prevalence - Ziquan Lv; Chang Shu; Yulin Fu; Yinghui Li; Shisong Fang; Xiangjie Yao; Qinglan Sun; Kesheng Peng; Jian Lu; Guomei Fan; Dongmei Liu; Jinzhen Tang; et al. (Water Research, 2025)

Tunable surface potential nanomaterials for enhanced environmental nucleic acid extraction and surveillance - Jiahui Lv; Tong Li; Ying Liu; Bing Li; Peng Jia; Chuwei Ma; Hongjun Xiao; Guanghui Wang; Li Cheng; Jingkai Yang; Ziyi Xu; Xuan Tan; et al. (Water Research, 2025)

Corrigendum to “Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk” [Toxicology and Applied Pharmacology Volume 503, October 2025, 117465]. - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

Labdane-type diterpenoids from Hypoestes phyllostachya inhibit pancreatic cancer stem cells - Tong Yan; Lin-Fen Ding; Ya Chen; Guo-Xian Hu; Lu Qu; Ming Hu; Ya-Xuan Ma; Rong-Qing Yuan; Lin Jia; Mei-Ju Zhao; Liu-Dong Song; Jia Su; et al. (Phytochemistry, 2025)

Relating small waterbody denitrification with ecosystem respiration in an intensive anthropogenic region - Xuemei Zhao; Yi Zhu; Xu Yang; Li Zhang; Xuan Huang; Chunwang Li; Kebing Chen; Han Lin; Dongli She; Yongqiu Xia (Journal of Hydrology, 2025)

Diminishing heavy metal co-resistance aids in antibiotic resistome elimination from livestock manure - Xinyuan Zhang; Xuan Wang; Chunxu Song; Guanyu Zheng; Yubo Cao; Fenghua Wang; Zhaohai Bai; Lin Ma (Journal of Hazardous Materials, 2025)

Advances in thermoelectric coupling catalysis for CO2 reduction: Synergistic mechanisms, catalyst development, and application perspectives - Mengke Niu; Lei Wang; Linjie Cai; Jia Liu; Xuan Lin; Jun Yu; Sam Toan; Zhaoteng Xue; Dongsen Mao (Journal of Environmental Chemical Engineering, 2025)

PQS signaling and temperature variation modulate phage infection in Pseudomonas aeruginosa: Implications for foodborne pathogen control - Yinfeng Wang; Jiuna Kong; Yating Chen; Hong Lin; Xiuping Jiang; Guanhua Xuan; Jingxue Wang (International Journal of Food Microbiology, 2025)

Trade of crop products contribute to the alleviation of global nitrate leaching risks - Xuchong Chen; Ling Liu; Yu Lu; Xuan Wang; Zhaohai Bai; Lin Ma (Global Environmental Change, 2025)

Interaction effect among key volatile compounds on the aroma profile of chardonnay wine co-inoculated with Saccharomyces cerevisiae and Oenococcus oeni - Xueshan Yang; Liu Yang; Xuan Zhang; Lin Shi; Xia Zhu (Food Research International, 2025)

Remodelling membrane lipid composition through exogenous supplementation of stearic acid improves the survival rate of spray-dried Bifidobacterium animalis - Fengzhi Qiao; Jiadong Li; Zhi Duan; Fan Yang; Shichao Xuan; Wenhao Ding; Meijun Liu; Zhe Zhang; Tongjie Liu; Lanwei Zhang; Kai Lin (Food Research International, 2025)

Astaxanthin enhances broiler health via integrated regulation of antioxidant capacity, immune function, and gut microbiota - Xiao-Ming Gu; Ding-Cheng Ye; Jun-Wei Cheng; Zhi-Xin Lin; Hai-Xuan Lv; Zai-Xing Cai; Yun Yang; Chang-Kang Wang; Yu-Yun Gao; Ling Jin (Food Chemistry, 2025)

Construction of 4,5 ′- diaminodibenzo-18-crown-6-grafted graphene cellulose composite aerogel for efficient and selective adsorption of Cs+ from acidic aqueous solution - Lin Guo; Xudong Zheng; Xuan Ma; Xiang Gu; Xinmao Pan; Jinfeng Mei; Zhongyu Li (Environmental Research, 2025)

Upcycling plastic waste into high-value gases via pulsed joule heating for economic and carbon benefits - Zitong Wan; Xuan Xie; Yunfeng Ma; Guohua Zhu; Rong Jin; Bingcheng Lin; Minghui Zheng (Chemical Engineering Journal, 2025)

A carboxymethyl chitosan/oxidized alginate hydrogel with controlled fullerenol release accelerates diabetic wound healing through cellular senescence reprogramming - Ze-Bang Du; Qi Yuan; Ke-Jian Ni; Jie He; Jia-Shen Wu; Hai-Yan Huang; Yan-Yan Zhou; Xiao-Qing Li; Chang-Feng Zhu; Xiao-Xuan Chen; Li-Li Pan; Ran An; et al. (Chemical Engineering Journal, 2025)

An enhanced nanoenzyme for remodeling the inflammatory microenvironment and low-temperature photothermal cascade therapy for rheumatoid arthritis - Sui Zhou; Yong Li; Yi-Tong Zhou; Meng-Wen Ma; Kai-Lin He; Kai Cheng; Jin-Xuan Fan; Bo Liu; Ling-Li Dong; Yuan-Di Zhao; Xin Liu (Chemical Engineering Journal, 2025)

A functional self-assembled layer with preferential sodium adsorption sites for ultra-stable sodium metal batteries - Moazzam Ali; Asif Mahmood; Muhammad Ali; Samia Aman; Hamid Hussain; Xuan Zhang; Yinzhu Jiang; Xufeng Lin; Muhammad Yousaf (Chemical Engineering Journal, 2025)

Computational-assisted protein engineering to develop thermostable and highly active catalase for industrial and biocatalytic applications - Shuai Xu; Ya-min Chen; Xiang-yu Meng; Ru Pan; Ao-xuan Yan; Zhi-min Li; Zong-lin Li (Bioresource Technology, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Functional characterization of odorant binding proteins in Pharsalia antennata provides insights into diverse binding properties and the importance of C-terminal residues - Shu-Lin Li; Fu-Peng Li; Zi-Xuan Yang; Yu-Jie Zhao; Zhao-Qun Li; Nai-Yong Liu (Pesticide Biochemistry and Physiology, 2025)

Theoretical simulation-guided design and fabrication of molecularly imprinted hydrogels for selective osteopontin separation - Shichao Xuan; Wenhao Ding; Fengzhi Qiao; Yanbin Li; Shaolei Wang; Zhe Zhang; Changhong Ma; Huaxi Yi; Cristabelle De Souza; Lanwei Zhang; Kai Lin (Food Research International, 2025)

A Sn-Ta-O-doped vertical graphene electrochemical sensor based on a machine learning prediction model for monitoring cadmium in beverages - Zhiyu Tao; Lin Su; Mingji Li; Xiuwei Xuan; Cuiping Li; Hongji Li (Food Chemistry, 2025)

Exogenous supplementation of key membrane lipid precursors enhances freeze-drying resistance in Lacticaseibacillus paracasei K56 by modulating membrane composition - Fengzhi Qiao; Xia Ma; Ting Sun; Baolei Li; Shaolei Wang; Shichao Xuan; Pimin Gong; Weilian Hung; Lanwei Zhang; Kai Lin (Food Chemistry, 2025)

Layer-by-layer assembly mechanism of particulate-continuous phase for sandwich-like nanoparticles in oral colon-targeted protein delivery - Wen-Xuan Hu; Chang-Sen Jin; Si-Lin Li; Jia-Yang Fu; Liang-Sen Liao; Xiuzhu Yu; Shuang-kui Du (Food Chemistry, 2025)

Smartphone-assisted Ce-POM/CuBTC peroxidase-like colorimetric detection of H2O2 and ascorbic acid in food samples - Yiyi Zhang; Haibo Zhang; Chengyuan Ma; Yihang Yang; Xuan Mo; Yuan Shi; Zhijia Yin; Hong Li; Lin Sun (Food Chemistry, 2025)

Unraveling profiles of organic ultraviolet filters in coastal waters of the East China Marginal Seas - Zilan Wu; Xuan Jia; Xing Liu; Xiaodan Pei; Tian Lin; Jianzhong Li; Xi Liu; Yuan Gao; Ziwei Yao (Environmental Pollution, 2025)

Corrigendum to “Nanoplatforms derived from iron dextran combined with ascorbic acid for enhanced photothermal-chemodynamic therapy of tumors” [Chem. Eng. J. 496 (2024) 154044] - Bin Zhang; Xiao-Lin Hou; Xiao-Ting Xie; Lin-Fang Tan; Meng Guan; Dong-Hui Zhao; Sui Zhou; Kai Cheng; Jin-Xuan Fan; Bo Liu (Chemical Engineering Journal, 2025)

Dipyridinium salt-enhanced type II ROS photodynamic antibacterial nanofiber films for long-term preservation of blueberries - Xue-Qi Zhang; Xiuxian Zhu; Fei Guo; Zi-Ming Zhou; Yu-Ting Zhao; Lin-Xuan Song; Zhao-Yang Zhi; Zi-Hui Liang; Zhen-Ke Li; Chang-Hai Yi; Zhen Wang (Chemical Engineering Journal, 2025)

Micro-finned nanostructured superhydrophobic surfaces for high-performance steam condensation heat transfer at high concentrations of non-condensable gases - Wen-Ze Yang; Tian-Yu Zhang; Zhen-Yu Lu; Xuan-Yi Lin; Li-Wu Fan (Chemical Engineering Journal, 2025)

Dopant-driven phase engineering to achieve color-tunable self-trapped exciton emission and multicolor afterglow - Peng Zhang; Zenggang Lin; Wanying Xie; Wei Zhang; Xuan Miao; Yuzhu Yang; Wei Liu; Weisheng Liu (Chemical Engineering Journal, 2025)

Crystal facet optimization in cadmium sulfide/reduced graphene oxide-based photosynthetic biohybrid systems for enhanced light-driven biohydrogen production - Xue-Meng Wang; Zhi-Xuan Zhang; Lin Chen; Rong Chen; Wen-Wei Li (Bioresource Technology, 2025)

Spatial distribution, potential sources, and dry deposition fluxes of per- and polyfluoroalkyl substances (PFAS) in atmospheric particles (PM2.5) in the offshore eastern China sea (OECS) - Hao Sun; Shuai Sun; Xuan Jia; Yadi Lou; Xing Liu; Zilan Wu; Yitao Pan; Zhongsheng Lin; Ziwei Yao; Jianmin Chen (Atmospheric Environment, 2025)

Multi-decadal changes in convection-circulation coupled structure of the Madden–Julian oscillation - Lu Wang; Jiacheng Xia; Pang-chi Hsu; Xuan Zhou; Ming Sun; Lin Chen (Climate Dynamics, 2025)

The dietary supplementation with probiotic Bacillus cereus G1-11 improved the growth parameters, immune performances, intestinal histomorphology, and disease resistance of hybrid grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂) - Ming-Qing Zhang; Zhong-Xuan Zhong; Qian-Ping Du; Wen Li; Ya-Ting Zhu; Guang-Ting Xie; Feng-Ying Yan; Jin-Lin Yang; Shui-Sheng Li; Hu Shu (Animal Feed Science and Technology, 2025)

From growth to decline: The dynamic effects of maize-based cropping systems on soil organic carbon storage in Northeast China - Jin-Sai Chen; Zhuo Shi; Yu-Gang Tian; Hao-Ran Li; Hong-Xuan Duan; Zhi-Heng Qin; Jia Cheng; Yash Pal Dang; Bai-Jian Lin; Xin Zhao; Hai-Lin Zhang (Agriculture, Ecosystems & Environment, 2025)

PolInSAR forest height inversion considering parameter correlation and vertical polarization scattering differences - Yongsheng Liu; Dongfang Lin; Sichun Long; Xuan Wang; Kailin Zhu (Advances in Space Research, 2025)

Prevalence and genetic analysis of porcine circovirus type 3 (PCV3) in Henan Province of China during 2022-2024 - Lin-Lin Chen; Hao Li; Xuan-Ang Wang; Lan-Lan Zheng; Shi-Jie Ma; Hong-Ying Chen (Archives of Virology, 2025)

Comparative analysis of feed efficiency in Pacific abalone and its hybrid under varied environmental conditions - Wenchao Yu; Ziheng Yin; Yuehan Yan; Lin Cong; Miaoqin Huang; Xuan Luo; Caihuan Ke; Weiwei You (Aquaculture International, 2025)

Three new triterpenoids from the fruit of Eleutherococcus senticosus (Rupr.) Harms - Yan Liu; Yu-Xuan Lin; Xiao-Hui Rong; Meng-Meng Li; Juan Pan; Wei Guan; Hai-Xue Kuang; Bing-You Yang (Natural Product Research, 2025)

Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

New natural products from Rhododendron ciliicalyx subsp. Lyi - Chun-Lin Guo; Si-Xuan Liu; Lu Zhang; Ling Li; Yong-Fu Lu; Si-Yang Dai; Chang Li; Yue-Hu Pei (Phytochemistry Letters, 2025)

Separation and recovery of iron from vanadium extraction tailing slag by P204-P507 mixture collector flotation process - Yi-bo Wang; Jing-wei Li; Xiao-long Liu; Xin-fei Jiang; Yin-he Lin; Zhi Tian; Jun-jie Yin; Bing-qing Huang; Jia-xin Yang; Chen-xuan Wang; Zi-wang Wu; Shi-xing Ma; et al. (Journal of Environmental Chemical Engineering, 2025)

Construction of low-temperature regenerable dual-functional AlCeZr adsorbent and its synergistic conversion mechanism for simultaneous removal of COS and CS2 - Xiaoli Cao; Jianyu Xuan; Lin Zhang; Qun Cui; Haiyan Wang (Journal of Environmental Chemical Engineering, 2025)

Influence of catechin–PAYCS interactions on gastrointestinal structural and bioactivity stability: Key mechanisms in digestive enzymes inhibition - Jieqiong Chen; Chunyan Lin; Lijia Yang; Yang Liu; Guowan Su; Yehui Zhang; Weifeng Liu; Mouming Zhao; Xuan Zhao; Lihua Huang; Tiantian Zhao (Food Chemistry, 2025)

Habitat suitability assessment and prediction using a physiological species distribution model based on whole-genome genotyping and microclimate data - Bing-Xian Liu; Liang Zhang; Zhan-Wei Zhao; Lin-Xuan Ma; Xiao-Nie Lin; Ming-Ling Liao; Yun-Wei Dong (Estuarine, Coastal and Shelf Science, 2025)

An excellent-performance electrocatalyst in oxygen reduction reaction: Pt anchored on a bulk-engineered black titania synthesized by nitrogen gliding arc plasma - Xuan-He Li; Xiao-Song Li; Jing-Lin Liu; Xiaobing Zhu; Ai-Min Zhu (Chemical Engineering Journal, 2025)

Machine learning-assisted dual-mode hydrogel sensor for the detection of nitrite - Si-Qi Yang; Bao-Zhu Jia; Jie Liu; Fan-Xuan Gong; Hong Wang; Hong-Tao Lei; Zhen-Lin Xu; Lin Luo (Chemical Engineering Journal, 2025)

Dopant alliance: K/Cu cooperative bonds lock structural stability in P2-type sodium cathodes - Yu Duan; Jia-xuan He; Zi-han Ma; Shu-wen Chen; Ying-ying Huang; Shuo Bao; Jin-lin Lu (Chemical Engineering Journal, 2025)

Upcycling waste PET into benzoxazines with simultaneously low curing temperatures and high thermal stability - Dula Daksa Ejeta; Meng-Xuan Li; Yu-Kuan Hsu; Muhammad Javed Iqbal; Ching-Hsuan Lin (Chemical Engineering Journal, 2025)

Bioinspired phosphorylated cellulose nanocrystals-based multi-crosslinked binder for enhanced stability and sustainability in silicon anodes - Lan Zhao; Fengcai Lin; Haijun Li; Lingling Qian; Yingshan Shi; Zhiyi Cao; Xuan Yang; Biao Huang; Beili Lu; Hanyang Liu; Lirong Tang (Carbohydrate Polymers, 2025)

2-Arylbenzofurans from the stems and leaves of Artocarpus tonkinensis and their potential antiproliferative activities - Jia-Ming Guo; Lin-Xuan Li; Xin-Yi Li; Tian-Yu Wang; En-Ning Zhu; An-Jiao Wu; Shu-Ri Li; Hui- Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2025)

Behavioural plasticity to different thermal regimes during range expansion of the intertidal snail Nerita yoldii - Jun-Chi Ma; Lin-Xuan Ma; Jie Wang (Animal Behaviour, 2025)

Identification of segment joint and automatic segmentation for shield tunnel based on LiDAR detection - Shui-Long Shen; Jia-Xuan Zhang; Yu-Lin Chen; Annan Zhou (Tunnelling and Underground Space Technology, 2025)

Genomic analysis of Pseudoalteromonas sp. SD03 reveals its potential in chitin hydrolysis - Yu-Xuan Jiang; Wen-Yue Xu; Hui Liu; Si-Qi Lin; Sha-Sha Liu; Xi-Ying Zhang; Yan-Ru Dang (Marine Genomics, 2025)

Effect of salinity on the physico-chemical characteristics of microalgal-bacterial granules treating shrimp farming wastewater - Mai-Duy-Thong Pham; Xuan-Thanh Bui; Thi-Kim-Quyen Vo; Nhu-Nguyet Phan; Thien-Tai Nguyen; Ky-Phuong-Ha Huynh; Chitsan Lin; Chettiyappan Visvanathan (Journal of Water Process Engineering, 2025)

Biocrust effects on soil stability and hydrodynamic erosion in southern China's red soil - Jieling Wu; Ruibo Zha; Shiting Chen; Qin Zhou; Qiang Lin; Xuan Zha (Journal of Environmental Management, 2025)

Impact of marine chlorine emissions on secondary organic aerosols in North China Plain - Zhaoqi Gao; Lin Li; Zhou Liu; Jiangshan Mu; Zhuyi Wang; Bin Luo; Jingzhu Zhang; Shuting Tang; Hongliang Zhang; Jianlin Hu; Xuan Wang; Xuehua Zhou; et al. (Environmental Pollution, 2025)

Activation rate-dependent reconstruction of Co-MOFs for efficient CoOOH conversion in oxygen evolution reaction - Youlei Feng; Jinzhi Jia; Zehua Zou; Youxiu Lin; Xuan Zheng; Wenqiang Lai; Xiaoping Chen; Qingxiang Wang; Cailing Xu (Chemical Engineering Journal, 2025)

Single cobalt atoms anchored on in-situ-formed carbon layers within restricted microenvironment: an efficient catalyst for oxygen evolution reaction - Yang Wang; Ying Zhou; Xuan-Yi Liu; Xiao-Qin Zheng; Shui-Jing Wang; Kai Zhang; Xiang-Bin Shao; Jiahui Kou; Lin-Bing Sun (Chemical Engineering Journal, 2025)

Structural optimization and mechanical property analysis of butterfly valves based on Kriging surrogate model - Lei Shi; Tao Yang; JiangYan Ma; Lin Huang; Ao Tian; Yang Xuan; Yan Tian; Ran Gao (Building and Environment, 2025)

Plasma-Derived Small Extracellular Vesicles miR- 182 - 5p Is a Potential Biomarker for Diagnosing Major Depressive Disorder - Lin-Lin Zhu; Lian-Di Li; Xuan-Yu Lin; Jian Hu; Chun Wang; Yi-Jun Wang; Qi-Gang Zhou; Jing Zhang (Molecular Neurobiology, 2025)

Rheinheimera fenheensis sp. nov., Isolated from Fenhe River Basin, China - Xuan Shao; Yun-Lin Peng; Jin-Hang Guo; Zhao-Tong Chen; Hua-Ming Zhong; Di Meng; Hong-Jian Hou; Xi-Ying Zhang; Yong Zhao; Yi Li (Current Microbiology, 2025)

Anti-disintegration property of red soil treated with building gypsum powder - Yinlei Sun; Zhen Li; Xuan-Chen Lin; Qing-Ru Du; Xi Zou; Xianwei Zhang (Applied Clay Science, 2025)

Multi-omics analysis reveals BPF exposure causes hepatic glucose and lipid metabolism disorder in rats by disrupting energy homeostasis - Zhi Li; Yuanyuan Wu; Mingqing Qian; Bingya Zhang; Xinxin Deng; Penghui Mao; Zhonghua Fan; Xu Fang; Lin Cheng; Xuan Liu; Li Wang; Hui Liu (Toxicology, 2025)

A neoflavonoid from the stems and leaves of Paris tengchongensis and its inhibitory activity against vascular calcification - Yan Chen; Shicheng Wu; Xuan Chen; Lin Zhang; Xirong Chen; Ya Zhu (Phytochemistry Letters, 2025)

Two new ursane type triterpenoids from adult leaves of Cyclocarya paliurus - Shan-Xuan Zhang; Meng-Fei Liu; Yu-Ling Tan; Jin-Long Duan; Qiao-Lin Xu; Jian-Wen Tan (Phytochemistry Letters, 2025)

A critical need to control thallium contamination in aquatic ecosystem for the age of low carbon - Juan Liu; Wenhuan Yuan; Yu Shi; Yanyi Liu; Pei Li; Wanpeng Chen; Xuan Zeng; Ying Li; Ke Lin; Yinyin Lu; Haiyao Hu; Jin Wang (Journal of Hazardous Materials, 2025)

Fate, transport, and plant uptake of ricinine in soils amended with castor cake organic fertilizer - Ya-Hui Chuang; Kai-Xuan Zheng; Siu Chun Wong; Yu-Min Tzou; Sichao Wang; Shiou-Ruei Lin; Hsiao-Ying Yang; Chinn-Yuan Fu; Jerry J. Wu; Cheng-Hua Liu (Journal of Hazardous Materials, 2025)

Ionotropic receptors participate in the perception of sinigrin in Plutella xylostella adults - Zhi-Qiang Wei; Ya-Xin Wang; Ji-Xiang Wang; Xuan-Pu Luan; Chen Ding; Fan-Zheng Meng; Yu He; Qi Yan; Jin Zhang; Shuang-Lin Dong (Insect Biochemistry and Molecular Biology, 2025)

Synergistic effect of hollow n-Al/H-MoO3 in the gas-phase reaction zone of solid propellant - Shuping Li; Cheng Dong; Xuan Qi; Shiyong Chen; Lixiao Shen; Yinning Zeng; Yan Li; Zhenxin Yi; Lin Zhang; Shunguan Zhu (Fuel, 2025)

Effects of alkaline water-assisted tea polyphenol soaking on the physicochemical, biochemical, bacterial structure, and free amino acid composition of grass carp fillets during storage at 4 °C - Yilin Lin; Xie Xuan; Kabore Manegdebwaoga Arthur Fabrice; Yigang Yu; Lihua Huang; Yehui Zhang (Food Control, 2025)

Tracing disinfection byproducts during shock chlorination of a seawater reverse osmosis (RO) desalination pilot and the blended and chlorinated potable water produced - Thi Xuan Hoa Le; Yingying Xiang; Chii Shang; Chuanjing Lin; Kun Wang (Desalination, 2025)

Effect of cadmium-resistant Proteus mirabilis Ch8 on active ingredients and cadmium content of traditional Chinese medicine Ligusticum sinense cv. Chuanxiong - Ting Li; Lin Liu; Xiu-wen Bao; Fei-fei Liu; Xuan Zhang; Hao-ran Song; Si-jing Liu; Jing Bai; Qing-he Wang; Fei-lin Yang; Yang Li; Shu-qi Niu; et al. (Plant and Soil, 2025)

Research on Optimization Design of Ice-Class Ship Form Based on Actual Sea Conditions - Yu Lu; Xuan Cao; Jiafeng Wu; Xiaoxuan Peng; Lin An; Shizhe Liu (Journal of Marine Science and Engineering, 2025)
With the natural evolution of the Arctic route and advancements in related technologies, the development of new green ice-class ships is becoming a key technological breakthrough for the global shipbuilding industry. As a special vessel form that must perform icebreaking operations and undertake long-distance ocean voyages, an ice-class ship requires sufficient icebreaking capacity to navigate ice-covered water areas. However, since such ships operate for most of their time under open water conditions, it is also crucial to consider their resistance characteristics in these environments. Firstly, this paper employs linear interpolation to extract wind, wave, and sea ice data along the route and calculates the proportion of ice-covered and open water area in the overall voyage. This provides data support for hull form optimization based on real sea state conditions. Then, a resistance optimization platform for ice-class ships is established by integrating hull surface mixed deformation control within a scenario analysis framework. Based on the optimization results, comparative analysis is conducted between the parent hull and the optimized hull under various environmental resistance scenarios. Finally, the optimization results are evaluated in terms of energy consumption using a fuel consumption model of the ship’s main engine. The optimized hull achieves a 16.921% reduction in total resistance, with calm water resistance and wave-added resistance reduced by 5.92% and 27.6%, respectively. Additionally, the optimized hull shows significant resistance reductions under multiple wave and floating ice conditions. At the design speed, calm water power and hourly fuel consumption are reduced by 7.1% and 7.02%, respectively. The experimental results show that the hull form optimization process in this paper can take into account both ice-region navigation and ice-free navigation. The design ideas and solution methods can provide a reference for the design of ice-class ships.

Enhancing growth, pigment composition, polysaccharides, fatty and amino acid content in Ulva prolifera by manipulating temperature, light intensity, and photoperiod - Xuan Zhou; Mingzi Lin; Jianan Jiang; Shenyuan Liang; Han Xu; Wenrong Zhu; Nianjun Xu; Yahe Li (Aquaculture, 2025)

Mitigation of the toxic effects of nitrite: Role and mechanism of isoleucine in mitigating mitochondrial DNA leakage-induced inflammation in grass carp (Ctenopharyngodon idella) under nitrite exposure - Kai-Xuan Ren; Lin Feng; Pei Wu; Yang Liu; Hong-Mei Ren; Xiao-Wan Jin; Cheng-Bo Zhong; Xiao-Qiu Zhou; Wei-Dan Jiang (Journal of Hazardous Materials, 2025)

Effective treatment of Cu2+-containing acid mine drainage with acidic-cupric resistant electroactive biofilms - Jing Song; Xin Nong; You Li; Yifei Liao; Boyu Xu; Wuhao Zhang; Xuan Qin; Lin Liu; Yuguang Wang; Chenbing Ai (Journal of Environmental Management, 2025)

A modeling framework for assessing the future changes in the occurrence of extreme rain-induced landslides - Xinlong Zhang; Qigen Lin; Manhoi Lok; Taosheng Huang; Xuan Yu; Weiping Wang; Ping Shen (Gondwana Research, 2025)

Rapid evaluation of Curcuma origin and quality based on E-eye, flash GC e-nose, and FT-NIR combined with machine learning technologies - Qiang Guo; Ming-xuan Li; Rao Fu; Xin Wan; Wen-hao Dong; Chun-qin Mao; Zhen-hua Bian; De Ji; Tu-lin Lu; Yu Li (Food Chemistry, 2025)

Characteristics of inland ship and the effect of combined diesel oxidation catalyst (DOC) and diesel particulate filter (DPF) aftertreatment system on their pollutant emissions - Thi-Hieu Le; Zhi-Ping Hsu; Cindy Soo Yun Tan; Cheng-Di Dong; Chitsan Lin; Tsun-Lirng Yang; Xuan-Thanh Bui; Lin-Chi Wang (Environmental Pollution, 2025)

Effect of honeycomb core cell geometry on the sandwich tube for internal blast loading - Vuong Nguyen-Van; Ngoc San Ha; H. Nguyen-Xuan; Xiaoshan Lin; Yi Min Xie; Guoxing Lu (Engineering Structures, 2025)

Bisphenol AF induces lipid metabolism disorders, oxidative stress and upregulation of heat shock protein 70 in zebrafish - Bingya Zhang; Zhonghua Fan; Xuan Liu; Yuanyuan Wu; Lin Cheng; Li Wang; Hui Liu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Tunable containing malononitrile AIEgens with reversible mechanochromic behaviors and promising applications - Guang Yang; Wen-Xuan Zhao; Ling Liang; Zeng-Min Xue; Fei Meng; Yu-Qing Kong; Hong-Tao Lin; Shu-Hai Chen; Chuan-Zeng Wang (Chemical Engineering Journal, 2025)

Mitigating non-point source pollution in tea plantations: SWAT modeling and field validation of slow-release fertilizers - Chia-Chun Ho; Pin-Chih Shih; Li-Chi Chiang; Yi-Xuan Lin; Hsiu-Feng Liu; Wen-Guei Chang; Guan-Zhou Lin (Environmental Monitoring and Assessment, 2025)

Supervised functional state-space modeling for monitoring multigrade batch processes with irregular data using meta-learning - Lin-Xuan You; Jingxiang Liu; Junghui Chen (Process Safety and Environmental Protection, 2025)

Odorant receptor 75 is essential for attractive response to plant volatile p-anisaldehyde in Western flower thrips - Xuan-Pu Luan; Xiao-Tong Zhang; Zhi-Qiang Wei; Jin-Meng Guo; George F.O. Obiero; Merid N. Getahun; Qi Yan; Jin Zhang; Shuang-Lin Dong (Pesticide Biochemistry and Physiology, 2025)

Near-complete recovery of phosphorus from fresh human urine: Combining magnesium-air fuel cells with modified granular attapulgite - Lin-Jiang Zhong; Lin-Feng He; Hao-Ran Yang; Shu-Jie Hu; Di Wu; Meng-Yue Zhang; Ying Chen; Xuan Zhao; Hong Liu; Yuan Liu (Journal of Environmental Management, 2025)

Efficient CO2 hydrogenation to methanol: Enhancing surface oxygen vacancies of In-doped ZnZrOx catalysts - Xuan Zhang; Qiong Kang; Wei Wang; Keying Lin; Dong Feng; Baojun Ma (Journal of Environmental Chemical Engineering, 2025)

Differential magmatism and tectonic evolution during the rift stage within the Baiyun Sag of the Pearl River Mouth Basin in the northern South China Sea - Bo Yan; Xuan-Long Shan; Zhe Wei; Guo-Li Hao; Peng-Lin Zhang; Ling Ma; Zhi-Hao Wang; Pu-Jun Wang; N.G. Boriskina (Gondwana Research, 2025)

Dynamic variations in flavor profiles of Guizhou high-mountain white tea produced by Eurotium cristatum using solid-state fermentation - Su Xu; Linyao Song; Dajuan Shi; Siyao Wu; Fengwei Ma; Haijiang Chen; Qinglong Meng; Qiang Fei; Lingshuai Meng; Wenneng Wu; Dong Lin; Guangcan Tao; et al. (Food Bioscience, 2025)

Harnessing microalgae: Pioneering strategies for cost-effective EPA synthesis - Yi-Ting Shen; Zi-Xu Zhang; Xin Qi; Hong-Xuan Wu; Yan-Cheng Lin; Wang Ma; Guang Yang; Xiao-Man Sun (Food Bioscience, 2025)

Characterization and gelling properties of pectin extracted from Gardenia fruit - Xuan Wang; Tian Tian; Na Li; Lingling Zheng; Yuyao Wu; Wei Bian; Jian-Lin Wu; Tingting Zhou (Food Hydrocolloids, 2025)

Mass transfer analysis of a concentration-regulated metal-assisted chemical etching system and its application in Si nanohole fabrication - Jiecai Long; Xuan Zhang; Haojun Zhang; Haoya Wang; Congkai Xie; Xun Chen; Guohuai Lin; Yun Chen; Xin Chen; Huitao Liu; Renquan Lu (Chemical Engineering Journal, 2025)

Energy-saving and visual-thermal performance of multi-sectional DSF system in a typical office room across five climate zones in China - Feng Shi; Chenyuan Zheng; Junwei Lin; Xuan Yang; Yilin You; Mengsheng Yang; Xiaoqiang Hong (Building and Environment, 2025)

Mechanistic insights into the chlorination volatilization of oxidized heavy metals via novel staggered chlorination roasting - Chenglong Lu; Xuan Yu; Guohao Yang; Qianqian Guo; Long Jiao; Jinxiang Lin; Kai Deng; Yanjun Hu (Waste Disposal & Sustainable Energy, 2025)

Effects of Environmentally Friendly Aquaculture Chamber Coatings on Enzyme Activities, Histology, and Transcriptome in the Liver of Larimichthys crocea - Xuan Xu; Huayu Song; Huicai Wu; Lu Zhang; Fengjun Lin; Chonghui Chen; Xiaoxu Zhang; Yiying Liu; Chao Li; Qiang Fu (Marine Biotechnology, 2025)

Latitudinal patterns of reproduction in the intertidal mussel Mytilisepta virgata along the coast of China - Xiao-Ning Zhang; Xiao-Xu Li; Lin-Xuan Ma; Xin Qi; Ming-Ling Liao; Yun-Wei Dong (Marine Biology, 2025)

N6-methyladenosine-modified circ_0000517 promotes non-small cell lung cancer metastasis via miR-1233-3p/CDH6 axis - Weixian Lin; Lifang Huang; Zhu’an Ou; Yiwen Xuan; Daoqi Zhu; Qipeng Zhang; Enwu Xu (Journal of Molecular Histology, 2025)

ZCCHC3 inhibits PEDV proliferation by degrading nuclear coat proteins via the proteasome pathway - Zuyao Zhang; Shuangyang Wang; Huihui Sun; Jie Li; Jun Wang; Yangfan Li; Haichen Lin; Xuan Wang; Ruimin Bi; Zongyi Bo; Haixiao Shen; Liang Li; et al. (Veterinary Microbiology, 2025)

The depletion of TFAM and p-β-catenin(S552) in mitochondria in response to BoAHV-1 productive infection leads to decreased mitochondrial biogenesis - Jiayu Lin; Xiaotian Fu; Xuan Li; Xiuyan Ding; Shitao Li; Filomena Fiorito; Liqian Zhu (Veterinary Microbiology, 2025)

Discovery and configurations assignment of Ile/Leu-containing cyclic peptides with cytotoxic activity, Reniochpeptins A–D, from the marine sponge Reniochalina sp. - Shuai-Shuai Zhang; Zong-Mei Wu; Ying Wu; Ya-Jun Zeng; Yuan-Yuan Zhang; Xin-Li Lin; Si Zhang; Kai-Xuan Zhan; Hou-Wen Lin; Shu-Ping Wang (Phytochemistry, 2025)

The synergism between metabolic and target-site resistance enhances the intensity of resistance to pyrethroids in Spodoptera exigua - Yayun Zuo; Yakun Pei; Yuan Li; Shuang Wen; Xuan Ren; Lin Li; Yidong Wu; Zhaonong Hu (Insect Biochemistry and Molecular Biology, 2025)

In search of nanofiltration membranes for efficient lithium extraction from carbonate-type salt lakes - Ren-Jie Fan; Chun-Xu Zhang; Fujun Xiong; Lin-Hui Niu; Xiang-Xuan Ruan; Xiaohu Wang; Zhen-Yuan Wang; Mei-Ling Liu; Shi-Peng Sun; Weihong Xing (Desalination, 2025)

Metabolic engineering of Halomonas for effective production of tryptophan-derived compounds - Kai-Xuan Liu; Wei Chen; Yage Xiao; Ye Zheng; Xinying Xie; Weilin Li; Huaiming Wang; Hui Wang; Yi-Na Lin; Jian-Wen Ye (Chemical Engineering Journal, 2025)

Specifically targeted antimicrobial cyclic peptide to staphylococcal protein A for the treatment of S. aureus infection - Xiao-Ling Lei; Yong Li; Xue-Ting Cheng; Jie Zhuang; Fang Zhang; Xiao-Ting Xie; Lin-Fang Tan; Jin-Xuan Fan; Yuan-Di Zhao; Chuan-Liu Wu; Kai Cheng (Chemical Engineering Journal, 2025)

Chemical looping of catalytic methane decomposition with reverse Boudouard reaction using dual functional Ni-FeOx nanoparticle cluster for CO2-negative H2 production - Chien-Wei Wu; Zhi Xuan Law; Yu-Chun Zeng; Kun-Han Lin; De-Hao Tsai (Chemical Engineering Journal, 2025)

Interfacial engineered biomass-derived G/VMT-PCNCs networks as high-performance proton-conducting humidity sensors - Lirong Tang; Junwei Wu; Zhiyi Cao; Qiqi Hong; Fengcai Lin; Ningning Tan; Lan Zhao; Xinda You; Beili Lu; Xuan Yang; Biao Huang; Hanyang Liu (Carbohydrate Polymers, 2025)

Operant social seeking to a novel peer after social isolation is associated with activation of nucleus accumbens shell in rats - Adedayo Olaniran; Kristine T. Garcia; Megan A. M. Burke; Hongyu Lin; Marco Venniro; Xuan Li (Psychopharmacology, 2025)

Synergistic Regulation of Color Transformation by Nutrient Elements, Osmotic Regulators, and Antioxidant Enzymes in Erythrophleum fordii - Zi-Long Ouyang; Xiang-Lu Jia; Tian-dao Bai; Lin-juan Huang; Xuan Jiang; Wei-Chao Teng (Journal of Plant Growth Regulation, 2025)

Boosting propane combustion on dual active sites of Pt/WO3 through regulating Pt sites and activating propane on WO3 surface - Yi-Wei Xian; Bei Li; Cai-Hao Wen; Lin-Ya Xu; Wei-Xuan Lu; Qian Zhou; Wen-Zhi Jia; Meng-Fei Luo; Jian Chen (Fuel, 2025)

Investigation on fatigue performance and life prediction of PBL connectors in steel-UHPC composite structure - Yang Liu; Lin Xiao; Xing Wei; Xuan Liao; Shigang Wang (Engineering Structures, 2025)

Enhanced electron shuttle through S Doping-mediated interface modulation for promoting the degradation of chlorinated drugs by S-mZVImill/PDS - Hantong Qie; Xuan Pan; Zhen Zhang; Guoqiang Cai; Baoxin Xia; Aijun Lin; Wenjie Yang (Chemical Engineering Journal, 2025)

Association between sleep quality and serum biomarkers among long-term hot spring bathers: a cross-sectional study - Fen Yang; Yue Zou; Ying-ying Zhang; Hong-xia Li; Yi-hang Xu; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Yuan Yuan; Yun Zhou; Da-yong Zeng; et al. (International Journal of Biometeorology, 2025)

Complete genome analysis and biological characterization of phage vB_Bsu_hmny2 infecting Bacillus subtilis - Qihong Liu; Guanhua Xuan; Yinfeng Wang; Hong Lin; Jingxue Wang (Archives of Virology, 2025)

The bio-decolorization of methyl orange by S.putrefaciens CN32 and responding mechanism to salinity stress based on transcriptomic analysis - Bai-Hang Zhao; Bing-Lin Zhang; Bao-Yu Zhang; Rui-Xuan Liu; Xu-Ming Liu (Water Research, 2025)

Five brasilane-type sesquiterpenoids with neuroprotective activities from Xylaria nigripes - Hong-Ping Long; Xi Zhou; Si-Qian Zhou; Lan-Qing Li; Ai-Lin Liang; Wen-Yu Lu; Wen-Xuan Wang; Shao Liu; Jing Li; Ji-Kai Liu (Phytochemistry, 2025)

Harnessing oleaginous protist Schizochytrium for docosahexaenoic acid: Current technologies in sustainable production and food applications - Zongfan Peng; Liang Zhong; Yuqin Li; Siran Feng; Jinhua Mou; Yahui Miao; Carol Sze Ki Lin; Zhenyao Wang; Xuan Li (Food Research International, 2025)

Microbial diversity and antibacterial mechanism of slightly acidic electrolyzed water against Pseudomonas fluorescens in razor clam during storage - Xiaoting Xuan; Ziyi Zhang; Haitao Shang; Zheliang Sheng; Yan Cui; Xudong Lin; Shanqiao Chen; Lin Zhu (Food Research International, 2025)

Establishment and application of a high-performance liquid chromatography-mass spectrometry method for analysis of 15 bisphenols and halogenated phenols in tea - Zifan Hu; Weiyang Sun; Jiaqi Guo; Xuan Wang; Li Yong; Lin Ren; Dejian Feng; Xiaoli Zou (Food Chemistry, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Tuning photoluminescence and electroluminescence of multi-resonance thermally activated delayed fluorescence emitters through peripheral donor modification for highly efficient deep-blue OLEDs - Chen-Lu Hou; Sai Guo; Yu-Fu Sun; Jia-Xuan Hu; Hong-Jin Liao; Xiao Li; Fu-Lin Lin; Lingyi Meng; Xu-Lin Chen; Can-Zhong Lu (Chemical Engineering Journal, 2025)

High-affinity uric acid clearance based on motile β-CD/F-127 polyrotaxane microspheres for enhanced diabetic wound repair - Xinlin Jiang; Zipeng Wu; Xiaoru Tan; Yichen Lin; Hui Xing; Yinglin Xuan; Dong Ma; Xin Cui (Carbohydrate Polymers, 2025)

Plant diversity increases diversity and network complexity rather than alters community assembly processes of leaf-associated fungi in a subtropical forest - Jie Li; Xing-Chun Li; Hui-Yun Gan; Yue Zhang; Zi-Xuan Guo; Yu-Xuan Liu; Yong-Qing Lin; Liang-Dong Guo (Science China Life Sciences, 2025)

Late Quaternary slip rate of the Northern Margin Fault of the Huaizhuo Basin in the North China Block and its seismological implications - Lu-wei Li; Zhong-yuan Yu; Chun-miao Qiu; Wen-xuan Wang; Qian Zhao; Rong-ying Zheng; Yan-Lin Yang (Applied Geophysics, 2025)

α-asarone activates mitophagy to relieve diabetic encephalopathy via inhibiting apoptosis and oxidative stress - Xiao-dan Yan; Rong-hua Fan; Yu Wang; Xiao-xu Duan; Xuan Wei; Lin-sen Li; Qing Yu (Metabolic Brain Disease, 2025)

Aggregative Infestation of Nine Bostrichidae Species on the Madagascar Almond Tree, Terminalia neotaliala Capuron (Myrtales: Combretaceae) - Xiao-Lu Cao; Li Yu; Jian-Song Wei; Qiu-Hong Tao; Qian Lu; Wan-Xuan Wei; Xia-Lin Zheng (Neotropical Entomology, 2025)

Analysis of molecular advantages in offspring of large-sized Chinese mitten crabs based on reproductive lineage - Rongchen Liu; Xianrui Lin; Jinghao Hu; Jiajia Yang; Xuguang Li; Gang Wang; Yuzhu Yang; Yuchen Chen; Jianlin Pan; Weibing Guan; Yongxu Cheng; Jun Zhou; et al. (Aquaculture, 2025)

Improved soil organic matter monitoring by using cumulative crop residue indices derived from time-series remote sensing images in the central black soil region of China - Mei-Wei Zhang; Xiao-Lin Sun; Mei-Nan Zhang; Hao-Xuan Yang; Huan-Jun Liu; Hou-Xuan Li (Soil and Tillage Research, 2025)

Distribution characteristics and influencing factors of benthic diatoms on several typical beaches along the southern coast of China - Min Chen; Jiayu Li; Guobiao Huang; Yanting Lin; Shuting Zeng; Ya Xu; Xuan Liu; Feng Cai; Hongshuai Qi (Marine Environmental Research, 2025)

Unraveling carbon mineralization patterns and mechanisms in conservation agriculture: A global synthesis and multi-point experiment - Cong He; Jin-Sai Chen; Shou-Wei Han; Wen-Sheng Liu; Wen-Xuan Liu; Olatunde Pelumi Oladele; Yash Pal Dang; Rattan Lal; Xin Zhao; Hai-Lin Zhang (Journal of Cleaner Production, 2025)

Cis-regulation of the CYP6CS1 gene and its role in mediating cross-resistance in a pymetrozine-resistant strain of Nilaparvata lugens - Pin-Xuan Lin; Yu-Xuan Peng; Ji-Yang Xing; Zhao-Yu Liu; Fang-Rui Guo; Joshua A. Thia; Cong-Fen Gao; Shun-Fan Wu (Insect Biochemistry and Molecular Biology, 2025)

Contribution of phosphorylation modification by sodium tripolyphosphate to the functional properties of hollow zein nanoparticles - Sheng-qi Rao; Cao-chen Jia; Lin Du; Wei-biao Zhou; Wen-xuan Hu; Yi Jiang; Zhi-rong Wang; Zhen-quan Yang (Food Research International, 2025)

Uncovering characteristic and enantiomeric distribution of volatile components in Huangshan Maofeng and Zhejiang baked green teas - Yu-Hui Zhang; Pan-Deng Lei; Yong Ding; Xiao-Ting Zhai; Xiao-Chun Wan; Wei-Xuan Li; Yue Zhang; Hai-Peng Lv; Zhi Lin; Yin Zhu (Food Chemistry, 2025)

Insight into volatile metabolites and key odorants in black teas processed from Jianghua Kucha tea germplasm (Camellia sinensis var. assamica cv. Jianghua) - Ying-Lin Zhu; Wei-Xuan Li; Yu-Hui Zhang; Han Yan; Long-Yu Guo; Yue Zhang; Hai-Peng Lv; Ling-Hong Zhou; Zhi Lin; Wen-Liang Wu; Yin Zhu (Food Chemistry, 2025)

Deep eutectic solvent-based ultrasonic-assisted extraction of polyphenol from Chenopodium quinoa Willd.: Optimization and lipid-lowering activity - Xiao-tong Lin; Si-xuan Zhou; Zhi-peng Sun; Ming-yuan Cao; Tao Zhou; Li-yan Zhao; Gui-tang Chen (Food Chemistry, 2025)

Exploration of the impact of different drying methods on the quality of Gastrodia elata: A study based on drying kinetics and multidimensional quality evaluation - Ming-xuan Li; Bin Wang; Yu Li; Xin-ru Nie; Jing Mao; Qiang Guo; Nuo Xu; Rao Fu; Zhi-jun Guo; Xiao-li Zhao; Zhen-hua Bian; Tu-lin Lu; et al. (Food Chemistry, 2025)

Prenatal exposure on nanoplastics: A study of spatial transcriptomics in hippocampal offspring - Lei Tian; Jiang Chen; Xuan Liu; Yizhe Wei; Yiming Zhao; Yue Shi; Kang Li; Huanliang Liu; Wenqing Lai; Bencheng Lin (Environmental Pollution, 2025)

Sucrose non-fermenting 1-related protein kinase 2–14 participating in lipid elevating efficacy and biodiesel upgrade by Coccomyxa subllipsoidea - Yuanyuan Luo; Sisi Zhao; Zhixuan Fan; Yuqin Li; Zongfan Peng; Yulong Zhang; Siran Feng; Jinhua Mou; Zhenyao Wang; Carol Sze Ki Lin; Xuan Li (Chemical Engineering Journal, 2025)

Modulation of Fe0-FexSy heterostructure by sulfurization constitutes an electron transfer channel for efficient triclosan degradation - Hantong Qie; Xuan Pan; Daibing Hou; Zihan Wang; Xuedan Cui; Aijun Lin; Jun Cui; Wenjie Yang; Dan Zhao (Chemical Engineering Journal, 2025)

Engineered silicon-titania heterojunction elicits catalytic cancer cell death - Deliang Xu; Tingting Xu; Min Ge; Shibo Cao; Zhaoda Yu; Zhixin Chen; Ya-Xuan Zhu; Zhuang Liu; Ming Zong; Han Lin; Jianlin Shi (Chemical Engineering Journal, 2025)

Peroxisome-inspired T4 phage hybrid enzyme nanoreactors for photodynamic therapy of breast cancer - Xiao-Lin Hou; Lin-Fang Tan; Xiao-Ting Xie; Bin Zhang; Qiong Wang; Kai Cheng; Jin-Xuan Fan; Tian-Cai Liu; Bo Liu (Chemical Engineering Journal, 2025)

Microalgae − bacteria based wastewater treatment systems: Granulation, influence factors and pollutants removal - Mai-Duy-Thong Pham; Xuan-Thanh Bui; Thi-Kim-Quyen Vo; Thanh-Son Dao; Linh-Thy Le; Thi-Dieu-Hien Vo; Ky-Phuong-Ha Huynh; Thanh-Binh Nguyen; Chitsan Lin; Chettiyappan Visvanathan (Bioresource Technology, 2025)

Biotic plant-soil feedbacks alone do not explain why more diverse plant communities are less invasible - Hao-Ming Yuan; Xiao-Mei Zhang; Peter Alpert; Lin-Xuan He; Wei Xue; Lin Huang; Ling Peng; Fei-Hai Yu (Plant and Soil, 2025)

Light-emitting diodes affect plantlet growth of Spathiphyllum cannifolium by regulating photosynthesis and sucrose metabolism during ex vitro rooting - Shuo Yu; Kui-Hua Li; Hang-Lin Song; Yue Dai; Yin-Ji Jiang; Mei-Yu Jin; Xuan-Chun Piao; Mei-Lan Lian (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

NLRX1 in fish: A negative regulator of innate immunity during Edwardsiella piscicida infection via targeting TRAF6 through the NACHT domain - Binliang Wang; Xuan Lan; Sihan Lin; Hong Xu; Xiaodong Zhang; Junxia Yin; Yiwei Hu (Aquaculture, 2025)

Strategies for crop straw management in China's major grain regions: Yield-driven conditions and factors influencing the effectiveness of straw return - Jia Cheng; Bai-Jian Lin; Jin-Sai Chen; Hong-Xuan Duan; Yuan-Feng Sun; Xin Zhao; Yash Pal Dang; Zhi-Yu Xu; Hai-Lin Zhang (Resources, Conservation and Recycling, 2025)

Recent progress on triterpenoid derivatives and their anticancer potential - Zi-Xuan Zhao; Qiong-Yu Zou; Ying-Hong Ma; Susan L. Morris‐Natschke; Xiang-Yuan Li; Lin-Chun Shi; Guo-Xu Ma; Xu‐Dong Xu; Mei‐Hua Yang; Zi-Jian Zhao; Yuan-Xiang Li; Jing Xue; et al. (Phytochemistry, 2025)

Effect of microplastics concentration and size on pollutants removal and antibiotic resistance genes (ARGs) generation in constructed wetlands: A metagenomics insight - Lin Liang; Weiliang Pan; Merui Mu; Lin Zhang; Xiangyu Yang; Ruina Zhang; Lianfeng Du; Xuan Guo (Journal of Hazardous Materials, 2025)

Integrating traditional and biotechnological innovations for mitigating greenhouse gas emissions in dairy farming in China - Peixian Hao; Xiaofei Wu; Zelong Liu; Lijin Tian; Xiaohang Zhang; Xuan Wang; Zhaohai Bai; Lin Ma (Journal of Cleaner Production, 2025)

Comparative analyses of bacterial contamination and microbiome of broiler carcasses in wet market and industrial processing environments - Yuanyuan Zhou; Nan-lin Wang; Jin-qi Cen; Jia-tong Han; Yu-xuan Tang; Zi-qi Xu; Hang Zeng; Kurt Houf; Zhongjia Yu (International Journal of Food Microbiology, 2025)

Deciphering the distinct roles of polyketide synthase subunits in polyunsaturated fatty acid and lipid accumulation in Schizochytrium sp. - Hong-Xuan Wu; Wen-Qian Yang; Zi-Xu Zhang; Yan-Cheng Lin; Wang Ma; Xiao-Man Sun; He Huang (Food Bioscience, 2025)

Correlation study between structural parameters of droplets and rheological properties of O/W high internal phase Pickering emulsions above the closest packing density - Chenzhi Wang; Yan Li; Wei Xiong; Qiang Liang; Xin Hua; Pu Xuan; Wei Lin; Yingzheng Yao (Food Hydrocolloids, 2025)

Oil mist particulate matter induces myocardial tissue injury by impairing fatty acid metabolism and mitochondrial bioenergetics function via inhibiting the PPAR alpha signaling pathway in rats - Xuan Liu; Huanliang Liu; Huipeng Nie; Lei Tian; Yue Shi; Wenqing Lai; Zhuge Xi; Bencheng Lin (Environmental Pollution, 2025)

Confined ionic association and its effect on Li+/Mg2+ permselective transport through the HKUST-1 nanopore - Jianduo Zhang; Fucheng Dai; Jianbo Li; Dawei He; Xuan Lin; Xiaobin Jiang; Junjiang Bao; Xiaopeng Zhang; Gaohong He; Ning Zhang (Desalination, 2025)

Mitochondria-targeted delivery of zinc-coordinated resveratrol nanoparticles rescues the osteogenic potential of periodontal ligament stem cells compromised by inflammation for periodontal wound healing - Yu-Jie Tan; Xuan Li; Wen-Jie Zhang; Yu-Meng Cao; Jie-Kang Zou; Lin Jing; Dian Gan; Yu-Zhe Chen; Mei Xu; Ying An; Fa-Ming Chen; Xiao-Tao He; et al. (Chemical Engineering Journal, 2025)

Exploring the mechanism of ursolic acid in preventing liver fibrosis and improving intestinal microbiota based on NOX2/NLRP3 inflammasome signaling pathway - Qi Liu; Lin-Xiang Liu; Bi-Min Li; Wang Zhang; Yue Zhang; Peng Chen; Chen-Kai Huang; Yuan Nie; Xuan Zhu (Chemico-Biological Interactions, 2025)

ω-9 monounsaturated fatty acids in Sapindus mukorossi seed oil enhance calcium deposition expression of Wharton’s jelly mesenchymal stem cells - Yu-Xuan Huang; Yen-Chung Lin; Chin-Kai Lin; Haw-Ming Huang (Tissue and Cell, 2024)

Exploring the potential use of Caenorhabditis elegans as an animal model for evaluating chemical-induced intestinal dysfunction - Xiao-Pan Zhang; Xuan Ma; Jun-Ling Liu; Ai-Lin Liu (Toxicology and Applied Pharmacology, 2024)

Association of anthropogenic heat with asthma and related symptoms among children in China: A novel index reflecting climate change - Feng-Wen Shan; Xuan Liu; Ming-Kun Sun; Zhengmin Qian; Michael G. Vaughn; Niraj R. Chavan; Shu-Li Xu; He-Hai Huang; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; Li-Zi Lin; et al. (Sustainable Cities and Society, 2024)

Recycling waste tiles and waste catalysts for high-strength eco-porous ceramics in building applications - Ya-Wen Lin; Wei-Ting Lin; Bo-Xuan Zhang; Kae-Long Lin (Sustainable Chemistry and Pharmacy, 2024)

Carbonate precipitation-derived CO2 outgassing offsets the mineral weathering sink in the orogenic regime of southwestern Taiwan: Insights from triple Sr isotopes - Hou-Chun Liu; Yun-Cian Lin; Yan-Hong Chen; Meng-Xuan Li; Chen-Feng You; Kuo-Fang Huang; Wei-Jen Huang; Hung-Chun Chao (Science of The Total Environment, 2024)

Revealing the links between hair metal(loids) and alterations in blood pressure among children in e-waste recycling areas through urinary metabolomics - Hong-Xuan Kuang; Ye Liu; Jia-Rong Wang; Meng-Yang Li; Yang Zhou; Lin-Xue Meng; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

PM2.5-mediated cardiovascular disease in aging: Cardiometabolic risks, molecular mechanisms and potential interventions - Francis Chanda; Kai-xuan Lin; Abdallah Iddy Chaurembo; Jian-yuan Huang; Hui-juan Zhang; Wen-hui Deng; Yun-jing Xu; Yuan Li; Li-dan Fu; Hao-dong Cui; Chi Shu; Yang Chen; et al. (Science of The Total Environment, 2024)

A TT1–SCE1 module integrates ubiquitination and SUMOylation to regulate heat tolerance in rice - Hong-Xiao Yu; Ying-Jie Cao; Yi-Bing Yang; Jun-Xiang Shan; Wang-Wei Ye; Nai-Qian Dong; Yi Kan; Huai-Yu Zhao; Zi-Qi Lu; Shuang-Qin Guo; Jie-Jie Lei; Ben Liao; et al. (Molecular Plant, 2024)

Discovery of a polyurethane-degrading enzyme from the gut bacterium of plastic-eating mealworms - Jiakang Ru; Xuan Chen; Xuena Dong; Lin Hu; Jianli Zhang; Yu Yang (Journal of Hazardous Materials, 2024)

Comparison of environmental impacts from pyrolysis, gasification, and combustion of oily sludge - Hongdi Yu; Fawei Lin; Xuan Guo; Chujun Luan; Jiantao Li; Rundong Li; Lei Che; Wangyang Tian; Guanyi Chen (Journal of Hazardous Materials, 2024)

Increased atmospheric thallium threats to populated areas: A mini review - Juan Liu; Yaole Huang; Yanyi Liu; Shunlong Jiang; Qiong Zhang; Pei Li; Ke Lin; Xuan Zeng; Haiyao Hu; Yang Cao; Xinni Xiong; Jin Wang (Journal of Hazardous Materials, 2024)

Ultrasonic technology for predicting beef thawing degree and endpoint - Hongzhou Chen; Qing Sun; Lilei Xuan; Zitao Lin; Zeyu Yang; Xiaowei Huang; Zhihua Li; Wenjian Gao; Jun Ren; Jiyong Shi; Xiaobo Zou (Journal of Food Engineering, 2024)

Development of two-dimensional amyloid fibril/carboxymethyl cellulose hybrid membranes for effective adsorption of hexavalent chromium - You-Ren Lai; Xiao-Xuan Hou; Su-Chun How; Ta-Hsien Lin; Steven S.-S. Wang (Journal of Environmental Chemical Engineering, 2024)

Inhibitory mechanism of apigenin, quercetin, and phloretin on α-glucosidase - Xin Ren; Xuan Liu; Bu zhen Wang; Min Zhang; Lin xuan Wang (Food Bioscience, 2024)

Effects of salinity and temperature on the icing of sessile saltwater droplets on solid surfaces - Canjun Zhao; Zhifeng Hu; Yukai Lin; Xiaomin Wu; Xuan Zhang; Fuqiang Chu (Desalination, 2024)

Control of stepwise subduction and slab breakoff on volcanism and uplift in the Tibetan Plateau - Jian Wang; Zhi Wang; Xiugen Fu; Xuan-Ce Wang; Simon A. Wilde; Yi Fu; Jian Lin; Hengye Wei; Lijun Shen; Gang Rao; Ahmed Mansour (Earth and Planetary Science Letters, 2024)

Phase control and energy-trapping management for high quality X-ray afterglow imaging - Peng Zhang; Wanying Xie; Xuan Miao; Zenggang Lin; Yuzhu Yang; Wei Liu; Weisheng Liu (Chemical Engineering Journal, 2024)

Ru induced charge redistribution of MnO2 spheric nanozyme boosted hydrogen sulfide selective detection and cystathionine γ-lyase activity sensitive evaluation - Zhao Li; Xuan Zhang; Haorong Cheng; Zhongyuan Gu; Changchun He; Ju Wang; Xinxin Shi; Weidan Na; Tongxiang Li; Lin Tian (Chemical Engineering Journal, 2024)

Nano-fuels-driven self-sacrificed ZIF-8@Apt integrated chip coupled with a DNAzyme system for the isolation and detection of glioblastoma-derived extracellular vesicles - Zehan Zeng; Mingzhen Zhong; Tong Liao; Xuan Zhou; Lin Shi; Xin Zhang; Ye Zhang; Jingyan Feng; Yiqian Chen; Shuya Sheng; Jun Chen; Lei Zheng; et al. (Chemical Engineering Journal, 2024)

Assessment of multidimensional diversity and conservation of threatened timber trees in China under climate change - Jian-Lin Hu; Xiu-Qin Ci; Xiao-Yan Zhang; Run Zhou; Jian-Hua Xiao; Zhi-Fang Liu; Can-Yu Zhang; Xuan Jin; Jie Li (Biological Conservation, 2024)

Molecular properties, structure, neurotrophic and anti-inflammatory activities of cultured secondary metabolites from the cultures of the mushroom Cyathus striatus CBPFE A06 - Jing Wei; Mei-Yu Ye; Zhen-Xin Wang; Yi-Lin Zhang; Xuan-Sheng Hu; He-ping Hui; Yi-tong Liu; Jianzhao Qi (Natural Product Research, 2024)

Isolation, characterization, and application of a novel Pseudomonas fluorescens phage vB_PF_Y1-MI in contaminated milk - Guanhua Xuan; Xianjun Liu; Yinfeng Wang; Hong Lin; Xiuping Jiang; Jingxue Wang (Molecular Genetics and Genomics, 2024)

Precise diagnosis of a hereditary spherocytosis patient with complicated hematological phenotype - Guanxia Liang; Zezhang Lin; Yang Zhang; Qianqian Zhang; Dina Zhu; Xiongda Liang; Hongting Xie; Xiaofeng Wei; Xuan Shang (Molecular Genetics and Genomics, 2024)

Lymph nodes in oral squamous cell carcinoma: a comprehensive anatomical perspective - Guang-Rui Wang; Nian-Nian Zhong; Lei-Ming Cao; Xuan-Hao Liu; Zi-Zhan Li; Yao Xiao; Kan Zhou; Yi-Fu Yu; Bing Liu; Lin-Lin Bu (Clinical & Experimental Metastasis, 2024)

Berbamine inhibits porcine epidemic diarrhea virus in vitro and in vivo - Hongwei Xiang; Jixue Qiao; Haicheng Lin; Jie Li; Yangfan Li; Huihui Sun; Xuan Wang; Ruimin Bi; Zuyao Zhang; Zongyi Bo; Haixiao Shen; Jinchi Zhou; et al. (Veterinary Microbiology, 2024)

Alendronate sodium induces G1 phase arrest and apoptosis in human umbilical vein endothelial cells by inhibiting ROS-mediated ERK1/2 signaling - Yi Feng; Shao-Qin Tu; Yu-Luan Hou; Yi-Ting Shao; Lin Chen; Zhi-Hui Mai; Yu-Xuan Wang; Jia-Ming Wei; Sai Zhang; Hong Ai; Zheng Chen (Toxicology, 2024)

Effects of alligator weed invasion on wetlands in protected areas: A case study of Lishui Jiulong National Wetland Park - Xiang-Hua Fang; Xuan-Ming Chen; Ri-Lin Liu; Si-Hai Zhang; Jun-Qin Gao; Bi-Cheng Dong; Fei-Hai Yu (Science of The Total Environment, 2024)

Effects of soil microplastic heterogeneity on plant growth vary with species and microplastic types - Xiao-Mei Zhang; Wei-Long Li; Wei Xue; Michael Opoku Adomako; Min Tang; Lin-Xuan He; Fei-Hai Yu (Science of The Total Environment, 2024)

Hydrology controls sulfuric acid-mediated weathering in an orogenic regime of southwestern Taiwan - Hou-Chun Liu; Meng-Xuan Li; Chen-Feng You; Yan-Hong Chen; Kuo-Fang Huang; Chuan-Hsiung Chung; Guan-Wei Lin (Science of The Total Environment, 2024)

Effects of filter-feeding fish faeces on microbial driving mechanism of lake sediment carbon transformation - Yiming Li; Xuan Che; Hongyuan Chen; Zhanpeng Meng; Xinfeng Li; Xiaodong Wang; Lin Zhu; Yunlong Zhao (Science of The Total Environment, 2024)

Force mechanism analysis of composite microbial dust suppressants based on extracellular polymeric substances (EPS) mode components - Mei-Xuan Ha; Yu Liu; Yue Feng; Xiang-Ming Hu; Yan-Yun Zhao; Jin-Di Liu; Li Chen; Yan-Lin Qu (Journal of Environmental Management, 2024)

Different preferences for inorganic carbon influence CO2 flux under Cyanobacteria or Chlorophyta dominance days - Kai-Kai Deng; Yi-Xuan Li; Peng Yan; Yuan-Chen Huo; Hao Yang; Bin Chen; Qiang He; Gui-Jiao Lin; Jin-Song Guo (Journal of Environmental Management, 2024)

Insights on aggregation-algae consortium based removal of sulfamethoxazole: Unraveling removal effect, enhanced method and toxicological evaluation - Yongtao Cheng; Yuanyuan Wu; Chuanyue Peng; Yang Yang; Liang Xuan; Lin Wang; Yan Wang; An Xu; Ying Liu (Journal of Environmental Management, 2024)

Unveiling the occurrence and ecological risks of triclosan in surface water through meta-analysis - Zhenyao Wang; Xuan Li; Yi Li; Huan Liu; Carol Sze Ki Lin; Jing Sun; Qilin Wang (Environmental Pollution, 2024)

Evaluation of aspartame effects at environmental concentration on early development of zebrafish: Morphology and transcriptome1 - Yitian Wu; Ziyuan Lin; Feng Chen; Xuan Zhang; Yanyan Liu; Huaqin Sun (Environmental Pollution, 2024)

Modifying functional groups of straw-based hydrogel provide soil N2O mitigation potential by complete denitrification - Weishuai Wang; Xuan Wang; Shuping Qin; Jiao Yuan; Jiafa Luo; Zhaohai Bai; Lin Ma (Chemical Engineering Journal, 2024)

Efficient integration of calcium looping with methane bi-reforming using Pd-enhanced Ni-CaO dual functional nanomaterials - Zhi Xuan Law; Kun-Han Lin; De-Hao Tsai (Chemical Engineering Journal, 2024)

Core-shell structured composite high-efficiency catalyst Co@Pd/TiO2 with a compressed-strain Pd shell for the direct synthesis of H2O2 - Feifei Hu; Meng Wang; Xin Zhou; Shisong Yang; Xuan Chen; Chaochuang Yin; Qian Lin; Hongyan Pan; Zheng Chen (Chemical Engineering Journal, 2024)

Delaying cyclization of polyacrylonitrile by boric acid for sulfurized poly(acrylonitrile) cathode materials - Xuan Zhang; Hui-Chao Lu; Chen-Ran Hao; Ji-Qiong Liu; Xi-Rui Kong; Jiu-Lin Wang (Chemical Engineering Journal, 2024)

The predictive value of the neutrophil/platelet ratio on in-hospital adverse events and long-term prognosis in patients with coronary artery disease after percutaneous coronary intervention and its possible internal mechanism - Yifei Xiang; Jilang Zeng; Xueqin Lin; Xiaoling Cai; Liwei Zhang; Manqing Luo; Gengyu Zhou; Xiaofang Chen; Biting Lin; Junhan Chen; fan Chen; Xuan Huang; et al. (Molecular and Cellular Biochemistry, 2024)

The response of surface sedimental diatoms to the environment and its potential significance in the Taiwan Strait, western Pacific - Min Chen; Xuan Liu; Shuqin Tao; Aijun Wang; Yanting Lin; Zhaohe Luo; Ya Xu; Jiayu Li; Qing Huang (Acta Oceanologica Sinica, 2024)

Hindcasted Body Temperatures Reveal Underestimated Thermal Stress Faced by Intertidal Species - Lin‐Xuan Ma; Jie Wang; Mark W. Denny; Yun‐Wei Dong (Global Ecology and Biogeography, 2024)
Aim As global climate changes, there is a clear mismatch between the temporal and spatial characteristics of body temperature and environmental temperature, confounding the assessment of thermal stress for organisms in many ecological studies. Here, we hindcast the hourly body temperatures of intertidal molluscs to explore the differences between them and environmental temperatures (air and water temperatures) in multiple metrics of thermal stress. Location Intertidal shores in East Asia (0°–45°N, 100°E–140°E). Time Period 40 years, 1980 to 2019. Major Taxa Studied Mollusca. Methods We collected habitat zonation data and measured the morphological characteristics of 25 intertidal molluscs living in East Asia. For three different types of intertidal molluscs (i.e., bivalves, limpets and snails), we built corresponding heat budget models (HBMs) to hindcast the hourly body temperatures from 1980 to 2019. We analysed the thermal stress of intertidal species faced in three metrics, annual extreme high temperatures ( T 99 ), seasonal daily maximum temperatures (DMT) and heatwaves, and compared them with environmental temperatures. Results We found that T 99 of body temperatures and their interannual warming rates are significantly higher than those of environmental temperatures. Moreover, there were non‐negligible mismatches between the seasonal thermal pattern and heatwaves of body temperatures and environmental temperatures, suggesting that the deleterious impacts of global warming on intertidal species are underestimated and cannot be directly revealed by environmental temperatures. Main Conclusions Thermal stress patterns of body temperature were significantly different from those of environmental temperature, and the thermal stress faced by intertidal species had been persistently underestimated. These results emphasise that body temperature should be used as the appropriate metric for evaluating and predicting the impacts of global warming and weather extremes in the intertidal biological system.

Genomics‐Informed Range Predictions Under Global Warming Reveal Reduced Adaptive Diversity Whilst Buffering Range Shifts for a Marine Snail - Xiao‐Nie Lin; Chao‐Yi Ma; Li‐Sha Hu; Ming‐Ling Liao; Lin‐Xuan Ma; Peter R. Teske; Ary Hoffmann; Yun‐Wei Dong (Global Change Biology, 2024)
Understanding the genetic basis of local adaptation in thermal performance is useful for predicting species distribution shifts under anthropogenic climate change. Many species are distributed across multiple biogeographic regions, and the uniquely adapted populations in each region may respond to future ocean warming with distinct distribution changes. In the present study, we investigated phylogeographic patterns, thermal sensitivity, and genetic differentiation in the intertidal snail Littorina brevicula along China's coast. Whole‐genome sequencing results based on a newly assembled chromosome‐level genome revealed two genetic lineages, with a north–south divergence that is linked to the thermal environment. Within each lineage, individuals could be further subdivided into genetic subgroups that differ at key genomic loci underpinning differences in upper heat tolerance. Heat stress drives adaptive divergence across multiple levels of organization, from the individual to the biogeographic level. Taking into account genetic diversity associated with variation in heat tolerance, a physiological species distribution model (pSDM) was applied to predict the distributions of the different genetic subgroups in response to climate change. Both northern and southern lineages were predicted to experience declines in habitat suitability under a 4°C future warming scenario, and that a genotypic subset of snails from the southern lineage may even be driven to extinction. These findings illustrate that even when a species' range is maintained, it can nonetheless experience a significant decrease in adaptive diversity as a result of climate change. The integrated approach presented here, which considered both physiological and adaptive genetic variation at the level of individuals within a biogeographical context, provided new insights into how marine species can respond to global warming.

Advantages of targeted ventilation for farrowing houses: An analysis from perspectives of thermal environment, biosecurity and ventilation efficacy - Longhuan Du; Xuan Tao; Lin Zhu; Jinchuan Li; Min Fu; Jingwen Lai; Chaowu Yang; Zhiping He (Computers and Electronics in Agriculture, 2024)

Most appropriate nozzle of six-rotor UAV for prescribed spraying liquid in tea plantation under effects of downwash flow structure in hover - Nai-Hong Hu; Wen-Xuan Zhou; Lin Zhu; Yan-Cheng Li; Xin-Yu Xie; Ru-Yan Hou; Cheng-Long Yin (Crop Protection, 2024)

EtROP38 suppresses apoptosis of host cells infected with Eimeria tenella by inhibition of the p38MAPK pathway - Bu-ting Duan; Hao-yu Zhang; Zi-hao Song; Xiao-yi Han; Kai-ling Cui; Tong Xu; Yu Zhang; Yong-juan Zhao; Xuan Lei; Fan Tan; Lu-lu Guo; Hui-lin Yang; et al. (Veterinary Parasitology, 2024)

Thallium isotopic fractionation in soils from a historic Hg Tl mining area: New insights on thallium geochemistry - Wenhuan Yuan; Jingye She; Jingfen Lin; Ke Lin; Qiaohui Zhong; Xinni Xiong; Huimin Cao; Xuan Zeng; Jin Wang; Juan Liu (Science of The Total Environment, 2024)

Optimizing straw and nitrogen fertilizer resources for low-carbon sustainable agriculture - Bai-Jian Lin; Jia Cheng; Hong-Xuan Duan; Wen-Xuan Liu; Yash Pal Dang; Xin Zhao; Hai-Lin Zhang (Resources, Conservation and Recycling, 2024)

The adsorption behavior and mechanism of antimony in water by jarosite ball milling mixed with nano zero-valent iron - Ming-Xuan Chen; Zhi-Bin Wu; Lin Luo; Yuan Yang; Qi-Ming Mao (Journal of Environmental Chemical Engineering, 2024)

Development of a NiFe2O4 covalent organic framework based magnetic solid-phase extraction approach for specific capture of quinolones in animal innards prior to UHPLC–Q–Orbitrap HRMS detection - Shumin Lin; Yun-kai Lv; Aixue Zhu; Ming Su; Xiliang Li; Shu-xuan Liang (Food Chemistry, 2024)

Selenium-enriched Bifidobacterium longum DD98 significantly improves the efficacy of Mesalazine and Cyclosporin A in colitis mice - Yongjia Hu; Chengchen Xu; Ziqi Xu; Xuan Chen; Fei Gao; Ting Lin; Ping Yang; Shidong Kan; Yu Yin; Daijie Chen (Food Bioscience, 2024)

Comprehensive insights into the refractory melanoidins production from structural extracellular polymeric substances via thermal hydrolysis pretreatment and the inhibition on anaerobic fermentation - Si-Di Hong; Shuai Wang; Xiao-Fei Yang; Xing-Chen Huang; Jia-Xiang Xiao; Wen-Xuan Wang; Jiahuan Tang; Hao Lin; Raymond Jianxiong Zeng; Kun Dai; Fang Zhang (Chemical Engineering Journal, 2024)

Inflammatory microenvironment-responsive “double-insurance” nanoreactors for accurate sonodynamic-chemodynamic therapy of rheumatoid arthritis - Sui Zhou; Meng-Wen Ma; Shao-Zhe Cai; Kai-Lin He; Lin-Fang Tan; Kai Cheng; Jin-Xuan Fan; Ling-Li Dong; Bo Liu (Chemical Engineering Journal, 2024)

New insights into the chemotaxonomic implications of diterpenoid alkaloid composition in Aconitum sessiliflorum - Jing-chuan Wu; Pei-xin Deng; Bo Yang; Yi-xuan Guan; Shuai Huang; Lin Chen; Xian-li Zhou (Biochemical Systematics and Ecology, 2024)

Dexmedetomidine attenuates ferroptosis by Keap1-Nrf2/HO-1 pathway in LPS-induced acute kidney injury - Rui-Rui Luo; Jing Yang; Yan-Lin Sun; Bi-Ying Zhou; Si-Xuan Zhou; Guo-Xing Zhang; Ai-Xiang Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Phenotypic and genetic effect of carotid intima-media thickness on the risk of stroke - Wenqiang Zhang; Jingwei Zhu; Xuan Wu; Tianle Feng; Wei Liao; Xuan Li; Jianci Chen; Li Zhang; Chenghan Xiao; Huijie Cui; Chao Yang; Peijing Yan; et al. (Human Genetics, 2024)

Distribution characteristics, sources and risk assessment of heavy metals in the surface sediments from the largest tributary of the Lancang River in the Tibet Plateau, China - Min Liu; Liangyuan Zhao; Li Lin; Yuting Zhang; Huawei Huang; Wei Deng; Yunjiao He; Jingxiang Tao; Yuan Hu; Luyi Nan; Yu Xuan Zhu (Environmental Geochemistry and Health, 2024)

Triclosan in sludge: Exploring its journey from the sewage treatment plants to land application and potential impacts on the environment - Zhenyao Wang; Xuan Li; Huan Liu; Ting Zhou; Jibin Li; Yi Li; Carol Sze Ki Lin; Qilin Wang (Critical Reviews in Environmental Science and Technology, 2024)

Green transformation of oily sludge through geopolymer: Material properties and hydration mechanisms - Xuan Guo; Hongdi Yu; Hongyun Yao; Fawei Lin; Eslam Salama; Mona Ossman; Beibei Yan; Guanyi Chen (Chemosphere, 2024)

Assessing the population genetic structure of yellow croaker in China: Insights into the ecological and genetic consequences of artificial breeding on natural populations - Jigui Yuan; Xuan Zhuang; Lisheng Wu; Hungdu Lin; Yulong Li; Lina Wu; Jixiang Yao; Jinxian Liu; Shaoxiong Ding (Aquaculture, 2024)

Expression of a novel hydrolase MhpC in Brevibacillus parabrevis BCP-09 and its characteristics for degrading synthetic pyrethroids - Yingyue Zhang; Dan Xiang; Jie Tang; Chuanning Peng; Siqi Chen; Siqi Huang; Qi Wen; Lin Liu; Wenliang Xiang; Qing Zhang; Ting Cai; Xuan Yu (Pesticide Biochemistry and Physiology, 2024)

Investigation on the induced electrical wakes generated by underwater vehicles - Qing Chen; Yimin Xuan; Qunqing Lin; Yuge Han; Kai Wei (Ocean Engineering, 2024)

Analysis of the dynamic mechanism of trans-boundary pollution collaborative control in the Yangtze River Economic Belt - Tao Tang; Xuan Lin; Meng Lu (Environmental Research, 2024)

Visible light irradiation enhanced sulfidated zero-valent iron/peroxymonosulfate process for organic pollutant degradation - Jialu Xu; Hao Cheng; He Zhang; Chengyou Sun; Haoran Tian; Jikun Yang; Yingxin Ding; Xuan Lin; Ping Wang; Chao Huang (Environmental Research, 2024)

Layered laser-engraved wood-based composite capable of photothermal conversion and energy storage for indoor thermal management in buildings - Ziqi Li; Jian Zhang; Lin Lin; Xuan Zhang; Qianxi Liu; Junyou Shi (Energy and Buildings, 2024)

Nanoplatforms derived from iron dextran combined with ascorbic acid for enhanced photothermal-chemodynamic therapy of tumors - Bin Zhang; Xiao-Lin Hou; Xiao-Ting Xie; Lin-Fang Tan; Meng Guan; Dong-Hui Zhao; Sui Zhou; Kai Cheng; Jin-Xuan Fan; Bo Liu (Chemical Engineering Journal, 2024)

An injectable COL6-crosslinked HA-DTPH hydrogel promotes spinal tract-like structure organization during spinal cord regeneration - Jia-Hui Sun; Zhou Fang; Zhiling Li; Ting-Ting Zheng; Sheng Liu; Jixiang Zhu; Wensheng Lin; Li-Kang Zhang; Aihua Yin; Aiguo Xuan; Jian-Long Zou (Chemical Engineering Journal, 2024)

Bacteriophage-encoded protein utilization in bacterial ghost production: a mini-review - Guanhua Xuan; Dongdong Qiu; Yinfeng Wang; Jingxue Wang; Hong Lin (World Journal of Microbiology and Biotechnology, 2024)

Mixing with Schima Superba Enhanced Soil Fertility and Simplified Soil Microbial Community of Eucalyptus Urophylla Forests - Wentao Hu; Jinrui Chen; Mengyao Liu; Xueqin Tian; Xuemei Chen; Wei Lin; Zuying Xuan; Lan Pan (Journal of Soil Science and Plant Nutrition, 2024)

Neutrophil-secreted S100A8/A9 participates in fatty liver injury and fibrosis by promoting myofibroblast migration - Na Chang; Yuran Liu; Weiyang Li; Yuehan Ma; Xuan Zhou; Xinhao Zhao; Lin Yang; Liying Li (Journal of Molecular Medicine, 2024)

Influence of arbuscular mycorrhizal fungi on root foraging and competitive ability depends on soil phosphorus distribution: evidence from two pairs of invasive and native plants - Na-Na Yao; Ao Liu; Xiao-Jing Wang; Hao-Hui Deng; Sheng-Qi Fan; Hai-Jie Zhang; Hui-Xuan Liao; Shao-Lin Peng; Bao-Ming Chen (Applied Soil Ecology, 2024)

Genotoxicity and cytotoxicity in male reproductive cells caused by sediment pollutants - Meng-Wei Lin; Jai-Yu Chen; Yu-Xuan Ye; Wei-Yi Chen; Hong-Lin Chan; Hsiu-Chuan Chou (Science of The Total Environment, 2024)

Genomic analysis of Alteromonas sp. M12 isolated from the Mariana Trench reveals its role in dimethylsulfoniopropionate cycling - Yue Lin; Min Zhang; Yu-Xiang Lai; Teng Liu; Meng Meng; Yan Sun; Yu Wang; Qing-Yu Dong; Chen-Xi Li; Meng-Xue Yu; Jin Cheng; Shu-Jun Liu; et al. (Marine Genomics, 2024)

Effects of nanoplastic exposure during pregnancy and lactation on neurodevelopment of rat offspring - Lei Tian; Yaping Zhang; Jiang Chen; Xuan Liu; Huipeng Nie; Kang Li; Huanliang Liu; Wenqing Lai; Yue Shi; Zhuge Xi; Bencheng Lin (Journal of Hazardous Materials, 2024)

Comprehensive comparison of aroma profiles and chiral free and glycosidically bound volatiles in Fujian and Yunnan white teas - Han Yan; Wei-Xuan Li; Ying-Lin Zhu; Zhi-Yuan Lin; Dan Chen; Yue Zhang; Hai-Peng Lv; Wei-Dong Dai; De-Jiang Ni; Zhi Lin; Yin Zhu (Food Chemistry, 2024)

Analysis of proteomics and in silico allergenicity prediction of soluble proteins in selenium-enriched peanut leaves - Qi Gao; Wei-Xuan Li; Zi-Heng Liu; Mei Tie; Xue-Jun Gu; Masaru Tanokura; You-Lin Xue (Food and Bioproducts Processing, 2024)

High-performance static formation of methane hydrate in fixed bed constructed by incorporating expanded graphite into polyimide foam - Xinran Sun; Daiming Liu; Zhibing Xuan; Yongtao Zhang; Guodong Zhang; Chen Chen; Mengting Sun; Yan Lin; Jie Zhong; Fei Wang (Chemical Engineering Journal, 2024)

Utilization of tofu wastewater and Nannochloropsis oceanica for eutrophication mitigation and eicosapentaenoic acid valorization: Advancing carbon neutrality and resource recycling - Yuqin Li; Xing Meng; Zhenyao Wang; Xin Lin; Yuan Xu; Jinhua Mou; Rong Zhou; Yufang Tang; Carol Sze Ki Lin; Xuan Li (Chemical Engineering Journal, 2024)

Number of global change factors alters plant-soil feedbacks via its effect on soil fungal communities - Wei Xue; Lin Huang; James D. Bever; Cheng Du; Hao-Ming Yuan; Lin-Xuan He; Xiao-Mei Zhang; Fei-Hai Yu (Soil Biology and Biochemistry, 2024)

Association between ambient air pollution and dry eye symptoms among Chinese individuals during the COVID-19 pandemic: A national-based study - Jia-Yan Kai; Yi-Bo Wu; Xing-Xuan Dong; Yi-Fan Miao; Dan-Lin Li; Dan-Ning Hu; Carla Lanca; Andrzej Grzybowski; Chen-Wei Pan (Science of The Total Environment, 2024)

A new species of Populus and the extensive hybrid speciation arising from it on the Qinghai-Tibet Plateau - Yu-Jie Shi; Jia-Xuan Mi; Jin-Liang Huang; Fei-Fei Tian; Fang He; Yu Zhong; Han-Bo Yang; Fang Wang; Yu Xiao; Lin-Kai Yang; Fan Zhang; Liang-Hua Chen; et al. (Molecular Phylogenetics and Evolution, 2024)

The involvement of SigmaR1K142 degradation mediated by ERAD in neural senescence linked with CdCl2 exposure - Bo Qian; Ting-Yu Li; Zhao-Xuan Zheng; Han-Yu Zhang; Wen-Qi Xu; Su-Min Mo; Jia-Jia Cui; Wei-Jie Chen; Yu-Chun Lin; Zhong-Ning Lin (Journal of Hazardous Materials, 2024)

Pathways to zero plastic waste in Chinese cities: Implications of different disposal options under the zero waste cities policy - Xingmin Chen; Youfei Ma; Kathinka Furst; Quanyin Tan; Wanying Lin; Xuan Shi; Jinfen Huo; Xueqiang Lu; Jinhui Li; Yan Lin (Journal of Cleaner Production, 2024)

Three thousand years of Hg pollution recorded in mangrove wetland sediments from South China - Minqi Chen; Bigyan Neupane; Xuan Zhan; Ting Liu; Zhanyi Lin; Changjun Gao; Claudio Zaccone; Kunshan Bao (Environmental Research, 2024)

Dual regulation of the orderly aggregation of covalent organic frameworks at the molecular level and nanoscale to achieve efficient phototherapy and gene therapy - Tong Li; Dianwei Wang; Meng Meng; Xiaoya Guo; Lin Lin; Zhiyu Yang; Zhen Li; Longwei Xiang; Cong Liu; Jie Chen; Xuan Pang; Kai Hao; et al. (Chemical Engineering Journal, 2024)

Constructing hydroxyoxime-functionalized ionic liquid [BHIB][NTf2] for the separation of Mo(VI) from U(VI) - Feng Liu; Tao-Yuan Xiu; Wei Jin; Xuan Fu; Lin Wang; Xin-Peng Wang; Wei-Qun Shi; Li-Yong Yuan (Chemical Engineering Journal, 2024)

A Review on Analytical Approaches for Ambient Ozone Open Data in Taiwan - Duy-Hieu Nguyen; Chih-Hsiang Liao; Xuan-Thanh Bui; Chung-Shin Yuan; Chitsan Lin (Current Pollution Reports, 2024)

Thermal infrared hyperspectral image band selection based on dynamic metric-guided particle swarm optimization for quantitative analysis of potash - Liqin Cao; Lin Gao; Yuting Wan; Xuan Zhang; Lyuzhou Gao; Yanfei Zhong (International Journal of Remote Sensing, 2024)

The loss of dissolved organic matter from biological soil crust at various successional stages under rainfall of different intensities: Insights into the changes of molecular components at different rainfall stages - Hao Wang; Qing-wei Zhang; Guo Chen; Xuan Li; Qi-lin Wang; Li Gao; Jian Wang; Ding He; Ming Li (Water Research, 2024)

Meta-analysis addressing the potential of antibiotic resistance gene elimination through aerobic composting - Hongge Wang; Xuan Wang; Lu Zhang; Xinyuan Zhang; Yubo Cao; Ran Xiao; Zhaohai Bai; Lin Ma (Waste Management, 2024)

Genome-wide sequencing reveals geographical variations in the thermal adaptation of an aquaculture species with frequent seedling introductions - Liang Zhang; Zhan-Wei Zhao; Lin-Xuan Ma; Yun-Wei Dong (Science of The Total Environment, 2024)

A new acetophenone derivative from Rhododendron irroratum subsp. pogonostylum - Yong-Fu Lu; Si-Xuan Liu; Chun-Lin Guo; Si-Yang Dai; Yi-Hui Yang; Chang Li; Yue-Hu Pei (Phytochemistry Letters, 2024)

Produce low-CO2 silica fume hybrid high-strength concrete using dry ice (solid CO2) as a CO2-utilized admixture - Mei-Yu Xuan; Run-Sheng Lin; Yi Han; Gui-yu Zhang; Cheng Guo; Xiao-Yong Wang (Journal of Cleaner Production, 2024)

Critical review for the potential analysis of material utilization from inorganic industrial solid waste - Xuan Guo; Menglan Zeng; Hongdi Yu; Fawei Lin; Jingwei Li; Wenlong Wang; Guanyi Chen (Journal of Cleaner Production, 2024)

High-frequency monitoring during rainstorm events reveals nitrogen sources and transport in a rural catchment - Xuan Huang; Yi Zhu; Han Lin; Dongli She; Ping Li; Man Lang; Yongqiu Xia (Journal of Environmental Management, 2024)

Deseasonalized trend of ground-level ozone and its precursors in an industrial city Kaohsiung, Taiwan - Duy-Hieu Nguyen; Chih-Hsiang Liao; Xuan-Thanh Bui; Lin-Chi Wang; Chung-Shin Yuan; Chitsan Lin (Environmental Pollution, 2024)

High-performance antibacterial tight ultrafiltration membrane constructed by co-deposition of dopamine and tobramycin for sustainable high-salinity textile wastewater management - Wenyuan Ye; Fan Yu; Zijian Yu; Na Kong; Xiaoyan Lin; Riri Liu; Jiale Du; Xuan Huang; Ailiang Gu; Sotto Arcadio; Wenyi Zhang; Xuewei Li; et al. (Desalination, 2024)

Modified lignin can achieve mitigation of ammonia and greenhouse gas emissions simultaneously in composting - Weishuai Wang; Xuan Wang; Xinyuan Zhang; Zhaohai Bai; Lin Ma (Bioresource Technology, 2024)

In vivo transgenic studies confirm the critical acylation function of LeBAHD56 for shikonin in Lithospermum erythrorhizon - Liu Yang; Changyi Wang; Xiaohui Lai; Suo Jin; Xuan Wang; Zhongling Wen; Minkai Yang; Aliya Fazal; Yuhang Ding; Zhongyi Li; Jinfeng Cai; Guihua Lu; et al. (Plant Cell Reports, 2024)

Identification of Key Factors in Cartilage Tissue During the Progression of Osteoarthritis Using a Non-targeted Metabolomics Strategy - Shiyu Sun; Minghui Chen; Tingting Zhang; Yanyan Wang; Weijun Shen; Tao Zhang; Jian Liu; Haidan Lan; Jianyuan Zhao; Fuqing Lin; Xuan Zhao (Phenomics, 2024)
This research was to reveal the key factors in the progression of osteoarthritis (OA) using non-targeted metabolomics and to find targeted therapies for patients with OA. Twenty-two patients with knee OA scheduled for total knee arthroplasty were divided into two groups: Kellgren–Lawrence (KL) grade 3 ( n = 16) and grade 4 ( n = 6), according to plain X-rays of the knee. After the operation, the cartilages of femur samples were analyzed using non-targeted metabolomics. When compared with grade 3 patients, the levels of choline, 2-propylpiperidine, rhamnose, and monomethyl glutaric acid were higher; while 1-methylhistamine, sphingomyelin (SM) (d18:1/14:0), zeranol, 3- (4-hydroxyphenyl)-1-propanol, 5-aminopentanamide, dihydrouracil, 2-hydroxypyridine, and 3-amino-2-piperidone were lower in grade 4 patients. Furthermore, some metabolic pathways were found to be significantly different in two groups such as the pantothenate and coenzyme A (CoA) biosynthesis pathway, the glycerophospholipid metabolism pathway, histidine metabolism pathway, lysine degradation pathway, glycine, serine and threonine metabolism pathway, fructose and mannose metabolism pathway, the pyrimidine metabolism pathway, and beta-alanine metabolism pathway. This work used non-targeted metabolomics and screened out differential metabolites and metabolic pathways, providing a reliable theoretical basis for further study of specific markers and their specific pathways in the progression of OA.

PARP-2 mediates cardiomyocyte aging and damage induced by doxorubicin through SIRT1 Inhibition - Chaoming Huang; Xuan Zhang; Shulin Wang; Ao Shen; Tianfen Xu; Yanhong Hou; Shuhan Gao; Yongwan Xie; Yi Zeng; Jiayu Chen; Runxiang Lin; Yu Zhang; et al. (Apoptosis, 2024)

Tidal zone effects on the diet composition of leaf-eating crabs in natural mangrove communities: a stable isotope analysis - Xiaoyan Lu; Xuan Gu; Lin Zhang; Jinhan Zhang; Wenqing Wang; Mao Wang (Frontiers in Marine Science, 2024)
Background In natural mangrove communities, mangrove species are often distributed zonally. Leaf-eating crabs are one of the most abundant and iconic arboreal brachyurans in mangrove forests, but variation in the composition of crab diets in different mangrove tidal zones is unknown. Methods To determine the contributions of mangrove leaves and other organic carbon (C) sources to leaf-eating crab diets, dual stable C and nitrogen (N) isotope signatures (δ13C and 1δ5N) were used in a Bayesian stable isotope mixing model. We conducted experiments at various tidal levels in the Dongzhaigang Bay National Natural Reserve in China. We analyzed δ13C and δ15N of leaf-eating crabs, mangrove leaves, sediment organic matter (SOM), and animal tissues (prey). Results The food composition of the dominant crab species, Parasesarma continentale, exhibited significant differences among the four tidal zones. From the margin to the high tide zone, the main food source shifted from predominantly mangrove leaves and SOM to primarily SOM and animal tissues. We observed a significant negative relationship between the C/N ratios of mangrove leaves and the proportion of leaves consumed by leaf-eating crabs. Additionally, as the tidal level increased, the C/N ratio of mangrove leaves also increased, whereas the proportion of leaves consumed by crabs decreased. Conclusion Leaf-eating crab diets vary significantly across tidal zones, highlighting the importance of considering tidal zone differentiation when studying consumer diets in mangrove ecosystems.

Deciphering decadal observation of Fukushima-derived radiocesium in the most polluted port near the Fukushima Daiichi Nuclear Power Plant: from seawater to marine fish - Wuhui Lin; Yibang Zhang; Jinqiu Du; Jiliang Xuan; Fei Tuo (Frontiers in Marine Science, 2024)
The biological concentration effect of radionuclides in marine fish has exacerbated public anxiety about seafood security in the context of Fukushima nuclear-contaminated water discharged into the ocean. However, the most polluted port near the Fukushima Daiichi Nuclear Power Plant (FDNPP) has seldom been investigated, especially for radioactivity in marine fish. In this study, decadal observations of radiocesium in marine fish and seawater from the most polluted port were simultaneously established after the Fukushima Nuclear Accident. We found a generally decreasing trend of historical 137 Cs activity in seawater, with seasonal variations modulated by precipitation. Seasonal variations were elucidated with finer detail and divided into exponential decline in the dry season and steady variation in the wet season. A novel method was proposed to estimate the continuing source term of 137 Cs derived from the FDNPP, which was 3.9 PBq in 2011 and 19.3 TBq between 2012 and 2022 on the basis of historical 137 Cs. The biological concentration effect of marine fish is quantitatively emphasized according to the higher ratio of over-standards for radiocesium in marine fish relative to that in seawater. Long-term observation and analysis of radiocesium in marine fish and seawater from the most polluted port would provide insights into the scientific evaluation of the effectiveness of the decommissioning of the FDNPP in the past and share lessons on the fate of Fukushima-derived radionuclides in the future.

Wavelength dependency and photosensitizer effects in UV-LED photodegradation of iohexol - Meng-Yuan Xu; Chao Zeng; Yi-Li Lin; Tian-Yang Zhang; Qi Fu; Heng-Xuan Zhao; Zhen-Ning Luo; Zheng-Xiong Zheng; Tong-Cheng Cao; Chen-Yan Hu; Bin Xu (Water Research, 2024)

Life cycle assessment of traditional and innovative sludge management scenarios in Australia: Focusing on environmental impacts, energy balance, and economic benefits - Zhenyao Wang; Xuan Li; Huan Liu; Jibin Li; Dan Cristian Vodnar; Carol Sze Ki Lin; Qilin Wang (Resources, Conservation and Recycling, 2024)

Optimization of ultrasonic extraction of bioactive components from Alpiniae oxyphyllae Fructus using response surface methodology - Yuyi Liu; Ruimin Wang; Xuan Hu; Chengfeng Yu; Zexin Wang; Lin Zhang; Sixin Liu; Congfa Li (Journal of Applied Research on Medicinal and Aromatic Plants, 2024)

Co-pyrolysis of saw dust and oily sludge with waste-heat utilization of steel slag on rotary kiln simulated engineering practice - Hongdi Yu; Fawei Lin; Xuan Guo; Hongyun Yao; Fa Zheng; Jiantao Li; Meng Zhang; Rundong Li; Beibei Yan; Guanyi Chen (Fuel, 2024)

Synthesis and characterization of a host–guest complex based on acetylated-β-cyclodextrin and its application in improving the viscosity of supercritical carbon dioxide - Wei-An Huang; Rui Su; Jing-Wen Wang; Yu Fan; Lin Jiang; Xuan Li; Jie Cao (Fuel, 2024)

E-eye and FT-NIR combined with multivariate algorithms to rapidly evaluate the dynamic changes in the quality of Gastrodia elata during steaming process - Jiu-ba Zhang; Bin Wang; Yun-fei Zhang; Yi Wu; Ming-xuan Li; Ting Gao; Tu-lin Lu; Zhen-hua Bian; Lian-lin Su (Food Chemistry, 2024)

Rapid determination of geographical authenticity and pungency intensity of the red Sichuan pepper (Zanthoxylum bungeanum) using differential pulse voltammetry and machine learning algorithms - Di Zhang; Zitao Lin; Lilei Xuan; Minmin Lu; Bolin Shi; Jiyong Shi; Fatao He; Maurizio Battino; Lei Zhao; Xiaobo Zou (Food Chemistry, 2024)

Investigation of the Influence of Operating Parameters on the Settling Performance of a Vertical Sedimentation Tank Through Computational Fluid Dynamics Simulations - Xuan Wu; Jiaqi Wei; Lin Shen; Xueqin Li (Water, Air, & Soil Pollution, 2024)

Occurrence and fate of pharmaceutical pollutants in wastewater: Insights on ecotoxicity, health risk, and state–of–the-art removal - Minh-Ky Nguyen; Chitsan Lin; Xuan-Thanh Bui; Md. Refat Jahan Rakib; Hoang-Lam Nguyen; Quoc-Minh Truong; Hong-Giang Hoang; Huu-Tuan Tran; Guilherme Malafaia; Abubakr M. Idris (Chemosphere, 2024)

Plant and microbial response in constructed wetland treating tetracycline antibiotic polluted water: Evaluating the effects of microplastic size and concentration - Weiliang Pan; Yi Zhou; Huimin Xie; Lin Liang; Guoyuan Zou; Lianfeng Du; Xuan Guo (Chemosphere, 2024)

Estimation of crop residue production and its contribution to carbon neutrality in China - Xin Zhao; Ruo-Chen Li; Wen-Xuan Liu; Wen-Sheng Liu; Ying-Hao Xue; Ren-Hua Sun; Yu-Xin Wei; Zhe Chen; Rattan Lal; Yash Pal Dang; Zhi-Yu Xu; Hai-Lin Zhang (Resources, Conservation and Recycling, 2024)

A novel integrating approach to assess the role of LiFePO4 battery recycling in the automotive industries in the Greater Bay Area of China - Jinfeng Tang; Zhicheng Zhang; Jianzhao Wu; Qian Feng; Lezhang Wei; Xinmei Lin; Minhua Su; Xuan Tang; Kaimin Shih; Junhua Xu (Journal of Cleaner Production, 2024)

Photodegradation of oxytetracycline hydrochloride by Z-scheme g-C3N4 @MIL-101(Fe) heterojunction: Experimental optimization, mechanism evaluation and practical application - Hongbin He; Bolong Liang; Shumin Lin; Yan Chen; Xin Zhang; Shu-Xuan Liang (Journal of Environmental Chemical Engineering, 2024)

Whole-genome sequencing of Escherichia coli from retail meat in China reveals the dissemination of clinically important antimicrobial resistance genes - Qin Wang; Ying-Yue Han; Tie-Jun Zhang; Xuan Chen; Heng Lin; Hong-Ning Wang; Chang-Wei Lei (International Journal of Food Microbiology, 2024)

Using in situ untargeted flavoromics analysis to unravel the empty cup aroma of Jiangxiang-type Baijiu: A novel strategy for geographical origin traceability - Busheng Zhang; Liangcai Lin; Canjie Zheng; Xuan Liu; Wanjing Cui; Xin Li; Xiaotong Lyu; Cuiying Zhang (Food Chemistry, 2024)

Trophic transfer of micro- and nanoplastics and toxicity induced by long-term exposure of nanoplastics along the rotifer (Brachionus plicatilis)-marine medaka (Oryzias melastigma) food chain - Xuan Li; Yuqi Zheng; Lin Lu; Junho Eom; Shaoguo Ru; Yuejiao Li; Jun Wang (Environmental Pollution, 2024)

Coculture of Chlorella protothecoides and Coccomyxa subellipsoidea enhances cell growth and lipid accumulation: An effective strategy for biodiesel production - Yuqin Li; Yuanyuan Luo; Rong Zhou; Xiaohong Zuo; Yong Zhang; Zhenyao Wang; Xuan Li; Xing Zhang; Zihao Qin; Carol Sze Ki Lin (Chemical Engineering Journal, 2024)

Stimulus-responsive nanomedicine mediated by metabolic intervention mechanisms to amplify redox anticancer therapy - Yongli Shen; Lin Wang; Binglong Ji; Xinlei Lu; Delong Zhao; Yujie Dai; Xuan Meng (Chemical Engineering Journal, 2024)

Exploring nanoparticle emissions and size distributions during incense burning and filtration in an indoor space - Hsi-Hsien Yang; Wei-Cheng Weng; Yong-Wen Chen; Xuan-Yi Lin; Ying I. Tsai (Air Quality, Atmosphere & Health, 2024)

The longevity evaluation of multi-metal stabilization by MgO in Pb/Zn smelter–contaminated soils - Ze-Lin Xu; Da-Mao Xu; Hai-Xuan Li; Hao-Kai Li; Rong-Bing Fu (Environmental Science and Pollution Research, 2024)

Multi-object detection and behavior tracking of sea cucumbers with skin ulceration syndrome based on deep learning - Fengli Ge; Kui Xuan; Peng Lou; Juan Li; Lingxu Jiang; Jiasheng Wang; Qi Lin (Frontiers in Marine Science, 2024)
Skin ulceration syndrome of sea cucumbers is one of the most serious diseases in intensive aquaculture, and it is the most effective way of preventing the spread of this disease to detect the abnormal behavior of sea cucumbers in time and take corresponding measures. However, the detection and tracking of multi-object is a hard problem in sea cucumber behavior analysis. To solve this problem, this paper first proposes a novel one-stage algorithm SUS-YOLOv5 for multi-object detection and tracking of sea cucumbers. The proposed SUS-YOLOv5 optimizes the maximum suppression algorithm in the overlapping region of the object detection box. Next, the SE-BiFPN feature fusion structure is proposed to enhance the transmission efficiency of feature information between deep and shallow layers of the network. Then, a MO-Tracking algorithm is proposed integrated with DeepSORT to achieve real-time multi-object tracking. Experimental results show that the mAP @0.5 and mAP @0.5:0.95 of the proposed object detector reach 95.40% and 83.80%, respectively, which are 3.30% and 4.10% higher than the original YOLOv5s. Compared with the traditional SSD, YOLOv3, and YOLOv4, the mAP of SUS-YOLOv5 is improved by 5.49%, 1.57%, and 3.76%, respectively. This research can realize the multi-object detection and tracking, which lays the foundation for the prediction of skin ulceration syndrome in sea cucumbers and has a certain practical application value for improving the intelligence level of aquaculture.

Identifying the source and fate of boron in geothermal water: Evidence from B/Na and B isotopes - Ying Tan; Xiao-Wei Jiang; Tao-Tao Ji; Yin-Fei Luo; Wan Dai; Hong Zhang; Zhao-Xuan Niu; Yu-De Lei; Zhi-Yuan Zhang; Tian-Yi Lin; Hua-Ming Guo (Science of The Total Environment, 2024)

Brunonianines A-C, C20-diterpenoid alkaloids with cyano group from Delphinium brunonianum Royle - Qing Li; Zhi-Wei Wang; Mu-Xuan Wang; Hao-Lin Yu; Lei Chen; Zhuoer Cai; Yu Zhang; Min-Min Gu; Yuan-Ling Shao; Hong-Ping Han; Zhi-Xin Liao (Phytochemistry, 2024)

Perturbation of lipid metabolism in 3T3-L1 at different stages of preadipocyte differentiation and new insights into the association between changed metabolites and adipogenesis promoted by TBBPA or TBBPS - Yun-Jiang Yu; Jing-Lin Tian; Tong Zheng; Hong-Xuan Kuang; Zong-Rui Li; Chao-Jie Hao; Ming-Deng Xiang; Zhen-Chi Li (Journal of Hazardous Materials, 2024)

Food search and transport in red imported fire ants (Hymenoptera: Formicidae) under wet conditions - Jintao Lin; Xinya Yang; Hailong Lyu; Xuan Chen; Lei Wang; Cai Wang; Xiujun Wen (Journal of Asia-Pacific Entomology, 2024)

Analyzing the correlation between quinolone-resistant Escherichia coli resistance rates and climate factors: A comprehensive analysis across 31 Chinese provinces - Yi-Chang Zhao; Zhi-Hua Sun; Ming-Xuan Xiao; Jia-Kai Li; Huai-yuan Liu; Hua-Lin Cai; Wei Cao; Yu Feng; Bi-Kui Zhang; Miao Yan (Environmental Research, 2024)

Directly capturing native fatty acid synthase from cancer cells by affinity-based probe for precise inhibitor discovery - Yuanyuan Lin; Huaqiu Lu; Jinhao Yu; Xuan Chen; Ningbo Chen; Huamin Zhang; Lu Ye; Yimin Chen; Weiyang Tang; Guizhong Xin; Jian-Liang Zhou (Chemical Engineering Journal, 2024)

Precision co-composting of multi-source organic solid wastes provide a sustainable waste management strategy with high eco-efficiency: a life cycle assessment - Hongge Wang; Zelong Liu; Xuan Wang; Lu Zhang; Xiaofei Wu; Shuo Li; Yubo Cao; Lin Ma (Environmental Science and Pollution Research, 2024)

Mechanism of deltamethrin biodegradation by Brevibacillus parabrevis BCP-09 with proteomic methods. - Yingyue Zhang; Jie Tang; Su Wang; Xuerui Zhou; Chuanning Peng; Hu Zhou; Dan Wang; Haoran Lin; Wenliang Xiang; Qing Zhang; Ting Cai; Xuan Yu (Chemosphere, 2024)

Exposure to ambient air pollution and chronic bronchitis: Findings from over 6.6 million adults in northwestern China - Weidong Ji; Yushan Wang; Xiao-Xuan Liu; Lin Li; Hua Yao; Yi Zhou; Bo-Yi Yang (Chemosphere, 2024)

The associations of secondhand smoke exposure with neurodevelopmental disorders and critical time window identification: A systematic review and meta-analysis - Xiao-Xuan Ou; Xin Wang; Xiao-Ling Zhan; Shu-Li Shen; Shamshad Karatela; Jin Jing; Li Cai; Ru-Qing Liu; Li-Zi Lin; Guang-Hui Dong (Science of The Total Environment, 2024)

Comparison of four pre-oxidants coupled powdered activated carbon adsorption for odor compounds and algae removal: Kinetics, process optimization, and formation of disinfection byproducts - Heng-Xuan Zhao; Shuang Zhang; Tian-Yang Zhang; Yi-Ping Zhu; Ren-Jie Pan; Meng-Yuan Xu; Zheng-Xiong Zheng; Chen-Yan Hu; Yu-Lin Tang; Bin Xu (Science of The Total Environment, 2024)

Four pairs of neolignan enantiomers with distinctive isochroman moiety from the fruits of Crataegus pinnatifida and their protective activities against H2O2-induced SH-SY5Y cells - Peng Zhao; Shi-Fang Li; Jiao-Yang Hou; Shu-Yan Qin; Jia-Yi Li; Xiao-Fang Zhou; Xuan Liu; Jin-Le Hao; Bin Lin; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2024)

The Earth Summit Mission-2022: Successful ozone soundings contribute to source identification in the north Mt. Qomolangma region - Jinqiang Zhang; Chunxiang Ye; Yuejian Xuan; Zhixuan Bai; Weili Lin; Dan Li; Lingkun Ran; Baofeng Jiao; Yaoming Ma; Weiqiang Ma; Nan Yao; Yunshu Zeng; et al. (Journal of Environmental Sciences, 2024)

Mechanism of ferrous ions reversibly inhibiting of oxidase-Like activity of Co3O4 nanowires and its application in horticultural fertilizer analysis - Ziting Lin; Tao Dong; Lingxi Niu; Xin Zhang; Mingyang Wang; Xuan Liu; Yuanyuan Cai; Aihua Liu (Chemical Engineering Journal, 2024)

Microbial electrochemical composting: A sustainable strategy to enhance lignocellulose conversion into humus - Lu Zhang; Xuan Wang; Hongge Wang; Lin Liu; Chunxu Song; Lin Ma (Chemical Engineering Journal, 2024)

ZIF-67-derived FeCoNi-LDH with a 3D nanoflower hierarchical structure for highly efficient oxidation of 5-Hydroxymethylfurfural and coupling seawater splitting hydrogen production - Zhenzhen Lin; Lili Wang; Tianbo Jia; Xuan Wang; Cunjun Li; Hairong Wang; Liang Li; Yingtang Zhou; Chunyang Zhai; Hengcong Tao; Shunli Li (Chemical Engineering Journal, 2024)

A novel R2R3-MYB transcription factor PbMYB1L of Pyrus bretschneideri regulates cold tolerance and anthocyanin accumulation - Xuan Zhou; Diya Lei; Wantian Yao; Shangyun Li; Haiyan Wang; Jiayu Lu; Yunting Zhang; Yuanxiu Lin; Yan Wang; Wen He; Mengyao Li; Qing Chen; et al. (Plant Cell Reports, 2024)

DSPE-PEG2000-methotrexate nanoparticles encapsulating phenobarbital sodium kill cancer cells by inducing pyroptosis - Fengyue Yin; Xiao Xu; Julia Qi; Mengyu Guo; Yubo Wang; Yun Wang; Roumei Ye; Qian Lin; Daowei Yang; Xuan Zhu; Jinling Wang (Journal of Molecular Medicine, 2024)

Sea buckthorn oil regulates primary myoblasts proliferation and differentiation in vitro - Jiamin Zhao; Lin Liang; Weipeng Zhang; Xuan Liu; Guoqiang Huo; Xiangdong Liu; Xiaoyang Lv; Junxing Zhao (In Vitro Cellular & Developmental Biology - Animal, 2024)

Benzoquinone and furopyridinone derivatives from the marine-derived fungus Talaromyces sp. MCCC 3A01752 - Xuan Hong; Lingzhi Tang; Zhongwei Chen; Qiliang Lai; Beibei Zhang; Youwei Jiang; Xunjie Wang; Ruonan He; Jianhui Lin; Zongze Shao; Shan Lin; Weiyi Wang (Natural Product Research, 2024)

Development and evaluation of a bivalent vaccine based on recombinant newcastle disease virus expressing infectious bursal disease virus VP2L-CH3-CH4 in SPF chickens - Wen Ying Sun; Xiao Lin Cao; Yi Xuan Wang; Xiao Chen Guo; Jin Miao Liu; Zhi Qiang Xue; Hui Juan Li; Wei Wang; Ting Ting Zhang; Qianhui Li; Rui Han Qin; Yu Han Jin; et al. (Veterinary Microbiology, 2024)

Nitric oxide regulates the lignification and carotenoid biosynthesis of postharvest carrot (Daucus carota L.) - Miao Sun; Tao Yang; Xuan-Huan Qiao; Peng Zhao; Zhi-Peng Zhu; Guang-Long Wang; Lin-Lin Xu; Ai-Sheng Xiong (Postharvest Biology and Technology, 2024)

A model of hybrid speciation process drawn from three new poplar species originating from distant hybridization between sections - Yu-Jie Shi; Jin-Liang Huang; Jia-Xuan Mi; Jing Li; Fan-Yu Meng; Yu Zhong; Fang He; Fei-Fei Tian; Fan Zhang; Liang-Hua Chen; Han-Bo Yang; Hong-Lin Hu; et al. (Molecular Phylogenetics and Evolution, 2024)

Enhanced short-chain fatty acids production from anaerobic fermentation of secondary sludge by lignosulfonate addition: Towards circular economy - Zhenyao Wang; Xuan Li; Huan Liu; Ting Zhou; Jibin Li; Muhammad Ahmar Siddiqui; Carol Sze Ki Lin; Siyu Huang; Julie M. Cairney; Qilin Wang (Journal of Cleaner Production, 2024)

The complexity of heatwaves impact on terrestrial ecosystem carbon fluxes: Factors, mechanisms and a multi-stage analytical approach - Lu-Ping Qu; Jiquan Chen; Jingfeng Xiao; Hans J. De Boeck; Gang Dong; Shi-Cheng Jiang; Ya-Lin Hu; Yi-Xuan Wang; Chang-Liang Shao (Environmental Research, 2024)

The brominated flame retardant tetrabromobisphenol A-bis(2,3-dibromo-2-methylpropyl ether) as well as hexabromocyclododecane lead to lipid disorders in mice - Xuan-Yue Chen; Yuan-Yuan Li; Lin Lv; Yi-Ming Xiong; Zhan-Fen Qin (Environmental Pollution, 2024)

Electric field as extracellular enzyme activator promotes conversion of lignocellulose to humic acid in composting process - Lu Zhang; Xuan Wang; Hongge Wang; Yubo Cao; Liping Weng; Lin Ma (Bioresource Technology, 2024)

Molecular compositions of marine organic aerosols over the Bohai and Yellow Seas: Influence of primary emission and secondary formation - Fang Cao; Yi-Xuan Zhang; Yan-Lin Zhang; Wen-Huai Song; Yu-Xian Zhang; Yu-Chi Lin; Chaman Gul; Md. Mozammel Haque (Atmospheric Research, 2024)

The clinical trajectory of peripheral blood immune cell subsets, T-cell activation, and cytokines in septic patients - Xuan Lu; Cong-Ying Song; Ping Wang; Li Li; Li-Ying Lin; Shuai Jiang; Jia-Ning Zhou; Meng-Xiao Feng; Yun-Mei Yang; Yuan-Qiang Lu (Inflammation Research, 2024)

Response of distributions and emissions of summer biogenic sulfur in the Pacific Arctic to enhanced Pacific Water inflow - Cheng‐Xuan Li; Bao‐Dong Wang; Kan Chen; Gui‐Peng Yang; Jian‐Fang Chen; Li‐Na Lin; Zi‐Cheng Wang (Limnology and Oceanography, 2024)
The inflow of warm and nutrient‐rich Pacific Water (PW) through the Bering Strait into the Arctic Ocean is likely to have far‐reaching consequences for the ecosystem and biogenic sulfur cycle in the Earth's sensitive subarctic–arctic region of the Pacific sector, even impacting climate change under global warming scenarios. We performed a detailed biogeochemical study of summer biogenic sulfur cycling from cold (2012) to warm (2014) years in the Bering Strait and the Chukchi Sea, so as to highlight the importance of enhanced Pacific inflow in driving dimethylsulfide (DMS) variability. In the Bering Strait, the enhanced Pacific inflow led to the vertical expansion of the eastern high‐DMS regions due to the vertical extension of Alaska Coastal Water, and the horizontal expansion of the western surface high‐DMS regions due to the westward intrusion of Bering Shelf Water. The enhanced extension of PW potentially stimulated seawater warming, the northward retreat of the ice edge, and the enlargement of sea ice‐free areas in the Chukchi Sea. The northern ice melting zone at 71°N with a bloom of phytoplankton was an area of locally high dimethylsulfoniopropionate concentrations and slow DMS consumption in 2012. A hotspot for dimethylated sulfur compound concentrations and DMS sea–air flux occurred in the convergence region near 67.7°N during 2014, due to enhanced mixing caused by increased Bering Sea Water. Owing to the increased advection of PW during 2012–2014, surface DMS and its emission to the atmosphere increased sharply by threefold in the Chukchi Sea.

Mixed chlorine/chloramines in disinfected water and drinking water distribution systems (DWDSs): A critical review - Renjie Pan; Tian-Yang Zhang; Huan He; Zheng-Xiong Zheng; Zheng-Yu Dong; Heng-Xuan Zhao; Meng-Yuan Xu; Zhen-Ning Luo; Chen-Yan Hu; Yu-Lin Tang; Mohamed Gamal El-Din; Bin Xu (Water Research, 2023)

Spatialized importance of key factors affecting park cooling intensity based on the park scale - Zhihua Liu; Lizhao Fu; Chaofan Wu; Zhenzhen Zhang; Zhaoyang Zhang; Xingwen Lin; Xuan Li; Yuhong Hu; Haixian Ge (Sustainable Cities and Society, 2023)

Ecological benefits of artificial light at night (ALAN): Accelerating the development and metamorphosis of marine shellfish larvae - Mo Zhang; Xiaolong Gao; Qi Luo; Shihui Lin; Mingxin Lyu; Xuan Luo; Caihuan Ke; Weiwei You (Science of The Total Environment, 2023)

Influence of salinity on microalgae-bacteria symbiosis treating shrimp farming wastewater - Thi-Kim-Quyen Vo; Quang-Huy Hoang; Huu Hao Ngo; Cong-Sac Tran; Tung N.N. Ninh; Song-Lam Le; An-Tan Nguyen; Tan Thi Pham; Thanh-Binh Nguyen; Chitsan Lin; Xuan-Thanh Bui (Science of The Total Environment, 2023)

Emission characteristics of naphthalene from ship exhausts under global sulfur cap - Chin-Ko Yeh; Fu-Ming Tzu; Po-Yang Chen; Hsueh-Chen Shen; Chung-Shin Yuan; Chitsan Lin; Han-Pin Pu; Huu Hao Ngo; Xuan-Thanh Bui (Science of The Total Environment, 2023)

Vacuolar H+-ATPase and BZR1 form a feedback loop to regulate the homeostasis of BR signaling in Arabidopsis - Yu-Tong Jiang; Lu-Han Yang; Ji-Xuan Zheng; Xian-Chen Geng; Yu-Xuan Bai; Yu-Chen Wang; Hong-Wei Xue; Wen-Hui Lin (Molecular Plant, 2023)

Algal strains, treatment systems and removal mechanisms for treating antibiotic wastewater by microalgae - Juan Peng; Kai-Lu Cao; Si-Bo Lv; Yu-Xuan Hu; Jia Lin; Qian-Zhi Zhou; Jiang-Hai Wang (Journal of Water Process Engineering, 2023)

Hydraulic circulation technology remediates the contaminated groundwater with petroleum hydrocarbon: Evidence from laboratory and field tests - Zhan Chen; Yu-Lin Wu; Tao Li; Yi-Xiang Wang; Ling-Kang Xuan; Shi-Feng Lu (Journal of Cleaner Production, 2023)

Prediction of resilience and cohesion of deep-fried tofu by ultrasonic detection and LightGBM regression - Lilei Xuan; Zitao Lin; Jing Liang; Xiaowei Huang; Zhihua Li; Xinai Zhang; Xiaobo Zou; Jiyong Shi (Food Control, 2023)

Enhancing methane production from anaerobic digestion of secondary sludge through lignosulfonate addition: Feasibility, mechanisms, and implications - Zhenyao Wang; Xuan Li; Huan Liu; Ting Zhou; Jibin Li; Muhammad Ahmar Siddiqui; Carol Sze Ki Lin; Mohammad Rafe Hatshan; Siyu Huang; Julie M. Cairney; Qilin Wang (Bioresource Technology, 2023)

Long-term ozone exposure is negatively associated with estimated glomerular filtration rate in Chinese middle-aged and elderly adults - Yiqin Zhang; Chen Tang; Yuwen Liu; Hanxiang Jiang; Jiaosheng Lu; Zhonghua Lu; Liping Xu; Siyu Zhang; Lina Zhou; Jing Ye; Xianfa Xuan; Ting Wu; et al. (Chemosphere, 2023)

Non-destructive fruit firmness evaluation using a soft gripper and vision-based tactile sensing - Jiahao Lin; Qing Hu; Jinming Xia; Liang Zhao; Xuan Du; Shanjun Li; Yaohui Chen; Xing Wang (Computers and Electronics in Agriculture, 2023)

Hydrogen sulfide delays postharvest ripening of white fleshed strawberry by regulating phytohormone accumulation and ROS generation - Miao Sun; Tao Yang; Xuan-Huan Qiao; Peng Zhao; Zhi-Peng Zhu; Kai-Yue Su; Chuan-Wen Sun; Zhao-Biao Xie; Shu-Song Zhang; Meng Xu; Lin-Lin Xu; Ai-Sheng Xiong (Postharvest Biology and Technology, 2023)

Reverse genetic study reveals the molecular targets of chordotonal organ TRPV channel modulators - Yu-Xuan Peng; Zhao-Yu Liu; Pin-Xuan Lin; Shao-Cong Su; Cong-Fen Gao; Shun-Fan Wu (Pesticide Biochemistry and Physiology, 2023)

Propeller hydrodynamic excitation influenced by shafting whirling vibration considering different nonuniform inflow conditions: A numerical study - Chang-Lin Meng; Lie-Yi Dong; Dong-Hua Wang; Jia-Xuan He; Zhi-Jun Shuai; Wan-You Li; Shi-Wei Ni; Chen-Xing Jiang (Ocean Engineering, 2023)

Evaluation of species thermal sensitivity with individual-based physiological performance - Liang Zhang; Yu-Yang Zhang; Lin-Xuan Ma; Yun-Wei Dong (Marine Environmental Research, 2023)

Sulforaphane alleviates the meiosis defects induced by 3-nitropropionic acid in mouse oocytes - Wei-Jian Li; Xuan Zhang; Ming Shen; Hong-Lin Liu; Li-Ren Ding (Food and Chemical Toxicology, 2023)

Analysis of the spatial-temporal evolution of Green and low carbon utilization efficiency of agricultural land in China and its influencing factors under the goal of carbon neutralization - Jun Fu; Rui Ding; Yu-qi Zhu; Lin-yu Du; Si-wei Shen; Li-na Peng; Jian Zou; Yu-xuan Hong; Juan Liang; Ke-xin Wang; Wen-qian Xiao (Environmental Research, 2023)

Time-dependent multicolor evolution of photoluminescence and afterglow in lanthanide-doped gallate - Yuzhu Yang; Peng Zhang; Wanying Xie; Zenggang Lin; Xuan Miao; Sixia Li; Haining Wang; Weisheng Liu (Chemical Engineering Journal, 2023)

Extended exposure to tetrabromobisphenol A-bis(2,3-dibromopropyl ether) leads to subfertility in male mice at the late reproductive age - Yuan-Yuan Li; Yi-Ming Xiong; Xuan-Yue Chen; Jia-Yi Sheng; Lin Lv; Xing-Hong Li; Zhan-Fen Qin (Archives of Toxicology, 2023)

Design, synthesis, and biological activity of 9- O -cinnamoylberberines as novel lipid-lowering agents - Yuan Kong; Qi-Qi Xing; Yu-Xuan Tian; Lin Li; Pan Yu; Lin-Guo Zhao; Dong-Dong Li (Natural Product Research, 2023)

Examination of the effects of blue light stress on monoamine oxidase-mediated immunomodulatory function in the Pacific abalone, Haliotis discus hannai - Mo Zhang; Xiaolong Gao; Mingxin Lyu; Shihui Lin; Xuan Luo; Caihuan Ke; Weiwei You (Aquaculture, 2023)

Genome-centric metagenomics provides new insights into metabolic pathways of polyhydroxyalkanoates biosynthesis and functional microorganisms subsisting on municipal organic wastes - Ruo-hong Li; Jin Huang; Cheng-xi Liu; Ke Yu; Feng Guo; You Li; Zuo-hong Chen; Xuan Wang; Ren-xin Zhao; Jia-yu Zhang; Jia-jin Liang; Yun Li; et al. (Water Research, 2023)

Opportunities and challenges for ribosome-inactivating proteins in traditional Chinese medicine plants - Yi-xuan Yang; Xin-yi Wang; Tong Lin; Yu Sun; Yi-cheng Yu; Zhen-hong Zhu (Toxicon, 2023)

Towards effective recovery of humate as green fertilizer from landfill leachate concentrate by electro-neutral nanofiltration membrane - Wenyuan Ye; Mingqiu Hong; Xuan Huang; Tianci Chen; Ailiang Gu; Xiaocheng Lin; Xuewei Li; Xiangrong Chen; Dong Han Seo; Shuaifei Zhao; Xueming Chen; Bart Van der Bruggen; et al. (Science of The Total Environment, 2023)

The molecular basis of heat stress responses in plants - Yi Kan; Xiao-Rui Mu; Jin Gao; Hong-Xuan Lin; Youshun Lin (Molecular Plant, 2023)

Non-target and target analysis to identify and characterize thiophenes in soil from an abandoned coking plant - Qiaofeng Ai; Lirong Gao; Di Huang; Jing Yang; Qiang Fu; Xuan Zheng; Yang Liu; Lin Qiao; Jiyuan Weng; Minghui Zheng (Journal of Hazardous Materials, 2023)

Enhanced biodegradation of endocrine disruptor bisphenol A by food waste composting without bioaugmentation: Analysis of bacterial communities and their relative abundances - Adnan Hussain; Suei Chang Wu; Thi-Hieu Le; Wen-Yen Huang; Chitsan Lin; Xuan-Thanh Bui; Huu Hao Ngo (Journal of Hazardous Materials, 2023)

Efficient activation of persulfate by metallic sulfide mineral for the efficient removal of pesticides: Performance, radical generation and mechanism - Xie Chen; Wen-Xuan Zhang; Zhi-Liang Chen; Xiao-Wen Yao; Man-Li Chen; Lin-Yin Tong; Wei Qian; Peng-Ran Guo; Ling-Jun Kong; Zeng-Hui Diao (Journal of Cleaner Production, 2023)

Quorum sensing autoinducers AHLs protect Shewanella baltica against phage infection - Guanhua Xuan; Lin Tan; Yuqing Yang; Jiuna Kong; Hong Lin; Jingxue Wang (International Journal of Food Microbiology, 2023)

A novel variable power microwave (VPM) drying technology for lowering energy consumption and improving the in vitro protein digestibility of black solider fly larvae - Xiaofei Wu; Wenyu Zhao; Xuan Wang; Zhaohai Bai; Lin Ma (Innovative Food Science & Emerging Technologies, 2023)

E-eye, flash GC E-nose and HS-GC-MS combined with chemometrics to identify the adulterants and geographical origins of Ziziphi Spinosae Semen - Jiu-ba Zhang; Ming-xuan Li; Yun-fei Zhang; Yu-wen Qin; Yu Li; Lian-lin Su; Lin Li; Zhen-hua Bian; Tu-lin Lu (Food Chemistry, 2023)

GABAergic Neurons in the Nucleus Accumbens are Involved in the General Anesthesia Effect of Propofol - Jing Yan; Bei-Ning Hang; Lin-Hui Ma; Jia-Tao Lin; Yue Zhou; Xin-Hao Jiao; Ying-Xuan Yuan; Ke-Jie Shao; Le-Meng Zhang; Qi Xue; Zi-Yi Li; Hong-Xing Zhang; et al. (Molecular Neurobiology, 2023)

Effect of humic substances on the anaerobic digestion of secondary sludge in wastewater treatment plants: a review - Zhenyao Wang; Xuan Li; Muhammad Ahmar Siddiqui; Huan Liu; Ting Zhou; Lei Zheng; Siyu Huang; Li Gao; Carol Sze Ki Lin; Qilin Wang (Environmental Chemistry Letters, 2023)

Research on stability and control strategies for a spring-loaded valve with bypass outlet - Jie Jian; Zhi-Jun Shuai; Jia-Xuan He; Chang-Lin Meng; Tao Yu; Xi Wang; Wan-You Li; Shi-Wei Ni; Chen-Xing Jiang (Annals of Nuclear Energy, 2023)

Early Paleozoic subduction imprints of the Proto-Tethys Ocean: Evidence from the Appinite–Diorite–Granodiorite complex in East Kunlun, Northern Tibet - Yang-Ming Hu; Xiao-Wei Li; Xuan-Xue Mo; Lin Li; Kai Wang; Bing-Zhang Wang; Xiao-Ping Gong; Guo-Chen Dong; Yan-Bin Liu (Lithos, 2023)

Novel hydrocortisone magnetic molecularly imprinted polymers: Preparation, characterization, and application - Si-xuan Zhou; Xiao-tong Lin; Jie Wang; Hai-xiang Wang; Gui-tang Chen (Food Chemistry, 2023)

Development of machine learning algorithms to estimate maximum residue limits for veterinary medicines - Nader Zad; Lisa A. Tell; Remya Ampadi Ramachandran; Xuan Xu; Jim E. Riviere; Ronald Baynes; Zhoumeng Lin; Fiona Maunsell; Jennifer Davis; Majid Jaberi-Douraki (Food and Chemical Toxicology, 2023)

Meteorological and hydrological droughts in the Lancang-Mekong River Basin: Spatiotemporal patterns and propagation - Xuan Luo; Xian Luo; Xuan Ji; Wenting Ming; Lin Wang; Xin Xiao; Jianan Xu; Yue Liu; Yungang Li (Atmospheric Research, 2023)

Characterization of a novel phage vB_Pae_HB2107-3I that infects Pseudomonas aeruginosa - Jiuna Kong; Guanhua Xuan; Hong Lin; Jingxue Wang (Molecular Genetics and Genomics, 2023)

Applying an air curtain to reduce surgical smoke concentration - Xuan-Huy Ninh; Hung-Yu Tzeng; Tak-Wah Wong; Yu-Ting Wu; Yao-Lung Kuo; Ming-Yeng Lin (Air Quality, Atmosphere & Health, 2023)

Macroscopic carbonaceous compression fossils from the Tonian Liulaobei Formation in the Huainan region of North China - Shujian Qin; Lin Dong; Xuan Liu; Feng Tang; Hui Liu (Precambrian Research, 2023)

Bioremediation of aniline aerofloat wastewater at extreme conditions using a novel isolate Burkholderia sp. WX-6 immobilized on biochar - Jin-Cheng Ye; Qiu-Shi Zhao; Jin-Wei Liang; Xiao-Xiao Wang; Zhen-Xuan Zhan; Huan Du; Ji-Liang Cheng; Lei Xiang; Nai-Xian Feng; Bai-Lin Liu; Yan-Wen Li; Hui Li; et al. (Journal of Hazardous Materials, 2023)

SWD1 epigenetically chords fungal morphogenesis, aflatoxin biosynthesis, metabolism, and virulence of Aspergillus flavus - Xiaohua Pan; Ling Hao; Chi Yang; Hong Lin; Dandan Wu; Xuan Chen; Mengjuan Zhang; Dongmei Ma; Yu Wang; Wangzhuo Fu; Yanfang Yao; Shihua Wang; et al. (Journal of Hazardous Materials, 2023)

Characterization of reciprocation membrane bioreactor on treatment performance, energy consumption and membrane fouling - Phuong-Thao Nguyen; Duyen Phuc Hanh Tran; Linh-Thy Le; Chitsan Lin; Le Thi Kim Oanh; Van-Tung Tra; Xuan-Thanh Bui (Bioresource Technology, 2023)

Pilot-Scale Integrated Anaerobic–Aerobic Bioreactor for COD and NH3-N Removal: Start-up, Key Processes, and Performance - Jianxiang Jin; Qun Wang; Lin Yang; Weixing Ma; Xuan Li; Bairen Yang; Zhuqiu Sun; Zhaoxia Li (Water, Air, & Soil Pollution, 2023)

Migraine, chronic kidney disease and kidney function: observational and genetic analyses - Wenqiang Zhang; Li Zhang; Luo Yang; Chenghan Xiao; Xueyao Wu; Peijing Yan; Huijie Cui; Chao Yang; Jingwei Zhu; Xuan Wu; Mingshuang Tang; Yutong Wang; et al. (Human Genetics, 2023)
Epidemiological studies demonstrate an association between migraine and chronic kidney disease (CKD), while the genetic basis underlying the phenotypic association has not been investigated. We aimed to help avoid unnecessary interventions in individuals with migraine through the investigation of phenotypic and genetic relationships underlying migraine, CKD, and kidney function. We first evaluated phenotypic associations using observational data from UK Biobank ( N = 255,896). We then investigated genetic relationships leveraging genomic data in European ancestry for migraine ( N case / N control = 48,975/540,381), CKD ( N case / N control = 41,395/439,303), and two traits of kidney function (estimated glomerular filtration rate [eGFR, N = 567,460] and urinary albumin-to-creatinine ratio [UACR, N = 547,361]). Observational analyses suggested no significant association of migraine with the risk of CKD (HR = 1.13, 95% CI = 0.85–1.50). While we did not find any global genetic correlation in general, we identified four specific genomic regions showing significant for migraine with eGFR. Cross-trait meta-analysis identified one candidate causal variant (rs1047891) underlying migraine, CKD, and kidney function. Transcriptome-wide association study detected 28 shared expression–trait associations between migraine and kidney function. Mendelian randomization analysis suggested no causal effect of migraine on CKD (OR = 1.03, 95% CI = 0.98–1.09; P = 0.28). Despite a putative causal effect of migraine on an increased level of UACR (log-scale-beta = 0.02, 95% CI = 0.01–0.04; P = 1.92 × 10 −3 ), it attenuated to null when accounting for both correlated and uncorrelated pleiotropy. Our work does not find evidence supporting a causal association between migraine and CKD. However, our study highlights significant biological pleiotropy between migraine and kidney function. The value of a migraine prophylactic treatment for reducing future CKD in people with migraine is likely limited.

HtrA is involved in stress response and adhesion in Glaesserella parasuis serovar 5 strain Nagasaki - Xuan Zhang; Yan Lin; Xiaojuan Xu; Siting Wen; Zhichao Wang; Jiayun Gu; Qigai He; Xuwang Cai (Veterinary Microbiology, 2023)

Insight into mixed chlorine/chloramines conversion and associated water quality variability in drinking water distribution systems - Renjie Pan; Tian-Yang Zhang; Zheng-Xiong Zheng; Jian Ai; Tao Ye; Heng-Xuan Zhao; Chen-Yan Hu; Yu-Lin Tang; Jing-Jing Fan; Bing Geng; Bin Xu (Science of The Total Environment, 2023)

Ultraviolet-based synergistic processes for wastewater disinfection: A review - Yi-Xuan Zhang; Jue-Lin Xiang; Jun-Jie Wang; Hai-Sheng Du; Ting-Ting Wang; Zheng-Yang Huo; Wen-Long Wang; Min Liu; Ye Du (Journal of Hazardous Materials, 2023)

Cabernet sauvignon dry red wine ameliorates atherosclerosis in mice by regulating inflammation and endothelial function, activating AMPK phosphorylation, and modulating gut microbiota - Xinlong Cheng; Xue Han; Liangfu Zhou; Yasai Sun; Qian Zhou; Xuan Lin; Zhe Gao; Jie Wang; Wen Zhao (Food Research International, 2023)

Enantiomeric separation and precise quantification of chiral volatiles in Wuyi rock teas using an efficient enantioselective GC × GC-TOFMS approach - Yue Zhang; Yu-Hui Zhang; Han Yan; Chen-Yang Shao; Wei-Xuan Li; Hai-Peng Lv; Zhi Lin; Yin Zhu (Food Research International, 2023)

Phod-harboring bacterial communities mediated slow and fast phosphorus transformation in alkaline soil of a Robinia pseudoacacia afforestation chronosequence - Ying Wang; Lin Yang; Jiawen Zhang; Yan Li; Haibin Kang; Xiaoxiong Bai; Yongxing Cui; Min Zhang; Liguo Dong; Xuan Yu (Plant and Soil, 2023)

Effects of particle size and pyrolytic temperature of biochar on the transformation behavior of antibiotic resistance genes - Xuan Gao; Qingkang Meng; Jing Fang; Shengdao Shan; Daohui Lin; Dengjun Wang (Science of The Total Environment, 2023)

U-shaped association between low-density lipoprotein cholesterol levels and risk of all-cause mortality mediated by post-stroke infection in acute ischemic stroke - Zi-Mo Chen; Hong-Qiu Gu; Jing-Lin Mo; Kai-Xuan Yang; Ying-Yu Jiang; Xin Yang; Chun-Juan Wang; Jie Xu; Xia Meng; Yong Jiang; Hao Li; Li-Ping Liu; et al. (Science Bulletin, 2023)

Efficient adsorption and photocatalytic degradation of water emerging contaminants through nanoarchitectonics of pore sizes and optical properties of zirconium-based MOFs - Jia-Xuan Tan; Zih-Yu Chen; Celine H. Chen; Ming-Feng Hsieh; Angela Yu-Chen Lin; Season S. Chen; Kevin C.-W. Wu (Journal of Hazardous Materials, 2023)

Recent advances in luminescence and aptamer sensors based analytical determination, adsorptive removal, degradation of the tetracycline antibiotics, an overview and outlook - Ma-Lin Cui; Zi-Xuan Lin; Qing-Fan Xie; Xiao-Yan Zhang; Bing-Qing Wang; Miao-Ling Huang; Da-Peng Yang (Food Chemistry, 2023)

Dimethyl Itaconate Reduces Cognitive Impairment and Neuroinflammation in APPswe/PS1ΔE9 Transgenic Mouse Model of Alzheimer’s Disease - Jing Xiong; Dong-Lin Lu; Bai-Qiang Chen; Tong-Yun Liu; Zi-Xuan Wang (NeuroMolecular Medicine, 2023)

Using Pgst-4::GFP-transformed Caenorhabditis elegans for drinking water quality monitoring - Yan Wang; Xue Han; Jie Zhang; Meng-Xuan Zhou; Ai-Lin Liu (Environmental Monitoring and Assessment, 2023)

Simultaneous detection and phylogenetic analysis of porcine epidemic diarrhea virus and porcine circovirus 4 in Henan province, China - Hong-Xuan Li; Xi-Meng Chen; You-Yi Zhao; Hong-Lei Zhang; Lan-Lan Zheng; Lin-Qing Wang; Shi-jie Ma; Hong-Ying Chen (Archives of Virology, 2023)

Late Carboniferous extension-related magmatism in the southwestern Alxa block of NW China: geochronology, geochemistry, and tectonic implications - Zeng-Zhen Wang; Xuan-Hua Chen; Wei-Cui Ding; Bing Li; Yi-Ping Zhang; Zhao-Gang Shao; Sheng-Lin Xu (International Geology Review, 2023)

Metabolic and transcriptional responses demonstrating enhanced thermal tolerance in domesticated abalone - Feng Yu; Yawei Shen; Wenzhu Peng; Nan Chen; Yang Gan; Qizhen Xiao; Junyu Liu; Yisha Lu; Weihong Lin; Zhaofang Han; Xuan Luo; Weiwei You; et al. (Science of The Total Environment, 2023)

Nanoplastics induce more severe multigenerational life-history trait changes and metabolic responses in marine rotifer Brachionus plicatilis: Comparison with microplastics - Xuan Li; Lin Lu; Shaoguo Ru; Junho Eom; Dong Wang; Samreen; Jun Wang (Journal of Hazardous Materials, 2023)

Effects of clay minerals and organic matter on pore evolution of the early mature lacustrine shale in the Ordos Basin, China - Guanping Wang; Zhijun Jin; Qian Zhang; Rukai Zhu; Xuan Tang; Kouqi Liu; Lin Dong (Journal of Asian Earth Sciences, 2023)

Ultralight, robust, and high Prussian blue-loading polyacrylonitrile aerogel: Preparation, characterization and efficient adsorption/removal of Cs+ - Xiao-Bo Yang; Wei Li; Ze-Zhong Lin; Jing-Qi Liu; Hong-Xin Jiang; Hao Jia; Wei-Liang Jin; Xin-Long Hou; Bing-Xuan Du; Li-Na Zhu; De-Ming Kong (Chemical Engineering Journal, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

A systematic analysis and evaluation of nutritional composition of 23 strains of marine microalgae commonly used in aquaculture - Jia-Xing Zhang; Zhao-Shou Ran; Hai-Xuan Xie; Fei Kong; Meng-Qi Zhang; Yao Zhou; Yan-Rong Li; Kai Liao; Xiao-Jun Yan; Ji-Lin Xu (Algal Research, 2023)

A new species of the genus Catillopecten (Bivalvia: Pectinoidea: Propeamussiidae): morphology, mitochondrial genome, and phylogenetic relationship - Yi-Tao Lin; Yi-Xuan Li; Yanan Sun; Jun Tao; Jian-Wen Qiu (Frontiers in Marine Science, 2023)
Catillopecten is a small genus of deep-sea glass scallops, but its diversity is poorly known in many parts of the world ocean. We described C. margaritatus n. sp. (Pectinoidea: Propeamussiidae), and performed morphological analyses and DNA sequencing, and estimated the divergence time of scallops based on samples collected from Haima cold seep in the South China Sea. Morphologically, the new species can be distinguished from congeneric species by its large shell size, relatively small auricle length, absence of monocrystal aerials, presence of longitudinal radial ridges on the left valve, and the alternated rounded striae and distal and proximal growth lines of prisms on the right valve. Anatomically, this new species can be distinguished from C. vulcani by its anteriorly located auriculate gills, compared to the centrally located lamellar gills of the latter, and the different locations of the pericardium. Sequence comparison and phylogenetic analysis based on the 18S rRNA fragments supported the placement of the new species in Catillopecten . We also report the mitogenome of C. margaritatus n. sp. as the only reported mitogenome of the family Propeamussiidae, which differs from those of other scallops substantially in gene order arrangement. Divergence time estimation revealed that Propeamussiidae and Pectinidae diverged in the early Carboniferous, while Catillopecten and Parvamussium diverged during the late Cretaceous to early Eocene. Finally, we presented a key to the species of Catillopecten .

Toxicological characteristics of drinking water in two large-scale municipal water supply systems of a metropolitan city in Central China - Huai-Ji Wang; Chen-Wei Peng; Xue Han; Yan Wang; Jie Zhang; Jun-Ling Liu; Meng-Xuan Zhou; Fei Tang; Ai-Lin Liu (Environmental Science and Pollution Research, 2023)

A large-scale continuous optimization benchmark suite with versatile coupled heterogeneous modules - Peilan Xu; Wenjian Luo; Xin Lin; Jiajia Zhang; Xuan Wang (Swarm and Evolutionary Computation, 2023)

Two new germacrane sesquiterpenoids from the inflorescences of Mikania micrantha - Tao Lou; Qiao-Lin Xu; Yu-Ling Tan; Shao-Bo Liu; Shan-Xuan Zhang; Ying Zeng; Feng-Qiang Jiang; Jian-Wen Tan (Phytochemistry Letters, 2023)

Ultrapotassic enclaves in the Miocene adakitic granitoids, southern Tibet: Direct evidence for collision-related crust-mantle interaction and its implications - Chang-da Wu; Yuan-chuan Zheng; Bo Xu; Zeng-qian Hou; Peng Chai; Xin Li; Lin-yuan Zhang; Zi-xuan Wang; Lu Wang; Yang Shen (Lithos, 2023)

Metformin alleviates ethanol-induced cardiomyocyte injury by activating AKT/Nrf2 signaling in an ErbB2-dependent manner - Yunjie Chen; Suyan Zhu; Zhu Lin; Yuanbin Zhang; Cheng Jin; Shengqu He; Xueqin Chen; Xuan Zhou (Molecular Biology Reports, 2023)

Deciphering basic and key traits of antibiotic resistome in influent and effluent of hospital wastewater treatment systems - Lin Zhu; Ling Yuan; Xin-Yi Shuai; Ze-Jun Lin; Yu-Jie Sun; Zhen-Chao Zhou; Ling-Xuan Meng; Feng Ju; Hong Chen (Water Research, 2023)

Investigation of biochar amendments on odor reduction and their characteristics during food waste co-composting - Minh Ky Nguyen; Chitsan Lin; Hong Giang Hoang; Xuan Thanh Bui; Huu Hao Ngo; Van Giang Le; Huu-Tuan Tran (Science of The Total Environment, 2023)

Effect of biomass retention time on performance and fouling of a stirred membrane photobioreactor - Bao-Trong Dang; Xuan-Thanh Bui; Thanh-Tin Nguyen; Huu Hao Ngo; Long D. Nghiem; Ky-Phuong-Ha Huynh; Thi-Kim-Quyen Vo; Thi-Dieu-Hien Vo; Chitsan Lin; Shiao-Shing Chen (Science of The Total Environment, 2023)

Validation and calibration of partitioned integral ocean wave parameters from co-polarized synthetic aperture radar data - Xuan Wang; Xinle Wang; Lin Ge (Remote Sensing of Environment, 2023)

Characterization of procyanidin extracts from hawthorn (Crataegus pinnatifida) in human colorectal adenocarcinoma cell line Caco-2, simulated Digestion, and fermentation identified unique and novel prebiotic properties - Xue Han; Qian Zhou; Zhe Gao; Guanying Bianca Xu; Hong Chen; Bimal Chitrakar; Yasai Sun; Wen Zhao; Xuan Lin; Kaixuan Zhou; Zhisheng Zhang (Food Research International, 2023)

Shaking table tests and seismic assessment of a full-scale precast concrete sandwich wall panel structure with bolt connections - Jia-Xuan He; Zhao-Dong Xu; Lian-Yu Zhang; Zhi-Hua Lin; Zhong-Wei Hu; Qiang-Qiang Li; Yao-Rong Dong (Engineering Structures, 2023)

Influence of plants on anammox process in constructed Wetland: Irrelevance, inhibition or enhancement - Jie Li; Lin Liu; Yu-Ming Zheng; Lin Ma; Quan-Bao Zhao; Xuan Wang; Chao-Xiang Liu (Chemical Engineering Journal, 2023)

Self-supply of H2O2 and O2 by a composite nanogenerator for chemodynamic therapy/hypoxia improvement and rapid therapy of biofilm-infected wounds - Junjie Wu; Peng Shen; Xian Qin; Yulu Yang; Chuanchuan Lin; Xuan Li; Wenbo Geng; Pengfei Gao; Lixue Chen; Li Miao; Yang Jiao; Bailong Tao (Chemical Engineering Journal, 2023)

Comparing the structural characteristics and expression of GA2ox gene in dwarf banana and its wild type - Jiaqi Lin; Dou Feng; Yanpei Li; Shixiang Xiao; Weiyan Xuan (Journal of Plant Biochemistry and Biotechnology, 2023)
It is necessary to understand the molecular mechanism of banana dwarfing mutation in order to improve the high stem character of banana varieties and breed the new excellent dwarf lines. To elucidate the molecular-level regulation of banana dwarf mutations and identify the relevant genes, the complete cDNA sequence of the gibberellin 2-oxidase gene ( GA2ox ) in the dwarf banana and its wild type was cloned by RT-PCR and the encoded amino acid sequences bioinformatically was analyzed. Meanwhile, the expression levels of banana GA2ox gene in different tissues of dwarfed banana and its wild type were analyzed by qRT-PCR. Between the GA2ox gene sequences of the dwarf banana and its wildtype, there were 5 base pairs of variation, leading to the predicted GA2ox proteins having different molecular weights, isoelectric points, fat indices, total numbers of positive and negative charges, and hydrophilicity. In addition, the expression of GA2ox in the leaves, stalks, and fruits of dwarf banana plants was higher than that in the wild type in the early and middle stages of banana development. The results showed that the GA2ox gene may have important regulatory effects on banana stem dwarfing, the knowledge of which can help our understanding and manipulation of this important plant.

Distribution and physical–biological controls of dimethylsulfide in the western tropical Indian Ocean during winter monsoon - Shi-Mei Liang; Xing Zhai; Cheng-Xuan Li; Ming Xin; Ping Sun; Xuan-Li Liu; Lin Liu; Bao-Dong Wang (Frontiers in Marine Science, 2023)
New field observation on distribution, turnover, and sea–air flux of three dimethylated sulfur compounds (dimethylsulfide (DMS), dimethylsulfoniopropionate, and dimethylsulfoxide) in the western tropical Indian Ocean (WTIO; 4°N–10°S, 61°–65°E) were conducted under the major Global Change and Air–Sea Interaction Program during the 2021/2022 Northeast Monsoon (December 21, 2021 to January 11, 2022). Significantly high surface concentrations of DMS were identified in the region of the Seychelles–Chagos Thermocline Ridge (SCTR; 5°–10°S). This occurred because the shallow thermocline/nitracline and associated upwelling fueled biological production of DMS in the subsurface, which was brought to the surface through vertical mixing. The calculated sea–air DMS flux was also significantly strong in the SCTR region during the Northeast Monsoon owing to combination of high wind speed and high surface concentration of DMS. This finding is similar to results obtained previously during the Southwest Monsoon, suggesting that the SCTR region is an area of active DMS emission during both the Northeast Monsoon and the Southwest Monsoon. Microbial consumption was the dominant pathway of DMS removal, accounting for 74.4% of the total, whereas the processes of photolysis (17.7%) and ventilation (7.9%) were less important. Future work should be undertaken in the WTIO to establish how DMS emission is linked to aerosol properties and climate change.

Facile synthesis of triazine-based microporous organic network for high-efficient adsorption of flumequine and nadifloxacin: A comprehensive study on adsorption mechanisms and practical application potentials - Zhe Zhao; Shumin Lin; Zhendong Yu; Ming Su; Bolong Liang; Shu-Xuan Liang; Xue-Hai Ju (Chemosphere, 2023)

Templating agent-mediated Cobalt oxide encapsulated in Mesoporous silica as an efficient oxone activator for elimination of toxic anionic azo dye in water: Mechanistic and DFT-assisted investigations - Ta Cong Khiem; Po-Hsin Mao; Young-Kwon Park; Xiaoguang Duan; Bui Xuan Thanh; Chechia Hu; Suresh Ghotekar; Yiu Fai Tsang; Kun-Yi Andrew Lin (Chemosphere, 2023)

Development of a low-density SNP genotyping panel by a novel technology mGPS and its application in germplasm identification of abalone - Weihong Lin; Qizhen Xiao; Feng Yu; Zhaofang Han; Junyu Liu; Wenzhu Peng; Zekun Huang; Yuting Lei; Weiguo Li; Weiwei You; Xuan Luo; Caihuan Ke (Aquaculture, 2023)

Preferred prey reduce species realized niche shift and improve range expansion prediction - Lixia Han; Zhixin Zhang; Weishan Tu; Qing Zhang; Yanhua Hong; Shengnan Chen; Zhiqiang Lin; Shimin Gu; Yuanbao Du; Zhengjun Wu; Xuan Liu (Science of The Total Environment, 2023)

Ecological risk assessment and corrective actions for dioxin-polluted sediment in a chemical plant's brine water storage pond - Chi-Wei Huang; Wen-Yen Huang; Chitsan Lin; Yi-Lin Li; Tsung-Po Huang; Xuan-Thanh Bui; Huu Hao Ngo (Science of The Total Environment, 2023)

Seasonal influence on pollution index and risk of multiple compositions of microplastics in an urban river - Chi-Wei Huang; Yi-Lin Li; Chitsan Lin; Xuan-Thanh Bui; Thi-Dieu-Hien Vo; Huu Hao Ngo (Science of The Total Environment, 2023)

Catalytic pyrolysis of 5-Amino-1H-Tetrazole with copper and its oxide: A deep insight into the combustion mechanism for high nitrogen compound - Si-Yuan Zhou; Jiu Chen; Xuan Li; Fan Jia; Dan Zhang; Li-Feng Xie; Bin Li; Lin Jiang (Fuel, 2023)

Plastome evolution and phylogenomics of Impatiens (Balsaminaceae) - He Qiu; Zhi-Hui Zhang; Mei-Zhen Wang; Xin-Jie Jin; Jie-Dong Lin; Hans Peter Comes; Jing-Xuan Chen; Rui-Ning Cui; Ru-Qing Duan; Pan Li (Planta, 2023)

Establishment of an efficient method for kiwifruit in vitro micrografting - Wantian Yao; Lingling Kong; Diya Lei; Bing Zhao; Honglan Tang; Xuan Zhou; Yuanxiu Lin; Yunting Zhang; Yan Wang; Wen He; Mengyao Li; Qing Chen; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Detection and genetic analysis of porcine circovirus-like virus in pigs with diarrhea between 2016 and 2021 in Henan and Shanxi provinces of China - Liu-Hui Zhang; Lin-Qing Wang; Hong-Xuan Li; Hong-Lei Zhang; Lan-Lan Zheng; Xi-Meng Chen; Hong-Ying Chen (Archives of Virology, 2023)

Experimental study on failure law of subgrade concrete with different damage base - Xiangfeng Lv; Lingfeng Meng; Xin Lin; Xuan Ji; Yahan Yang (European Journal of Environmental and Civil Engineering, 2023)

Photocatalytic degradation of dissolved organic matter in landfill leachate by heterostructural ZnO-rGO composite catalysts - Bicai Li; Xuan Lin; Ziying Qi; Meng Dong; Caiyun Gao; Hong Zhang; Zhicheng Li (Environmental Science and Pollution Research, 2023)

Evaluating the release and metabolism of ricinine from castor cake fertilizer in soils using a LC-QTOF/MS coupled with SIRIUS workflow - Kai-Xuan Zheng; Cheng-Hua Liu; Sichao Wang; Yu-Min Tzou; Chih-Min Chiang; Shiou-Ruei Lin; Hsiao-Ying Yang; Jerry J. Wu; Ya-Hui Chuang (Chemosphere, 2023)

The tiered transaction system for sea use rights in China: Theoretical basis and market construction - Xuan Yu; Sen Lin; Weiteng Shen; Qi Chen (Marine Policy, 2023)

Composition of dissolved organic matter (DOM) in wastewater treatment plants influent affects the efficiency of carbon and nitrogen removal - Ling Wen; Fang Yang; Xuan Li; Siwan Liu; Yuye Lin; En Hu; Li Gao; Ming Li (Science of The Total Environment, 2023)

Quantification of N and C cycling during aerobic composting, including automated direct measurement of N2, N2O, NO, NH3, CO2 and CH4 emissions - Yubo Cao; Xuan Wang; Tom Misselbrook; Rui Wang; Xunhua Zheng; Lin Ma (Science of The Total Environment, 2023)

Assessment of algae and greenhouse gases in different reservoirs worldwide by reactor model - Yi-Xuan Li; Kai-Kai Deng; Shu-Qing Zhang; Gui-Jiao Lin; Fang Fang; Jin-Song Guo (Journal of Cleaner Production, 2023)

Can hot water injection with chemical additives be an alternative to steam injection: Static and dynamic experimental evidence - Xuan Du; Tong Liu; Changfeng Xi; Bojun Wang; Zongyao Qi; You Zhou; Jiacheng Xu; Lixing Lin; Georgeta Istratescu; Tayfun Babadagli; Huazhou Andy Li (Fuel, 2023)

Effects of physiologic activities of plankton on CO2 flux in the Three Gorges Reservoir after rainfall during algal blooms - Yi-Xuan Li; Kai-Kai Deng; Gui-Jiao Lin; Bin Chen; Fang Fang; Jin-Song Guo (Environmental Research, 2023)

Biodegradation of high di-(2-Ethylhexyl) phthalate (DEHP) concentration by food waste composting and its toxicity assessment using seed germination test - Huu-Tuan Tran; Chitsan Lin; Su Shiung Lam; Thi Hieu Le; Hong-Giang Hoang; Xuan-Thanh Bui; Eldon R. Rene; Po Han Chen (Environmental Pollution, 2023)

Prenatal exposure to phthalates and polybrominated diphenyl ethers on neonatal health: A birth cohort study in Guangxi, China - Bo Qian; Zhao-xuan Zheng; Lei Yang; Cheng-qiang Wang; Yu-Chun Lin; Zhong-Ning Lin (Environmental Research, 2023)

A High-efficiency blue-LED-excitable NIR-II-emitting MgO:Cr3+,Ni2+ phosphor for future broadband light source toward multifunctional NIR spectroscopy applications - Bo-Mei Liu; Xiao-Xuan Guo; Lu-Yu Cao; Lin Huang; Rui Zou; Zhi Zhou; Jing Wang (Chemical Engineering Journal, 2023)

Correction to: Reforming China’s fertilizer policies: implications for nitrogen pollution reduction and food security - Xiaoxi Wang; Meng Xu; Bin Lin; Benjamin Leon Bodirsky; Jiaqi Xuan; Jan Philipp Dietrich; Miodrag Stevanović; Zhaohai Bai; Lin Ma; Shuqin Jin; Shenggen Fan; Hermann Lotze-Campen; et al. (Sustainability Science, 2023)

Reforming China’s fertilizer policies: implications for nitrogen pollution reduction and food security - Xiaoxi Wang; Meng Xu; Bin Lin; Benjamin Leon Bodirsky; Jiaqi Xuan; Jan Philipp Dietrich; Miodrag Stevanović; Zhaohai Bai; Lin Ma; Shuqin Jin; Shenggen Fan; Hermann Lotze-Campen; et al. (Sustainability Science, 2023)
Reactive nitrogen (N) is a requisite nutrient for agricultural production, but results in greenhouse gas and air and water pollution. The environmental and economic impacts of N fertilizer use in China are particularly relevant, as China consumes the largest amount of N fertilizer in the world to meet its soaring food demand. Here, we use an agro-economic land system model (MAgPIE) in combination with a difference-in-differences econometric model to provide a forward-looking assessment of China’s fertilizer policies in terms of removing fertilizer manufacturing subsidies and implementing measures to improve agricultural nutrient management efficiency. Our model results indicate that enhancing soil N uptake efficiency and manure recycled to soil alongside fertilizer subsidy removal can largely reduce N fertilizer use and N losses and abate N pollution in the short and long term, while food security remains largely unaffected. Enhancing soil N uptake efficiency appears to be decisive to achieving China’s national strategic target of zero growth in N fertilizer use. This study also finds that improving agricultural nutrient management efficiency contributes to higher land productivity and less cropland expansion, with substantial benefits for the environment and food security.

Physiological and transcriptome analysis of Mytilus coruscus in response to Prorocentrum lima and microplastics - Xiao-wen Tang; Rong Yu; Mei-hua Fan; Zhi Yang; Zhi Liao; Zong-xin Yang; Chen-ying Xie; Yu-kun Xuan; Jian-xin Wang; Xiao-lin Zhang; Xiao-jun Yan (Frontiers in Marine Science, 2022)
Nowadays, diarrheic shellfish toxicity (DSP) toxin and microplastics (MPs) are commonly found in coastal waters worldwide. Due to their widespread use, their persistence and toxicity, they may induce adverse effects on Mytilus coruscus . However, the underlying toxic mechanisms of DSP and MPs on M. coruscus remain unclear. This study explored the physiological index and transcriptome change of the digestive gland of adult M. coruscus exposed for 3 days to polystyrene (PS) MPs (0.2 mg/L, 90-100 μm) and Prorocentrum lima alone or in combination. The results showed that the CAT activity and MDA content significantly increased, respiration rate and feeding rate significantly decreased. The combination of MPs and P. lima caused more structural damage to the rough surface endoplasmic reticulum and mitochondria in the digestive glands of M. coruscus . The transcriptome analysis showed that 485 and 220 genes were up- and down-regulated, respectively, after exposure to P. lima ; 1,989 up-regulated DEGs and 1,098 down-regulated DEGs were identified after exposure to MP treatment, and 1,004 up-regulated DEGs and 664 down-regulated DEGs were identified after exposure to the combination of P. lima and MPs. The DEGs were mainly enriched in the lysosome, mRNA surveillance pathway, carbon metabolism, the mTOR signaling pathway, the complement and coagulation cascades, and the TNF signaling pathway. The MP, P. lima exposure mainly induced the expression of RNA-binding protein musashi, serine/arginine repetitive matrix protein 1, low affinity immunoglobulin epsilon Fc receptor, toll-like receptor 2, caspase 7, calmodulin, E3 ubiquitin-protein ligase, serine/threonine-protein kinase PRP4, glutathione S-transferase, and heat shock 70 kDa protein. MPs and P. lima poison mainly influence the expression of RNA transport, immune related gene, apoptosis, signal related gene, and antioxidant gene change. The combination of MPs and P. lima has a synergistic toxic effect. This study provides a new insights into its physiological and molecular responses of M. coruscus to MPs and P. lima toxic exposure.

Mitochondrial DNA Diversity of Mesocricetus auratus and Other Cricetinae Species among Cricetidae Family - Ruijing Xuan; Jiping Gao; Qiang Lin; Wenbin Yue; Tianfu Liu; Songnian Hu; Guohua Song (Biochemical Genetics, 2022)

Effects of tillage and cropping sequences on crop production and environmental benefits in the North China Plain - Wen-Xuan Liu; Wen-Sheng Liu; Mu-Yu Yang; Yu-Xin Wei; Zhe Chen; Ahmad Latif Virk; Rattan Lal; Xin Zhao; Hai-Lin Zhang (Environmental Science and Pollution Research, 2022)

Sestrin2 attenuates renal damage by regulating Hippo pathway in diabetic nephropathy - Yawei Bian; Chonglin Shi; Shan Song; Lin Mu; Ming Wu; Duojun Qiu; Jiajia Dong; Wei Zhang; Chen Yuan; Dongyun Wang; Zihui Zhou; Xuan Dong; et al. (Cell and Tissue Research, 2022)

Correction to: Higher sequestration of wheat versus maize crop carbon in soil under rotations - Zheng-Rong Kan; Shou-Wei Han; Wen-Xuan Liu; Xin Zhao; Rattan Lal; Hai-Lin Zhang (Environmental Chemistry Letters, 2022)

PLXDC2 enhances invadopodium formation to promote invasion and metastasis of gastric cancer cells via interacting with PTP1B - Bin Wu; Yan-xia Wang; Jun-jie Wang; Dong-fang Xiang; Meng-si Zhang; Ze-xuan Yan; Wen-ying Wang; Jing-ya Miao; Xi Lan; Jia-jia Liu; Zheng-yan Li; Chuan Li; et al. (Clinical & Experimental Metastasis, 2022)
Plexin-domain containing 2 (PLXDC2) has been reported as an oncoprotein in several human malignancies. However, its expression and roles in gastric cancer remain largely unclear. In this study, we found that PLXDC2 was highly expressed in gastric cancer tissues, and the expression levels were positively correlated with clinicopathological features, but negatively with the patients’ outcome. Cox regression analysis identified PLXDC2 as an independent prognostic indicator for the patients. Knockdown of PLXDC2 markedly suppressed the in vitro invasion and in vivo metastasis of gastric cancer cells, while overexpression of PLXDC2 resulted in opposite effects. Mechanistically, PLXDC2 enhanced the level of phosphorylated Cortactin (p-Cortactin) by physically interacting with protein tyrosine phosphatase 1B (PTP1B), an important dephosphorylase, to prevent its dephosphorylating of p-Cortactin, thereby promoting the formation of invadopodia. Collectively, our results indicate that PLXDC2 contributes to the invasion and metastasis of gastric cancer by inhibiting PTP1B to facilitate the invadopodium formation, and may serve as a potential prognostic biomarker and a therapeutic target for this disease.

Sex differences in microstructural alterations in the corpus callosum tracts in drug-naïve children with ADHD - Qingxia Lin; Xuan Bu; Hong Chen; Yan Liang; Weiqian Wang; Yanhong Yi; Haixi Lin; Lu Lu; Yingxue Gao; Andan Qian; Shuangli Chen; Meihao Wang; et al. (Brain Imaging and Behavior, 2022)

Lelliottia steviae sp. nov. isolated from Stevia rebaudiana Bertoni - Jing Lin; Ke Huang; Jing-Yu Huang; Yuan-Ru Xiong; Meng-Meng Wei; Na Xiao; Jia Gao; Xuan-Kai Ding; Zi-Yang Ma; Jun-Hao Sang; Ling-Xian Kong; Zhi-Yun Hong; et al. (Archives of Microbiology, 2022)

Structure elucidation of a novel cyclic tripeptide from the marine-derived fungus Aspergillus ochraceopetaliformis DSW-2 - Yanyan Liao; Xuan Hong; Jing Yang; Jiang-Jiang Qin; Beibei Zhang; Jianhui Lin; Zongze Shao; Weiyi Wang (Natural Product Research, 2022)

Differentiation and Temperature Adaptation of Pampus Echinogaster Based on Genome-Wide SNPs - Yuan Li; Fangrui Lou; Shigang Liu; Hai Li; Jiali Xiang; Binbin Shan; Longshan Lin; Xuan Zhuang (Frontiers in Marine Science, 2022)
Climate change and overfishing have led to the degradation of the quality and stock of Pampus echinogaster. Exploring the genetic structure and local adaptive evolutionary mechanisms of P. echinogaster is crucial for the management of this species. This population genomic study of nine geographical populations of P. echinogaster in China was conducted by specific-locus amplified fragment sequencing (SLAF-seq). A total of 935,215 SLAF tags were obtained, and the average sequencing depth of the SLAF tags was 20.80×. After filtering, a total of 46,187 high-consistency genome-wide single nucleotide polymorphisms (SNPs) were detected. Based on all SNPs, the population size of the nine P. echinogaster geographical populations was large. The Shantou population had the lowest genetic diversity, and the Tianjin population had the highest. Moreover, the population genetic structure based on all SNPs revealed significant gene exchange and no significant genetic differentiation among the nine P. echinogaster geographical populations, probably because of the population expansion after the last glacial period, the lack of balance between migration and genetic drift, and the long-distance diffusion of eggs and larvae. We suspect that variation of material metabolism, ion transfer, breeding, stress response, and inflammatory reactions-related genes were critical for adaptation to spatially heterogeneous temperature selection in natural P. echinogaster populations.

New insight into the co-adsorption of oxytetracycline and Pb(II) using magnetic metal–organic frameworks composites in aqueous environment: co-adsorption mechanisms and application potentials - Meng-lu Wang; Zhe Zhao; Shumin Lin; Ming Su; Bolong Liang; Shu-xuan Liang (Environmental Science and Pollution Research, 2022)

Association between MAP3K4 gene polymorphisms and the risk of schizophrenia susceptibility in a Northeast Chinese Han population - Yang Sun; Ye Lv; Hui-Wen Ren; Guan-Yu Wang; Li-Na Xuan; Yi-Yang Luo; Zhi-Lin Luan (Metabolic Brain Disease, 2022)

Advanced Treatment Technologies for the Removal of Organic Chemical Sunscreens from Wastewater: a Review - ‬Huu-Tuan Tran; Bao-Trong Dang; Le Thi Thu Thuy; Hong-Giang Hoang; Xuan-Thanh Bui; Van-Giang Le; Chitsan Lin; Minh-Ky Nguyen; Kim-Qui Nguyen; Phuong-Thao Nguyen; Quach An Binh; Thi-Phuong Thuy Bui (Current Pollution Reports, 2022)

Complete genome analysis of the novel Shewanella phage vB_Sb_QDWS - Lin Tan; Guanhua Xuan; Hong Lin; Jingxue Wang (Archives of Virology, 2022)

Complete genome analysis of the newly isolated Vibrio phage vB_VpP_WS1 of the family Microviridae - Wenjing Xu; Guanhua Xuan; Hong Lin; Jingxue Wang (Archives of Virology, 2022)

Individual exposure to ambient PM2.5 and hospital admissions for COPD in 110 hospitals: a case-crossover study in Guangzhou, China - Jie-Qi Jin; Dong Han; Qi Tian; Zhao-Yue Chen; Yun-Shao Ye; Qiao-Xuan Lin; Chun-Quan Ou; Li Li (Environmental Science and Pollution Research, 2022)
Few studies have evaluated the short-term association between hospital admissions and individual exposure to ambient particulate matter (PM 2.5 ). Particularly, no studies focused on hospital admissions for chronic obstructive pulmonary disease (COPD) at the individual level. We assessed the short-term effects of PM 2.5 on hospitalization admissions for COPD in Guangzhou, China, during 2014–2015, based on satellite-derived estimates of ambient PM 2.5 concentrations at a 1-km resolution near the residential address as individual-level exposure for each patient. Around 40,002 patients with COPD admitted to 110 hospitals were included in this study. A time-stratified case-crossover design with conditional logistic regression models was applied to assess the effects of PM 2.5 based on a 1-km grid data of aerosol optical depth provided by the National Aeronautics and Space Administration on hospital admissions for COPD. Further, we performed stratified analyses by individual demographic characteristics and season of hospital admission. Around 10 μg/m 3 increase in individual-level PM 2.5 was associated with an increase of 1.6% (95% confidence interval [CI]: 0.6%, 2.7%) in hospitalization for COPD at a lag of 0–5 days. The impact of PM 2.5 on hospitalization for COPD was greater significantly in males and patients admitted in summer. Our study strengthened the evidence for the adverse effect of PM 2.5 based on satellite-based individual-level exposure data.

Higher sequestration of wheat versus maize crop carbon in soils under rotations - Zheng-Rong Kan; Shou-Wei Han; Wen-Xuan Liu; Xin Zhao; Rattan Lal; Hai-Lin Zhang (Environmental Chemistry Letters, 2022)

Mechanisms of soil organic carbon stability and its response to no‐till: A global synthesis and perspective - Zheng‐Rong Kan; Wen‐Xuan Liu; Wen‐Sheng Liu; Rattan Lal; Yash Pal Dang; Xin Zhao; Hai‐Lin Zhang (Global Change Biology, 2022)
Mechanisms of soil organic carbon (SOC) stabilization have been widely studied due to their relevance in the global carbon cycle. No‐till (NT) has been frequently adopted to sequester SOC; however, limited information is available regarding whether sequestered SOC will be stabilized for long term. Thus, we reviewed the mechanisms affecting SOC stability in NT systems, including the priming effects (PE), molecular structure of SOC, aggregate protection, association with soil minerals, microbial properties, and environmental effects. Although a more steady‐state molecular structure of SOC is observed in NT compared with conventional tillage (CT), SOC stability may depend more on physical and chemical protection. On average, NT improves macro‐aggregation by 32.7%, and lowers SOC mineralization in macro‐aggregates compared with CT. Chemical protection is also important due to the direct adsorption of organic molecules and the enhancement of aggregation by soil minerals. Higher microbial activity in NT could also produce binding agents to promote aggregation and the formation of metal‐oxidant organic complexes. Thus, microbial residues could be stabilized in soils over the long term through their attachment to mineral surfaces and entrapment of aggregates under NT. On average, NT reduces SOC mineralization by 18.8% and PE intensities after fresh carbon inputs by 21.0% compared with CT ( p Q 10 ) is observed in NT due to greater Q 10 in macro‐aggregates, an increase of soil moisture regime in NT could potentially constrain the improvement of Q 10 . This review improves process‐based understanding of the physical and chemical mechanism of protection that can act, independently or interactively, to enhance SOC preservation. It is concluded that SOC sequestered in NT systems is likely to be stabilized over the long term.

Responses of soil pH to no‐till and the factors affecting it: A global meta‐analysis - Xin Zhao; Cong He; Wen‐Sheng Liu; Wen‐Xuan Liu; Qiu‐Yue Liu; Wei Bai; Li‐Jun Li; Rattan Lal; Hai‐Lin Zhang (Global Change Biology, 2022)
No‐till (NT) is a sustainable option because of its benefits in controlling erosion, saving labor, and mitigating climate change. However, a comprehensive assessment of soil pH response to NT is still lacking. Thus, a global meta‐analysis was conducted to determine the effects of NT on soil pH and to identify the influential factors and possible consequences based on the analysis of 114 publications. When comparing tillage practices, the results indicated an overall significant decrease by 1.33 ± 0.28% in soil pH under NT than that under conventional tillage ( p −1 (−1.83%), or crop residue retention (−1.52%). Changes in organic matter decomposition under undisturbed soil and with crop residue retention might lead to a higher concentration of H + and lower of basic cations (i.e., calcium, magnesium, and potassium), which decrease the soil pH, and consequently, impact nutrient dynamics (i.e., soil phosphorus) in the surface layer under NT. Furthermore, soil acidification may be aggravated by NT within site‐specific conditions and improper fertilizer and crop residue management and consequently leading to adverse effects on soil nutrient availability. Thus, there is a need to identify strategies to ameliorate soil acidification under NT to minimize the adverse consequences.

Melatonin Reduces Neuroinflammation and Improves Axonal Hypomyelination by Modulating M1/M2 Microglia Polarization via JAK2-STAT3-Telomerase Pathway in Postnatal Rats Exposed to Lipopolysaccharide - Qiuping Zhou; Lanfen Lin; Haiyan Li; Huifang Wang; Shuqi Jiang; Peixian Huang; Qiongyu Lin; Xuan Chen; Yiyu Deng (Molecular Neurobiology, 2021)
Microglia activation and associated inflammation are implicated in the periventricular white matter damage (PWMD) in septic postnatal rats. This study investigated whether melatonin would mitigate inflammation and alleviate the axonal hypomyelination in the corpus callosum in septic postnatal rats. We further explored if this might be related to the modulation of microglial polarization from M1 phenotype to M2 through the JAK2/STAT3/telomerase pathway. We reported here that indeed melatonin not only can it reduce the neurobehavioral disturbances in LPS-injected rats, but it can also dampen microglia-mediated inflammation. Thus, in LPS + melatonin group, the expression of proinflammatory mediators in M1 phenotype microglia was downregulated. As opposed to this, M2 microglia were increased which was accompanied by upregulated expression of anti-inflammatory mediators along with telomerase reverse transcriptase or melatonin receptor 1(MT1). In parallel to this was decreased NG2 expression but increased expression of myelin and neurofilament proteins. Melatonin can improve hypomyelination which was confirmed by electron microscopy. In vitro in primary microglia stimulated by LPS, melatonin decreased the expression of proinflammatory mediators significantly; but it increased the expression of anti-inflammatory mediators. Additionally, the expression levels of p-JAK2 and p-STAT3 were significantly elevated in microglia after melatonin treatment. Remarkably, the effect of melatonin on LPS-treated microglia was blocked by melatonin receptor, JAK2, STAT3 and telomerase reverse transcriptase inhibitors, respectively. Taken together, it is concluded that melatonin can attenuate PWMD through shifting M1 microglia towards M2 via MT1/JAK2/STAT3/telomerase pathway. The results suggest a new therapeutic strategy whereby melatonin may be adopted to convert microglial polarization from M1 to M2 phenotype that would ultimately contribute to the attenuation of PWMD.

Two new diterpenoids with their antiproliferative activities from the supercritical fluid extraction of Croton crassifolius root - Chao Liu; Rui-rui Zhang; Qing-lin Niu; Jing Zhang; Mu-xuan Wang; Na-na Meng; Qing Wang; Jin-yue Sun; Wen-liang Wang (Natural Product Research, 2021)

Effects of Flow Velocity on the Growth and Survival of Haliotis discus hannai Larvae in the Recirculating Upflow System From the Point of Energy Metabolism - Mo Zhang; Xiaolong Gao; Mingxin Lyu; Shihui Lin; Ying Su; Xuan Luo; Weiwei You; Caihuan Ke (Frontiers in Marine Science, 2021)
For the abalone Haliotis discus hannai , attachment and metamorphosis are crucial stages in the transition from planktonic to benthic life. Increasing the larval metamorphosis rate by artificially controlling the external environment and simulating natural seawater flow is vital to enhance the hatchery efficiency of H. discus hannai . Thus, in the current study, an upflow recirculating aquaculture unit was designed for the rearing of larval abalone, and the larval hatching rate, survival rate, mode of energy metabolism, and expression levels of metamorphosis-related genes at different flow velocities (0, 5, 10, 20, and 40 L/h) were compared and analyzed. At flow velocities less than 20 L/h, no significant differences occurred in larval hatching, survival, and metamorphosis rates, whereas significant differences were recorded at flow rates of 20 and 40 L/h. Differences were also observed in the activity of enzymes, such as hexokinase (HK), pyruvate kinase (PK), lactate dehydrogenase (LDH), succinate dehydrogenase (SDH), and malate dehydrogenase (MDH), as well as glycogen levels, at the higher flow rates. These results suggested that velocity in excess of a certain limit leads to a higher glycolysis rate and transition of energy utilization from aerobic to anaerobic metabolism for the abalone larvae. Compared with conventional still-water aquacultural systems, the flow velocity at 5–10 L/h could maintain the water environment stability, and avoid both fertilized eggs from being densely deposited before hatching and the consumption of energy needed to resist high flow velocities. Thus, these results are useful references to enhance the hatchery efficiency, and to conduct large-scale rearing, of abalone larvae.

Effect of heat stress on oxidative damage and antioxidant defense system in white clover (Trifolium repens L.) - Hsiang-Lin Liu; Zhu-Xuan Lee; Tzu-Wei Chuang; Hui-Chen Wu (Planta, 2021)

The Beneficial Role of Exercise on Treating Alzheimer’s Disease by Inhibiting β-Amyloid Peptide - Zi-Xuan Tan; Fang Dong; Lin-Yu Wu; Ya-Shuo Feng; Feng Zhang (Molecular Neurobiology, 2021)

An efficient genetic manipulation protocol for dark septate endophyte Falciphora oryzae - Zhen-Zhu Su; Meng-Di Dai; Jia-Nan Zhu; Yu-Lan Zeng; Xuan-Jun Lu; Xiao-Hong Liu; Fu-Cheng Lin (Biotechnology Letters, 2021)

Comparative Study of the Feeding Characteristics and Digestion Physiology of Haliotis discus hannai and Haliotis gigantea - Mingxin Lyu; Xiaolong Gao; Mo Zhang; Shihui Lin; Xuan Luo; Weiwei You; Caihuan Ke (Frontiers in Marine Science, 2021)
Abalone ( Haliotis spp.) are typical nocturnal creatures but Haliotis discus hannai is bold and active in the nighttime whereas H. gigantea tends to be timid and inactive. In this study, we quantified and compared differences in movement, feeding, and digestive physiology between H. discus hannai and H. gigantea as well as the potential molecular mechanisms on the basis of video observations and expression levels of genes related to feeding regulation. The feeding behaviors of both species were characterized by significant circadian rhythms ( P < 0.05). However, the distance moved and the cumulative duration of movement were 2.61 and 1.94 times higher, respectively, in H. discus hannai than in H. gigantea over the 24-h cycle. The cumulative duration of feeding by H. discus hannai was only 1.15 times that by H. gigantea , but the feeding time as a percentage of the cumulative duration of movement (FTP) was up to 94.6% for H. gigantea and only 56.0% for H. discus hannai . The peaks for α-amylase activity and NPF expression levels in both species as well as the peak OX 2 R expression level in H. gigantea occurred during 20:00–00:00 h. By contrast, the peaks for alginate lyase activity and NPYR expression levels in H. discus hannai occurred at 16:00 h, when the FTP was significantly higher for H. discus hannai than for H. gigantea . These initial findings quantify specific behavior parameters and thus provide a reference for the selection of appropriate feeding strategies and the proliferation of abalone via bottom sowing.

Resource Status and Effect of Long-Term Stock Enhancement of Large Yellow Croaker in China - Jigui Yuan; Hungdu Lin; Lisheng Wu; Xuan Zhuang; Junkai Ma; Bin Kang; Shaoxiong Ding (Frontiers in Marine Science, 2021)
The large yellow croaker, Larimichthys crocea , was once the most abundant and economically important marine fish in China. Thus far, it has also been the most successful mariculture fish species in China. However, its wild stock severely declined in the 1970s because of overexploitation, and therefore hatchery release has been carried out for stock enhancement since 2000. As a migratory fish, large yellow croaker was divided into three geographical stocks according to ambiguous morphological and biological characteristics in early documents. To investigate the identity of wild large yellow croaker populations and assess the influence of hatchery supplementation on wild populations, a total of 2,785 cultured individuals and 591 wild individuals were collected from 91 hatcheries and six wild populations along the coast of mainland China and analyzed using two mitochondrial genes [cytochrome oxidase I ( COI ) and cytochrome b ( Cyt b )] and one nuclear gene ( RyR3 ). The higher haplotype diversity and moderate nucleotide diversity of wild large yellow croaker indicated that overexploitation, which caused a sharp decrease in biomass, did not lead to a loss of genetic diversity. According to phylogenetic construction and network analysis, the absence of a significant population structure pattern revealed a single panmictic population of wild large yellow croaker with exception of a population collected from the Sansha Bay, which showed high genetic relatedness to the cultured population, suggesting significant genetic effects resulting from stock enhancement. Overall, our study suggests no genetic differentiation in the entire wild population of large yellow croaker, which means that we have great flexibility in mixing and matching farmed and wild populations. However, since the result showed that domestication, the relaxation of purifying selection, increased genetic loads, and maladapted farmed fish will be at a selective disadvantage when cultured juveniles are released in the wild, the effectiveness of stock enhancement and the negative impact of hatchery-wild fish hybridization on the wild population must be carefully evaluated in future.

Experimental study on integrated and autonomous conductivity-temperature-depth (CTD) sensor applied for underwater glider - Bin Lv; Hai-lin Liu; Yi-fan Hu; Cheng-xuan Wu; Jie Liu; Hai-jing He; Jie Chen; Jian Yuan; Zhao-wen Zhang; Lin Cao; Hui Li (Marine Georesources & Geotechnology, 2021)

Contamination, source attribution, and potential health risks of heavy metals in street dust of a metropolitan area in Southern Vietnam - Nguyen Duy Dat; Van-Truc Nguyen; Thi-Dieu-Hien Vo; Xuan-Thanh Bui; Manh-Ha Bui; Ly Sy Phu Nguyen; Xuan-Cuong Nguyen; Anh Thi-Kim Tran; Thi-Tinh-Au Nguyen; Yun-Ru Ju; Thi-Minh-Trang Huynh; Duy-Hieu Nguyen; et al. (Environmental Science and Pollution Research, 2021)

Facile carboxylation of natural eggshell membrane for highly selective uranium (VI) adsorption from radioactive wastewater - Sensen Xuan; Bo Zhang; Lin Xiao; Guoqiang Li; Yaping Zhang; Yabin Zhang; Jinchao Li (Environmental Science and Pollution Research, 2021)

Future variation in mountainous discharge in arid northwestern China: A basin case study - Lei Wu; Chang-bin Li; Xu-hong Xie; Jia-nan Lv; Jian-mei Wei; Xuan Zhou; Lin-shan Yang (Journal of Mountain Science, 2021)

The Individual and Synergistic Indexes for Assessments of Heavy Metal Contamination in Global Rivers and Risk: a Review - Hong-Giang Hoang; Chitsan Lin; Chow-Feng Chiang; Xuan-Thanh Bui; Wisanukorn Lukkhasorn; Thi-Phuong-Thuy Bui; Huu-Tuan Tran; Thi-Dieu-Hien Vo; Van-Giang Le; Long D. Nghiem (Current Pollution Reports, 2021)

Characteristics of bacterial community and ARGs profile in engineered goldfish tanks with stresses of sulfanilamide and copper - Benjamin Makimilua Tiimub; Zhen-chao Zhou; Lin Zhu; Yang Liu; Xin-Yi Shuai; Lan Xu; Christophe’ Niyungeko; Ling-Xuan Meng; Yu-Jie Sun; Hong Chen (Environmental Science and Pollution Research, 2021)

Molecular mapping of quantitative disease resistance loci for soybean partial resistance to Phytophthora sansomeana - Feng Lin; Wenlong Li; Austin G. McCoy; Xuan Gao; Paul J. Collins; Na Zhang; Zixiang Wen; Sizhe Cao; Shabir H. Wani; Cuihua Gu; Martin I. Chilvers; Dechun Wang (Theoretical and Applied Genetics, 2021)

Comparative analysis of sRNAs, degradome and transcriptomics in sweet sorghum reveals the regulatory roles of miRNAs in Cd accumulation and tolerance - Weitao Jia; Kangqi Lin; Tengxue Lou; Juanjuan Feng; Sulian Lv; Ping Jiang; Ze Yi; Xuan Zhang; Duoliya Wang; Zijing Guo; Yetao Tang; Rongliang Qiu; et al. (Planta, 2021)

Common and specific neural correlates underlying insight and ordinary problem solving - Jiabao Lin; Xue Wen; Xuan Cui; Yanhui Xiang; Jiushu Xie; Yajue Chen; Ruiwang Huang; Lei Mo (Brain Imaging and Behavior, 2021)

The resurgent landscape of xenotransplantation of pig organs in nonhuman primates - Xuan Zhang; Quancheng Wang; Jingjun Zhao; Xiao Li; Wei Peng; Zhaoxu Yang; Zhibin Lin; Long Yang; Rui Ding; Kaishan Tao; Kefeng Dou (Science China Life Sciences, 2021)

Remediation of contaminated soil and groundwater using chemical reduction and solidification/stabilization method: a case study - Shi-Feng Lu; Yu-Lin Wu; Zhan Chen; Tao Li; Chao Shen; Lin-Kang Xuan; Ling Xu (Environmental Science and Pollution Research, 2021)

NLRP3 inflammasome priming and activation in cholestatic liver injury via the sphingosine 1-phosphate/S1P receptor 2/Gα(12/13)/MAPK signaling pathway - Lei Hou; Zhi Zhang; Le Yang; Na Chang; Xinhao Zhao; Xuan Zhou; Lin Yang; Liying Li (Journal of Molecular Medicine, 2021)

Associations of Serum Selenium Levels in the First Trimester of Pregnancy with the Risk of Gestational Diabetes Mellitus and Preterm Birth: a Preliminary Cohort Study - Peng Ju Liu; Aimin Yao; Liangkun Ma; Xiao Yan Chen; Song Lin Yu; Yanping Liu; Yi Xuan Hou (Biological Trace Element Research, 2021)

A DEM fusion method for ascending and descending orbit StereoSAR DEMs in complicated mountain areas considering SAR echo intensity - Guo-lin Cai; Dong Shen; Ao-li Zhang; Hai-hua Yu; Xuan-yu Zhang (Journal of Mountain Science, 2021)

Benzophenanthridine alkaloids suppress lung adenocarcinoma by blocking TMEM16A Ca2+-activated Cl− channels - Gaohua Zhang; Lin Zhu; Yucong Xue; Zhijun Zhao; Honglin Li; Zhiyun Niu; Xiangchong Wang; Pingping Chen; Jianping Zhang; Xuan Zhang (Pflügers Archiv - European Journal of Physiology, 2020)

Feasibility of using bed filters packed with rice-straw-based activated carbon and selected biomass waste for the control of frying fume exhaust - Yen-Chi Chen; Xuan-En Yang; Kun-Yi Lin; Wei-Wen Huang; Chi-Chi Lin; Kuo-Pin Yu (Environmental Science and Pollution Research, 2020)

Assessment of heavy metal contamination and adverse biological effects of an industrially affected river - Gavin Yeh; Hong-Giang Hoang; Chitsan Lin; Xuan-Thanh Bui; Huu-Tuan Tran; Chien-Chuan Shern; Chi-Thanh Vu (Environmental Science and Pollution Research, 2020)

Identification of Cyt2Ba from a New Strain of Bacillus thuringiensis and Its Toxicity in Bradysia difformis - Fan-Fan Wang; Shao-Xuan Qu; Jin-Sheng Lin; Hui-Ping Li; Li-Juan Hou; Ning Jiang; Xin Luo; Lin Ma (Current Microbiology, 2020)
Bradysia difformis is one of the most damaging pests in mushroom production in China. In this study, eight Bacillus thuringiensis strains were analyzed for insecticidal activity in B. difformis . The strain JW-1 showed the highest insecticidal activity against B. difformis larvae, but did not inhibit the mycelial growth of Pleurotus ostreatus and P. geesteranus . The 16S rRNA gene (1397 bp) and cyt2 gene (792 bp) were obtained from strain JW-1. The phylogenetic tree based on 16S rRNA gene and Cyt2 toxin showed that strain JW-1 was a member of B. thuringiensis and Cyt2 toxin belonged to Cyt2Ba toxin cluster. The Cyt2Ba toxin from strain JW-1 was overexpressed in E. coli as a fusion protein and the fusion protein (70 kDa) was purified by Ni-IDA affinity chromatography. The purified Cyt2Ba fusion protein was toxic to B. difformis larvae (LC 50 was 2.25 ng/mL). The identification of Cyt2Ba from strain JW-1 and confirmation of the insecticidal activity of Cyt2Ba in B. difformis provided a new means of biological control of the important pest in mushroom production.

Experimentally Induced Sepsis Causes Extensive Hypomyelination in the Prefrontal Cortex and Hippocampus in Neonatal Rats - Peixian Huang; Xuan Chen; Xiaoli Hu; Qiuping Zhou; Lanfen Lin; Shuqi Jiang; Hui Fu; Yajie Xiong; Hongke Zeng; Ming Fang; Chunbo Chen; Yiyu Deng (NeuroMolecular Medicine, 2020)

Drought-tolerant plant growth-promoting rhizobacteria isolated from jujube (Ziziphus jujuba) and their potential to enhance drought tolerance - Min Zhang; Lin Yang; Ruqian Hao; Xiaoxiong Bai; Ying Wang; Xuan Yu (Plant and Soil, 2020)

GPI7‐mediated glycosylphosphatidylinositol anchoring regulates appressorial penetration and immune evasion during infection of Magnaporthe oryzae - Caiyun Liu; Junjie Xing; Xuan Cai; Ahmed Hendy; Wenhui He; Jun Yang; Junbing Huang; You‐Liang Peng; Lauren Ryder; Xiao‐Lin Chen (Environmental Microbiology, 2020)
Summary Glycosylphosphatidylinositol (GPI) anchoring plays key roles in many biological processes by targeting proteins to the cell wall; however, its roles are largely unknown in plant pathogenic fungi. Here, we reveal the roles of the GPI anchoring in Magnaporthe oryzae during plant infection. The GPI‐anchored proteins were found to highly accumulate in appressoria and invasive hyphae. Disruption of GPI7 , a GPI anchor‐pathway gene, led to a significant reduction in virulence. The Δ gpi7 mutant showed significant defects in penetration and invasive growth. This mutant also displayed defects of the cell wall architecture, suggesting GPI7 is required for cell wall biogenesis. Removal of GPI‐anchored proteins in the wild‐type strain by hydrofluoric acid (HF) pyridine treatment exposed both the chitin and β‐1,3‐glucans to the host immune system. Exposure of the chitin and β‐1,3‐glucans was also observed in the Δ gpi7 mutant, indicating GPI‐anchored proteins are required for immune evasion. The GPI anchoring can regulate subcellular localization of the Gel proteins in the cell wall for appressorial penetration and abundance of which for invasive growth. Our results indicate the GPI anchoring facilitates the penetration of M. oryzae into host cells by affecting the cell wall integrity and the evasion of host immune recognition.

Perilipin LDP1 coordinates lipid droplets formation and utilization for appressorium‐mediated infection in Magnaporthe oryzae - Xuan Cai; Jingjing Yan; Caiyun Liu; Junjie Xing; Zhiyong Ren; Ahmed Hendy; Lu Zheng; Junbin Huang; Xiao‐Lin Chen (Environmental Microbiology, 2020)
Summary Lipid droplets (LDs) serve as one of the major reservoirs in conidia of Magnaporthe oryzae and are quickly utilized during appressorium formation. Here, we identified a gene, LDP1 , encoding a perilipin that is important for LD formation and utilization during appressorium maturation. LDP1 is highly expressed in conidium and immature appressorium. Disruption mutants of LDP1 were significantly reduced in virulence, due to appressorial turgor reduction and difficulty in penetration. LDs were significantly reduced in the Δ ldp1 mutant, indicating LDP1 was required for LDs formation. LDP1 was colocalized with the LDs in conidium and immature appressorium but was gradually separated during appressorium maturation. A typical intracellular triacylglycerol lipase, TGL1‐2, was clearly separated with LDs in conidium and immature appressorium but was well colocalized with LDs during appressorium maturation. The subcellular localization of TGL1‐2 was affected by LDP1. These data suggested that LDP1 was bound to LDs for protecting from utilization in conidia and at the early appressorium stage but was separated from LDs for lipase entering and degradation. LDP1 was phosphorylated by CPKA at Thr96, which was essential for its localization and functions. These data indicate perilipin LDP1 can coordinate LD formation and utilization for appressorium‐mediated infection of M . oryzae .

Aberrant white matter properties of the callosal tracts implicated in girls with attention-deficit/hyperactivity disorder - Qingxia Lin; Xuan Bu; Meihao Wang; Yan Liang; Hong Chen; Weiqian Wang; Yanhong Yi; Haixi Lin; Jiaxiu Zhou; Lu Lu; Xinyu Hu; Chuang Yang; et al. (Brain Imaging and Behavior, 2020)

A novel narnavirus from the plant-pathogenic fungus Magnaporthe oryzae - Yuan Lin; Jia Zhou; Xuan Zhou; Simin Shuai; Rendi Zhou; Hongliu An; Shouguo Fang; Songbai Zhang; Qingchao Deng (Archives of Virology, 2020)

Data rescue in manuscripts: a hydrological modelling study example - Xuan Yu; Anna Lamačová; Lele Shu; Christopher Duffy; Pavel Krám; Jakub Hruška; Tim White; Kairong Lin (Hydrological Sciences Journal, 2020)

Preparation of Novel ALRCs/nZVI Composite and Its Removal of Cr(VI) from Aqueous - Xuan Zhang; Xiao-qiang Cao; Guang Li; Jijie Yin; Di Zhang; Mingzhen Li; Na Meng; Liang Dong; Xian-jun Lyu; Lin Li; Jun Qiu; Yan Zhang; et al. (International Journal of Environmental Research, 2020)

Fractional Stochastic Interval Programming for Optimal Low Impact Development Facility Category Selection under Uncertainty - Jinjin Gu; Hui Hu; Lin Wang; Wei Xuan; Yuan Cao (Water Resources Management, 2020)

Evaluation of groundwater sustainable development considering seawater intrusion in Beihai City, China - Chuangming Ma; Yonggang Li; Xuan Li; Lin Gao (Environmental Science and Pollution Research, 2020)

Breakup unconformities at the end of the early Oligocene in the Pearl River Mouth Basin, South China Sea: significance for the evolution of basin dynamics and tectonic geography during rift–drift transition - Yue Gong; Changsong Lin; Zhongtao Zhang; Bo Zhang; Liangfeng Shu; Xuan Feng; Fanghao Hong; Zuochang Xing; Hanyao Liu; Enyu Su (Marine Geophysical Research, 2019)

Fatty acid composition and the evidence for mixed income–capital breeding in female Argentinean short-fin squid Illex argentinus - Dongming Lin; Fei Han; Sipeng Xuan; Xinjun Chen (Marine Biology, 2019)

Relationship between warfarin dosage and international normalized ratio: a dose–response analysis and evaluation based on multicenter data - Ling Xue; Yuzhen Zhang; Cheng Xie; Ling Zhou; Linsheng Liu; Haiyan Zhang; Lianhong Xu; Hongtao Song; Meiqin Lin; Hanfan Qiu; Junrong Zhu; Yubing Zhu; et al. (European Journal of Clinical Pharmacology, 2019)

Natural and synthetic flavonoids, novel blockers of the volume-regulated anion channels, inhibit endothelial cell proliferation - Yucong Xue; Honglin Li; Yuanyuan Zhang; Xue Han; Gaohua Zhang; Wenya Li; Huiran Zhang; Yue Lin; Pingping Chen; Xiaorun Sun; Yalei Liu; Li Chu; et al. (Pflügers Archiv - European Journal of Physiology, 2018)

TMEM88 mediates inflammatory cytokines secretion by regulating JNK/P38 and canonical Wnt/β-catenin signaling pathway in LX-2 cells - Tao Xu; Lin-xin Pan; Yun-xuan Ge; Peng Li; Xiao-ming Meng; Cheng Huang; Jun Li (Inflammopharmacology, 2018)

Research on In Situ Stress Measurement and Inversion, and its Influence on Roadway Layout in Coal Mine with Thick Coal Seam and Large Mining Height - Song Zhifei; Sun Yun-jiang; Lin Xuan (Geotechnical and Geological Engineering, 2018)

Total arsenic concentrations in Chinese children’s urine by different geographic locations, ages, and genders - Xuan Zhang; Beibei Wang; Xiaoyong Cui; Chunye Lin; Xitao Liu; Jin Ma (Environmental Geochemistry and Health, 2018)

Rice ecosystem services in South-east Asia - Josef Settele; Kong Luen Heong; Ingolf Kühn; Stefan Klotz; Joachim H. Spangenberg; Gertrudo Arida; Alexis Beaurepaire; Silke Beck; Erwin Bergmeier; Benjamin Burkhard; Roland Brandl; Jesus Victor Bustamante; et al. (Paddy and Water Environment, 2018)

Surface wave attenuation based polarization attributes in time-frequency domain for multicomponent seismic data - Xuan-Lin Kong; Hui Chen; Zhi-Quan Hu; Jia-Xing Kang; Tian-Ji Xu; Lu-Ming Li (Applied Geophysics, 2018)

Nanoparticle-encapsulated emodin decreases diabetic neuropathic pain probably via a mechanism involving P2X3 receptor in the dorsal root ganglia - Lin Li; Xuan Sheng; Shanhong Zhao; Lifang Zou; Xinyao Han; Yingxin Gong; Huilong Yuan; Liran Shi; Lili Guo; Tianyu Jia; Shuangmei Liu; Bing Wu; et al. (Purinergic Signalling, 2017)

Comparison of the ameliorative effects of Qingfei Tongluo formula and azithromycin on Mycoplasma pneumoniae pneumonia - Zhen Xiao; Yonghong Jiang; Xuan Gao; Shuzhu Lin; Yan Lin; Xiuxiu Liu; Dan Tan; Zhiyan Jiang (Journal of Natural Medicines, 2017)

An amplitude suppression method based on the decibel criterion - Xuan-Lin Kong; Hui Chen; Jin-Long Wang; Zhi-quan Hu; Dan Xu; Lu-Ming Li (Applied Geophysics, 2017)

Kitamycin C, a new antimycin-type antibiotic from Streptomyces antibioticus strain 200-09 - Fan Wang; Shu-Na Fu; Yi-Xuan Bao; Yu Yang; Hui-Fang Shen; Bi-Run Lin; Guang-Xiong Zhou (Natural Product Research, 2017)

Associations of rs3740677 within GAB2 Gene with LOAD in Chinese Han Population - Jing-Yu Zheng; Hui-Fu Wang; Yu Wan; Meng-Shan Tan; Chen-Chen Tan; Lin Tan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Interleukin-18, matrix metalloproteinase-22 and -29 are independent risk factors of human coronary heart disease - Dong-Yi Jin; Cong-Lin Liu; Jun-Nan Tang; Zhao-Zhong Zhu; Xue-Xi Xuan; Xiao-Dan Zhu; Yun-Zhe Wang; Tian-Xia Zhang; De-Liang Shen; Xiao-Fang Wang; Guo-Ping Shi; Jin-Ying Zhang (Journal of Zhejiang University-SCIENCE B, 2017)

Metformin Improves Functional Recovery After Spinal Cord Injury via Autophagy Flux Stimulation - Di Zhang; Jun Xuan; Bin-bin Zheng; Yu-long Zhou; Yan Lin; Yao-sen Wu; Yi-fei Zhou; Yi-xing Huang; Quan Wang; Li-yan Shen; Cong Mao; Yan Wu; et al. (Molecular Neurobiology, 2017)

Effects of HLA-DRB1/DQB1 Genetic Variants on Neuroimaging in Healthy, Mild Cognitive Impairment, and Alzheimer’s Disease Cohorts - Zi-Xuan Wang; Hui-Fu Wang; Lin Tan; Jinyuan Liu; Yu Wan; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Genetic Association of HLA Gene Variants with MRI Brain Structure in Alzheimer’s Disease - Zi-Xuan Wang; Yu Wan; Lin Tan; Jinyuan Liu; Hui-Fu Wang; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Full-length sequence and genome analysis of CHV1-CN280, a North China isolate of cryphonectria hypovirus 1 - Yanan Du; Yuan Lin; Xuan Zhou; Kerong Wang; Shouguo Fang; Qingchao Deng (Archives of Virology, 2017)

Association of DISC1 Polymorphisms with Late-Onset Alzheimer’s Disease in Northern Han Chinese - Xiao-Yan Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Ling-Li Kong; Zhan-Jie Zheng; Chen-Chen Tan; Wei Zhang; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; et al. (Molecular Neurobiology, 2017)

Involvement of FMRP in Primary MicroRNA Processing via Enhancing Drosha Translation - Rui-Ping Wan; Lin-Tao Zhou; Hai-Xuan Yang; Yong-Ting Zhou; Shun-Hua Ye; Qi-Hua Zhao; Mei-Mei Gao; Wei-Ping Liao; Yong-Hong Yi; Yue-Sheng Long (Molecular Neurobiology, 2017)

HLA-A2 Alleles Mediate Alzheimer’s Disease by Altering Hippocampal Volume - Zi-Xuan Wang; Hui-Fu Wang; Lin Tan; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

SORL1 Is Associated with the Risk of Late-Onset Alzheimer’s Disease: a Replication Study and Meta-Analyses - Cheng-Cheng Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

PGRN Is Associated with Late-Onset Alzheimer’s Disease: a Case–Control Replication Study and Meta-analysis - Hui-Min Xu; Lin Tan; Yu Wan; Meng-Shan Tan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Ommaya reservoir in the treatment of cryptococcal meningitis - Baozhu Wei; Cheng Qian; Yang Liu; Xuan Lin; Jing Wan; Yanggan Wang (Acta Neurologica Belgica, 2017)

17-Methoxyl-7-Hydroxy-Benzene-Furanchalcone Ameliorates Myocardial Ischemia/Reperfusion Injury in Rat by Inhibiting Apoptosis and Autophagy Via the PI3K–Akt Signal Pathway - Feifei Xuan; Jie Jian; Xing Lin; Jianchun Huang; Yang Jiao; Wansu Huang; Juman Li; Zhi Shi; Renbin Huang (Cardiovascular Toxicology, 2017)

Fungal spondylodiscitis in a patient recovered from H7N9 virus infection: a case study and a literature review of the differences between Candida and Aspergillus spondylodiscitis - Lie-dao Yu; Zhi-yun Feng; Xuan-wei Wang; Zhi-heng Ling; Xiang-jin Lin (Journal of Zhejiang University-SCIENCE B, 2016)

Variation in nesting behavior of eight species of spider mites, Stigmaeopsis having sociality - Yutaka Saito; Yan-Xuan Zhang; Kotaro Mori; Katsura Ito; Yukie Sato; Anthony R. Chittenden; Jian-Zhen Lin; Younghae Chae; Takane Sakagami; Ken Sahara (The Science of Nature, 2016)

Combined effects of age and polymorphisms in Notch3 in the pathogenesis of cerebral infarction disease - Chun-Yu Zhu; Yue Wang; Qing-Xuan Zeng; Yu Qian; Huan Li; Zi-Xia Yang; Ya-Mei Yang; Qiong Zhang; Fei-Feng Li; Shu-Lin Liu (Metabolic Brain Disease, 2016)

Greenhouse gas emissions and comprehensive greenhouse effect potential of Megalobrama amblycephala culture pond ecosystems in a 3-month growing season - Lin Zhu; Xuan Che; Huang Liu; Xingguo Liu; Chong Liu; Xiaolong Chen; Xu Shi (Aquaculture International, 2016)

Asymmetric synthesis and biological activities of natural product (+)-balasubramide and its derivatives - Jun Li; Jianzu Li; Yuan Xu; Yunjie Wang; Luyong Zhang; Li Ding; Yining Xuan; Tao Pang; Hansen Lin (Natural Product Research, 2016)

Heterologous expression of two Physcomitrella patens group 3 late embryogenesis abundant protein (LEA3) genes confers salinity tolerance in arabidopsis - Jing Du; Lei Wang; Xiaochen Zhang; Xuan Xiao; Fang Wang; Pingliang Lin; Fang Bao; Yong Hu; Yikun He (Journal of Plant Biology, 2016)

IL-17A enhances ADAMTS-7 expression through regulation of TNF-α in human nucleus pulposus cells - Shuai-Shuai Wang; Wei Zhang; Yuan-Qiang Zhang; Yunpeng Zhao; Yi Liu; Jing-kun Li; Hao-xuan Zhang; Lei Cheng; Lin Nie (Journal of Molecular Histology, 2015)

Impact of short-term climate variation and hydrology change on thermal structure and water quality of a canyon-shaped, stratified reservoir - Wei-Xing Ma; Ting-Lin Huang; Xuan Li; Hai-Han Zhang; Tuo Ju (Environmental Science and Pollution Research, 2015)

Posttraumatic spinal cord herniation - Yong Hou; Hao-Xuan Zhang; Xin Pan; Meng Si; Lin Nie (Acta Neurologica Belgica, 2015)

Estimation of residue depletion of cyadox and its marker residue in edible tissues of pigs using physiologically based pharmacokinetic modelling - Lingli Huang; Zhoumeng Lin; Xuan Zhou; Meiling Zhu; Ronette Gehring; Jim E. Riviere; Zonghui Yuan (Food Additives & Contaminants: Part A, 2015)

iMem-Seq: A Multi-label Learning Classifier for Predicting Membrane Proteins Types - Xuan Xiao; Hong-Liang Zou; Wei-Zhong Lin (The Journal of Membrane Biology, 2015)

Characterisation of the dark green islands of cucumber mosaic virus infected Nicotiana tabacum - Li-Juan Chen; Jian Liu; Fei-Fei Zhao; Jing-Yi Li; Sheng-Xuan Wang; Hong-Hui Lin; De-Hui Xi (Plant Cell Reports, 2015)

Prefrontal cortical α2A-adrenoceptors and a possible primate model of attention deficit and hyperactivity disorder - Chao-Lin Ma; Xuan Sun; Fei Luo; Bao-Ming Li (Neuroscience Bulletin, 2015)

Protective Effects of Poly (butyl) Cyanoacrylate Nanoparticles Containing Vasoactive Intestinal Peptide Against 6-Hydroxydopamine-Induced Neurotoxicity In Vitro - Zhi-Ran Xu; Wu-Fang Wang; Xin-Fang Liang; Ze-Hua Liu; Yu Liu; Liang Lin; Xuan Zhu (Journal of Molecular Neuroscience, 2015)

Pharmacokinetic interaction between HCV protease inhibitor boceprevir and methadone or buprenorphine in subjects on stable maintenance therapy - Ellen G. J. Hulskotte; R. Douglas Bruce; Hwa-Ping Feng; Lynn R. Webster; Feng Xuan; Wen H. Lin; Edward O’Mara; John A. Wagner; Joan R. Butterton (European Journal of Clinical Pharmacology, 2015)

Stress signaling in response to polycyclic aromatic hydrocarbon exposure in Arabidopsis thaliana involves a nucleoside diphosphate kinase, NDPK-3 - Hong Liu; David Weisman; Ling Tang; Long Tan; Wen-ke Zhang; Zong-hua Wang; Yan-he Huang; Wen-xiong Lin; Xuan-ming Liu; Adán Colón-Carmona (Planta, 2015)

A chimeric antibody targeting CD147 inhibits hepatocellular carcinoma cell motility via FAK-PI3K-Akt-Girdin signaling pathway - Yuan Wang; Lin Yuan; Xiang-Min Yang; Ding Wei; Bin Wang; Xiu-Xuan Sun; Fei Feng; Gang Nan; Ye Wang; Zhi-Nan Chen; Huijie Bian (Clinical & Experimental Metastasis, 2015)

Effects and Mechanism of Action of Ligustrazine on Isoprenaline-Induced Cardiomyocyte Hypertrophy - Xuan Xiu Ji; Xiao Li Song; Wei Qian; Xiao Lin Yu; Jian You Zhu (Cell Biochemistry and Biophysics, 2014)

Re-Transurethral Resection Treatment for Non-invasive Bladder Tumor - Cong-hui Han; Zhenduo Shi; Xujun Xuan; Bo Chen; Bingzheng Dong; Lin Hao; Xiangzheng Qiu; Xiangju Zhou; Tian-lin Wu; Dong Liu (Cell Biochemistry and Biophysics, 2014)

G Protein-Coupled Estrogen Receptor–Protein Kinase A–ERK–CREB Signaling Pathway is Involved in the Regulation of Mouse Gubernaculum Testis Cells by Diethylstilbestrol - Xuan Zhang; Jian-hong Li; Shou-xing Duan; Qing-Jun Lin; Song Ke; Lian Ma; Tian-hua Huang; Xue-wu Jiang (Archives of Environmental Contamination and Toxicology, 2014)

Unpalatable weed Stellera chamaejasme L. provides biotic refuge for neighboring species and conserves plant diversity in overgrazing alpine meadows on the Tibetan Plateau in China - Wei Cheng; Geng Sun; Lin-fang Du; Yan Wu; Qun-ying Zheng; Hong-xuan Zhang; Lin Liu; Ning Wu (Journal of Mountain Science, 2014)

CD24 mediates gastric carcinogenesis and promotes gastric cancer progression via STAT3 activation - Ying-Chao Wang; Ji-Lin Wang; Xuan Kong; Tian-Tian Sun; Hao-Yan Chen; Jie Hong; Jing-Yuan Fang (Apoptosis, 2014)

Genes in the serotonin pathway are associated with bipolar affective disorder in a Han Chinese population - Bo Xiang; Zhenxing Yang; Yin Lin; Lijie Guan; Xuan Li; Wei Deng; Zeyu Jiang; Guohui Lao; Qiang Wang; Xiaoyu Hao; Xiang Liu; Yingcheng Wang; et al. (Neuroscience Bulletin, 2014)

Forced expression of indoleamine-2,3-dioxygenase in human umbilical cord-derived mesenchymal stem cells abolishes their anti-apoptotic effect on leukemia cell lines in vitro - Yin Yuan; Xin Lu; Chang-li Tao; Xuan Chen; Hong-wei Shao; Shu-lin Huang (In Vitro Cellular & Developmental Biology - Animal, 2013)

Continental flood basalts of the Huashan Group, northern margin of the Yangtze block – implications for the breakup of Rodinia - Qi Deng; Jian Wang; Zheng-Jiang Wang; Xuan-Ce Wang; Yan-Sheng Qiu; Qing-Xiong Yang; Qiu-Ding Du; Xiao-Zhuang Cui; Xiao-Lin Zhou (International Geology Review, 2013)

Preladenant, a selective adenosine A2A receptor antagonist, is not associated with QT/QTc prolongation - Z. Wang; F. Xuan; W. H. Lin; M. D. Troyer; A. Tendolkar; D. L. Cutler (European Journal of Clinical Pharmacology, 2013)

Isolation and characterization of polymorphic microsatellite loci in Ping’s juniper Juniperus pingii - Zhong-Hu Li; Zhan-Lin Liu; Yu-Jin Wang; Min-Feng Fang; Ma-Li Wang; Zhi-Xuan Li; Gui-Fang Zhao (Conservation Genetics Resources, 2013)

Al-enhanced Expression and Interaction of 14-3-3 Protein and Plasma Membrane H+-ATPase is Related to Al-induced Citrate Secretion in an Al-resistant Black Soybean - Chuan-Long Guo; Qi Chen; Xiu-Ling Zhao; Xuan-qian Chen; Yan Zhao; Lin Wang; Kui-Zhi Li; Yong-Xiong Yu; Li-Mei Chen (Plant Molecular Biology Reporter, 2013)

Effects of single and combined genotypes of MC4R and POU1F1 genes on two production traits in Langshan chicken - Lin Jun Yan; Xing Tang Fang; Yao Liu; Chun Lei Zhang; Xuan Xuan Liu; Jing Zhao; Jing Jing Li; Hong Chen (Molecular Biology Reports, 2013)

Combined action of antioxidant defense system and osmolytes in chilling shock-induced chilling tolerance in Jatropha curcas seedlings - Zhong-Guang Li; Ling-Xuan Yuan; Qiu-Lin Wang; Zhi-Liu Ding; Chun-Yan Dong (Acta Physiologiae Plantarum, 2013)

Adhesion of osteoblast-like cell on silicon-doped TiO2 film prepared by cathodic arc deposition - Bing Wang; Jun-Ying Sun; Shi Qian; Xuan-Yong Liu; Shai-Lin Zhang; Sheng-Jie Dong; Guo-Chun Zha (Biotechnology Letters, 2013)

Selenium Attenuates Adriamycin-Induced Cardiac Dysfunction via Restoring Expression of ATP-Sensitive Potassium Channels in Rats - Zhong-Wei Liu; Xiao-Lin Niu; Kun-Lun Chen; Yu-Jie Xing; Xuan Wang; Chuan Qiu; Deng-Feng Gao (Biological Trace Element Research, 2013)

Levosimendan versus dobutamine in critically ill patients: a meta-analysis of randomized controlled trials - Xuan Huang; Shu Lei; Mei-fei Zhu; Rong-lin Jiang; Li-quan Huang; Guo-lian Xia; Yi-hui Zhi (Journal of Zhejiang University-SCIENCE B, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Orchid fleck virus: an unclassified bipartite, negative-sense RNA plant virus - De Wei Peng; Guo Hua Zheng; Zhi Zhong Zheng; Qing Xuan Tong; Yan Lin Ming (Archives of Virology, 2013)

Efficient multi-site-directed mutagenesis directly from genomic template - Fengtao Luo; Xiaolan Du; Tujun Weng; Xuan Wen; Junlan Huang; Lin Chen (Journal of Biosciences, 2012)

Isolation and Characterization of a Novel Noncoding RNA from Nickel-Induced Lung Cancer - Jing Zhang; Yang Zhou; Youjun Wu; Lin Ma; Yingying Fan; Xuan Kang; Hongjun Shi; Jun Zhang (Biological Trace Element Research, 2012)

Effects of heavy metals on the expression of a zinc-inducible metallothionein-III gene and antioxidant enzyme activities in Crassostrea gigas - Ming Cong; Huifeng Wu; Xiaoli Liu; Jianmin Zhao; Xuan Wang; Jiasen Lv; Lin Hou (Ecotoxicology, 2012)

Highly Sensitive Detection of Residual Chlorpromazine Hydrochloride with Solid Substrate Room Temperature Phosphorimetry - Jia-Ming Liu; Li-ping Lin; Xin-Xing Wang; Xuan Lin; Ping Zhou; Shao-Qin Lin; Zhi-Yong Zheng (Journal of Fluorescence, 2012)

A new insect cell line from pupal ovary of Spodoptera exigua established by stimulation with N-methyl-N′-nitro-N-nitrosoguanidine (MNNG) - Xuan Li; Qilian Qin; Ning Zhang; Wei Zhu; Jihong Zhang; Hongtuo Wang; Lin Miao; Huan Zhang (In Vitro Cellular & Developmental Biology - Animal, 2012)

Anti-tumor Function of Double-promoter Regulated Adenovirus Carrying SEA Gene, in the Treatment of Bladder Cancer - Jianpeng Hu; Xujun Xuan; Conghui Han; Lin Hao; Peiying Zhang; Meng Chen; Houguang He; Tao Fan; Binzheng Dong (Cell Biochemistry and Biophysics, 2012)

The proportions and variations of the light absorption coefficients of major ocean color components in the East China Sea - Hui Lei; Delu Pan; Yan Bai; Bangyi Tao; Jun Sun; Lin Zhang; Xuan Zhang (Acta Oceanologica Sinica, 2012)

A Novel Mutation in CACNA1S Gene Associated with Hypokalemic Periodic Paralysis Which has a Gender Difference in the Penetrance - Fei-Feng Li; Qian-Qian Li; Zhen-Xuan Tan; Si-Yao Zhang; Ji Liu; Er-ying Zhao; Gui-Chun Yu; Jin Zhou; Li-Ming Zhang; Shu-Lin Liu (Journal of Molecular Neuroscience, 2012)

Implementation of a Fast-Track Clinical Pathway Decreases Postoperative Length of Stay and Hospital Charges for Liver Resection - De-Xin Lin; Xuan Li; Qi-Wen Ye; Fen Lin; Lin-Li Li; Qi-Yu Zhang (Cell Biochemistry and Biophysics, 2011)

Biofilm-electrode process with high efficiency for degradation of 2,4-dichlorophenol - Xue-Na Zhang; Wei-Min Huang; Xuan Wang; Huiting Li; Hai-Yan Lu; Hai-Bo Lin (Environmental Chemistry Letters, 2011)

Establishment of a cerebral schistosomiasis experimental model in rabbits - Peng Wang; Dan Wang; Shi-Jie Chen; Ming-Can Wu; Xiang-Lin Cheng; Jun-Chuan Li; Ting-Xuan Chen; Zhan-Sheng Zhu (Neuroscience Bulletin, 2011)

Investigation of the Interaction Between the Ser447Term Polymorphism of Lipoprotein Lipase and the Stroke-Related Risk Factors in Ischemic Stroke - Yumei Yang; Danhua Du; Peng Gao; Xuan Zhang; Ning Wu; Feng Wang; Zhenqi Wang; Lin Ye; Jiang Wu; Ian L. Megson; Jun Wei (Translational Stroke Research, 2011)

Characterization of Outer Membrane Proteins of Escherichia Coli in Response to Phenol Stress - Dan-Feng Zhang; Hui Li; Xiang-Min Lin; San-Ying Wang; Xuan-Xian Peng (Current Microbiology, 2011)

Over-expression of the AtGA2ox8 gene decreases the biomass accumulation and lignification in rapeseed (Brassica napus L.) - Xiao-ying Zhao; Deng-feng Zhu; Bo Zhou; Wu-sheng Peng; Jian-zhong Lin; Xing-qun Huang; Re-qing He; Yu-hong Zhuo; Dan Peng; Dong-ying Tang; Ming-fang Li; Xuan-ming Liu (Journal of Zhejiang University-SCIENCE B, 2010)

The Chebyshev spectral element method using staggered predictor and corrector for elastic wave simulations - Cheng-Xuan Che; Xiu-Ming Wang; Wei-Jun Lin (Applied Geophysics, 2010)

Fine mapping and candidate gene analysis of spd6, responsible for small panicle and dwarfness in wild rice (Oryza rufipogon Griff.) - Jun-Xiang Shan; Mei-Zhen Zhu; Min Shi; Ji-Ping Gao; Hong-Xuan Lin (Theoretical and Applied Genetics, 2009)

Activity of the Antimicrobial Peptide and Thanatin Analog S-thanatin on Clinical Isolates of Klebsiella pneumoniae Resistant to Conventional Antibiotics with Different Structures - Guo-Qiu Wu; Jia-Xuan Ding; Lin-Xian Li; Hai-liang Wang; Rui Zhao; Zi-Long Shen (Current Microbiology, 2009)

A 70-kDa molecular chaperone, DnaK, from the industrial bacterium Bacillus licheniformis: gene cloning, purification and molecular characterization of the recombinant protein - Wan-Chi Liang; Xuan-Hui Wang; Min-Guan Lin; Long-Liu Lin (Indian Journal of Microbiology, 2009)

A cell strain cloned from Spodoptera exigua cell line (IOZCAS-Spex-II) highly susceptible to S. exigua nucleopolyhedrovirus infection - Huan Zhang; Yong-an Zhang; Qilian Qin; Xuan Li; Lin Miao; Yuzhu Wang; Liangjian Qu; Aijun Zhang; Qing Yang (In Vitro Cellular & Developmental Biology - Animal, 2009)

Role of desert annuals in nutrient flow in arid area of Northwestern China: a nutrient reservoir and provider - Bao-Ming Chen; Gen-Xuan Wang; Shao-Lin Peng (Plant Ecology, 2009)

Expression and purification of Zantedeschia aethiopica agglutinin in Escherichia coli - Ling Lin; Xue-Fen Liu; Ling-Chuan Hu; Yin Zhou; Xiao-Fen Sun; Ke-Xuan Tang (Molecular Biology Reports, 2009)

A Novel RUNX2 Mutation in Cleidocranial Dysplasia Patients - Dongying Xuan; Shi Li; Xiong Zhang; Lixin Lin; Chunxian Wang; Jincai Zhang (Biochemical Genetics, 2008)

Overexpression of the trehalose-6-phosphate phosphatase gene OsTPP1 confers stress tolerance in rice and results in the activation of stress responsive genes - Liang-Fa Ge; Dai-Yin Chao; Min Shi; Mei-Zhen Zhu; Ji-Ping Gao; Hong-Xuan Lin (Planta, 2008)

Cloning and expression of selenocysteine methyltransferase cDNA from Camellia sinensis - Lin Zhu; Chang-Jun Jiang; Wei-Wei Deng; Xuan Gao; Rang-Jian Wang; Xiao-Chun Wan (Acta Physiologiae Plantarum, 2008)

Phase velocity in 2D TTI media - Yihua Xuan; Qiaodeng He; Yan Lin (Applied Geophysics, 2007)

Construction and characterization of a bacterial artificial chromosome library of marine macroalgaPorphyra yezoensis (Rhodophyta) - Dai Yong Deng; Ge Zhao; Jin Song Xuan; Ji Liang Yang; Lin De Duan; Man Li Weng; Bin Wang (Plant Molecular Biology Reporter, 2004)

Potential biological control of weeds in rice fields by allelopathy of dwarf lilyturf plants - Dongzhi Lin; Eiji Tsuzuki; Yanjun Dong; H. Terao; T.D. Xuan (BioControl, 2004)

Relationship between resort life cycle and residents’ perception and attitude - Xiao-zhong Yang; Lin Lu; Guang-sheng Zhang; Song Lu; Guo-fu Xuan (Chinese Geographical Science, 2004)

The Arterial Supply of the Carpal Joint in the Bactrian Camel (Camelus Bactrianus) - Jian-Lin Wang; Cui-Sheng; Gen-Xuan Wang; Hai-Yan Li (Veterinary Research Communications, 2000)

Arrestment response of the predatory mite Amblyseius longispinosus to Schizotetranychus nanjingensis webnests on bamboo leaves (Acari: Phytoseiidae, Tetranychidae) - Yan-Xuan Zhang; Jie Ji; Zhi-Qiang Zhang; Jian-Zhen Lin (Experimental and Applied Acarology, 2000)

The Arterial Supply of the Cubital Joint in the Bactrian Camel (Camelus bactrianus) - Jian-Lin Wang; Gao-Lan; Cui-Sheng; Gen-Xuan Wang; Hai-Yan Li (Veterinary Research Communications, 2000)